La formation du contrat électronique : dispositif légal (répressif) de protection du cyberconsommateur et modes alternatifs de règlement des conflits (M.A.R.C.) - Diallo, Boubacary (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
L’objectif principal de cette étude est de révéler le dispositif légal répressif de protection du cyberconsommateur. Les résultats de cette étude montrent que le législateur malien, communautaire, sous régional et régional y compris, ont misé beaucoup sur la protection des cyberconsommateurs, en adoptant une politique qui s’articule principalement sur la confidentialité, la protection de la vie privée, la protection de la propriété intellectuelle, et le règlement des conflits par les modes alternatifs de règlement des conflits (M.A.R.C.) déclenchés entre les différentes parties de la transaction en ligne.
Keywords: Contrat électronique; Cyberconsommation; E-commerce; MARC; Règlement des conflits

Arbitration and state sovereignty in commercial disputes resolution within ohada laws - Buma, Roland Sigala; Biya, Fabilou (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Long ago before the creation of the state courts, men had resorted to arbitration for the resolution of diputes. Today, based on the principle of monopoly of the state to render justice, the power to judge is given only to the state. Rendering of justice is one of the areas where the state exeercises its sovereign powers. This has made us to ask the question : is arbitration a violation of the sovereignty of the state in the domain of dispute resolution ? Arbitration is not a violation of the sovereign powers of the state because, it is not all disputes that are resolved via arbitration (for example, crimnal, tax disputes etc can not be settled via arbitration) and the state courts intervene in arbitratin when ever it is necessary. The sate courts intervene in arbitration to grant exequatur, order interim mesaures etc. Nonetheless, since OHADA legislator has not given a complete list of all disputes that can not be resolve via arbitration, we recomend that OHADA should provide a list of all disputes whcih can be settle via arbitration as it is the case with the Arbitration Act of Zimbabw. This article aims at identifying those cases that can not be settled by way of arbitration and those instances in which the state courts intervene in arbitration. Avant la création des tribunaux étatiques, les hommes ont eu recours à l'arbitrage pour la résolution des litiges. Aujourd'hui, sur la base du principe du monopole de l'État à rendre la justice, le pouvoir de juger n'est conféré qu'à l'État. Le fait de rendre la justice est l'un des domaines dans lesquels l'État exerce ses pouvoirs souverains. Cela nous a amenés à poser la question : l'arbitrage constitue-t-il une violation de la souveraineté de l'État dans le domaine du règlement des différends ? L'arbitrage n'est pas une violation des pouvoirs souverains de l'État car, d'une part, tous les litiges ne sont pas résolus par voie d'arbitrage (par exemple, les litiges pénaux, fiscaux, etc. ne peuvent pas être réglés par arbitrage) et, d'autre part, les tribunaux étatiques interviennent dans l'arbitrage chaque fois que cela est nécessaire. Les tribunaux étatiques interviennent dans l'arbitrage pour accorder l'exequatur, ordonner des mesures provisoires, etc. Néanmoins, étant donné que le législateur de l'OHADA n'a pas établi une liste exhaustive de tous les litiges qui ne peuvent pas être résolus par arbitrage, nous recommandons que l'OHADA fournisse une liste de tous les litiges qui peuvent être réglés par voie d'arbitrage, comme c'est le cas dans la loi sur l'arbitrage du Zimbabwe. Cet article vise à identifier les litiges qui ne peuvent pas être réglés par voie d'arbitrage ainsi que les situations dans lesquelles les tribunaux étatiques interviennent dans l'arbitrage.
Keywords: Arbitrage; Arbitrage commerciale; Arbitragem; Arbitraje; Arbitration; Commercial disputes; Droit OHADA; Litiges commerciaux; OHADA law; Souveraineté; Sovereignty

Réflexion sur la procédure de médiation de l’acte uniforme de l’OHADA relatif à la Médiation (AUM) - Adjita, Shamsidine Akrawati (Revue Internationale de Droit et Science Politique, 2025)
La médiation n’est pas une invention du législateur de l’OHADA. Elle est aussi vieille que le monde. Sa consécration légale à travers l’Acte uniforme relatif à la médiation met en évidence son importance dans la résolution des litiges à l’amiable dans l’ordonnancement juridique de l’OHADA. Cela s’explique car la médiation renvoie à l’idée de justice. Le sentiment de justice n’est pas lié à une époque, il est plutôt inhérent à l’existence humaine et porte en lui-même une exigence, une valeur fondamentale universellement reconnue. Il s’agit du droit à la justice dont le respect permet d’apprécier de façon efficiente les valeurs auxquelles une société est attachée. Toute société a besoin de justice, mais elle ne peut la rendre de façon satisfaisante avec le procédé traditionnel qu’est le jugement. Le juge ne peut pas tout. Le bon sens dicte de l’éviter. Selon un adage populaire, « un mauvais accord vaut mieux qu’un bon procès ». Là où il y a une société, il y a des différends. Là où il y a des différends, il y a des modes de règlement des différends parmi lesquels la médiation occupe une place de choix. Avatar médiatisé de la justice consensuelle, panacée de la déjudiciarisation et de la déjuridicisation, la médiation est parée de toutes les vertus pour éviter le procès. Elle apparaît donc comme une alternative à laquelle peuvent recourir les parties en conflit pour régler leur malentendu à l’amiable tout en préservant leurs relations d’affaires. Elle n’est pas une procédure laissée à l’appréciation du juge, mais plutôt à celle des parties en conflit qui en sont les principales actrices. Cependant elles ne peuvent parvenir à la résolution de leur litige que par l’intermédiaire d’un tiers appelée médiateur et sans lequel la procédure serait incomplète. On a donc, d’un côté, les parties à la médiation qui la considèrent comme étant leur affaire et, de l’autre, le médiateur qui est considéré comme le chef d’orchestre de la procédure. Mediation is not an invention of the OHADA legislator. It is as old as the world itself. Its legal recognition through the Uniform Act on Mediation highlights its importance in the amicable resolution of disputes within the OHADA legal system. This is because mediation refers to the idea of justice. The sense of justice is not tied to a particular era; rather, it is inherent to human existence and carries with it a requirement, a universally recognized fundamental value. It is the right to justice, respect for which allows for the efficient appreciation of the values to which a society is attached. Every society needs justice, but it cannot deliver it satisfactorily through the traditional process of judgment. Judges cannot do everything. Common sense dictates that it should be avoided. According to a popular saying, “a bad agreement is better than a good trial.” Where there is society, there are disputes. Where there are disputes, there are ways of resolving them, among which mediation occupies a prominent place. As the media-friendly face of consensual justice and the panacea for reducing court cases and legal proceedings, mediation is seen as the ideal way to avoid litigation. It therefore appears to be an alternative that parties in conflict can use to settle their differences amicably while preserving their business relationships. It is not a procedure left to the discretion of the judge, but rather to that of the parties in conflict, who are the main actors. However, they can only resolve their dispute through a third party called a mediator, without whom the procedure would be incomplete. On the one hand, therefore, we have the parties to the mediation, who consider it to be their business, and on the other, the mediator, who is considered to be the conductor of the procedure.
Keywords: Acte uniforme; Judge; Juge; Mediation; Mediator; Médiateur; Médiation; Parties en conflit; Parties to the dispute; Uniform Act

La revalorisation des mécanismes locaux de prévention et de gestion des conflits au Mali : une valeur ajoutée inestimable pour le système judiciaire moderne - Yalcouyé, Seydou; Dolo, Anidjou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
La cohabitation entre les mécanismes modernes et traditionnels de prévention et de gestion des conflits au Mali (notamment dans en milieu rural) est une réalité. Entre les mécanismes modernes et les mécanismes traditionnels, le choix des communautés porte essentiellement sur les seconds ; quoique les premiers ne sont pas non plus en abandon. Comme raisons avancées pour justifier leur choix, elles considèrent de façon générale que le recours aux mécanismes modernes ne permet pas de vider totalement leur contentieux. Les communautés trouvent que ces mécanismes modernes rendent leurs conflits plus complexes et plus difficiles à gérer. D’où la méfiance du règlement administratif ou judiciaire des conflits car trop couteux et aux procédures trop complexes. Sur la base de ces constats, il reste permis de constater la nécessité de réaliser des compromis entre mécanismes modernes et mécanismes traditionnels de gestion des conflits en revalorisant davantage les seconds. Seul à ce prix que les défis de la décentralisation (gouvernance locale) et ceux de la démocratie seront relevés. The coexistence of modern and traditional conflict prevention and management mechanisms in Mali (particularly in rural areas) is a reality. Compared to modern and traditional mechanisms, communities primarily choose the latter; although they have not abandoned the former either. As reasons given to justify their choice, they generally consider that resorting to modern mechanisms does not completely resolve their disputes. Communities find that these modern mechanisms make their conflicts more complex and more difficult to manage. Hence their distrust of administrative or judicial conflict resolution, as they are too costly and require overly complex procedures. Based on these observations, it remains clear that compromises must be made between modern and traditional conflict management mechanisms by further revaluing the latter. Only in this way will the challenges of decentralization (local governance) and democracy be met.
Keywords: Autorité traditionnelle; Conflict management; Conflict prevention; Gestion des conflits; Gouvernance locale; Local governance; Légitimité traditionnelle; Prévention des conflits; Traditional authorities; Traditional legitimacy

The Interpretation of UNCITRAL Law in Australian Courts: A Roadmap for Elevating the UN Sales Convention’s Status to That of Arbitration Law - Hayward, Benjamin (Sydney Law Review, 2025)
Despite being part of Australian law for more than 30 years, the United Nations Convention on Contracts for the International Sale of Goods (‘CISG’) has not secured the internationally minded interpretation that CISG art 7(1) requires. Australia’s international commercial arbitration (‘ICA’) laws, however, are routinely approached by Australian courts with an internationalist perspective, as their own interpretative rules require. It is tempting to conclude that Australia’s approach to interpreting its ICA laws is transferable to the CISG context. In this article I address a previously unexplored nuance affecting that conclusion. Australian courts routinely accept Singaporean, Hong Kong and New Zealand interpretative influence concerning ICA laws. In the CISG context, however, significantly less influence from those jurisdictions exists. That being so, I explore how Australia’s courts might better apply the CISG in an internationalist manner. First, I recommend that Australia’s courts emphasise to practitioners the need to consider the CISG’s application and its internationalist interpretation requirements. Second, I recommend that Australian courts use the amicus curiae procedure to solicit third party submissions addressing the CISG’s interpretation. Both techniques are applied by foreign courts in the ICA context and would assist Australian courts in discharging their CISG art 7(1) obligations.
Keywords: Asia-Pacific; Australia; CISG; Harmonisation; International commercial arbitration; Model Law; New York Convention; Sales law; Statutory interpretation

El arbitraje como justicia alternativa y eficaz - Nieto, Gastón Fabricio Correa (Polo del Conocimiento, 2025)
El presente ensayo surge de la experiencia del ejercicio profesional de la abogacía en la que en el ámbito judicial, extrajudicial, donde se ha observado diferentes vicisitudes en el desarrollo y ejecución de procesos judiciales, generando de esta forma ineficiencia en la administración de justicia; para lo cual como alternativa viable surgen los métodos alternativos de solución de conflictos con la promulgación de la Ley de Arbitraje y Mediación surgen en septiembre de 1997 como una opción ante la deficiente administración de Justicia.Sin embargo, esta ineficiencia procesal representa a su vez un obstáculo real para su ejercicio efectivo de derechos, especialmente obtener “justicia” para los ciudadanos que enfrentan demoras prolongadas y procedimientos burocráticos que terminan por vulnerar sus derechos. Uno de los objetivos del artículo es la de establecer las medidas efectivas que se pueden adoptar en instancia extrajudicial y elementos necesarios alcanzar la tan preciada “Justicia” siendo esta “la constante y perpetua voluntad de dar a cada quien lo que le corresponde” (Ulpiano, 2015).
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Deficiencia judicial; Justicia; Negligencia; Retardo

Comercio sostenible y arbitraje internacional: un enlace estratégico para la resolución de conflictos - León, Jorge Guillermo Cedeño; Erazo, Angie Gabriela Sánchez (Polo del Conocimiento, 2025)
El arbitraje internacional ha emergido como una herramienta clave para la resolución de controversias en el comercio sostenible, ofreciendo un marco eficiente y flexible. Este estudio analiza el uso del arbitraje en casos relacionados con comercio y sostenibilidad, evaluando su efectividad en la promoción de prácticas comerciales responsables.
Keywords: Arbitrage international; Arbitraje internacional; Comercio sostenible; Commerce durable; International commercial arbitration; Prácticas responsables; Resolución de controversias; Sostenibilidad

Impacto de las tecnologías emergentes en la confidencialidad y transparencia del arbitraje internacional - Pérez-Pacheco, Yaritza; Lee, Díckar Bonyuet (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
El arbitraje comercial internacional enfrenta el desafío de integrar tecnologías emergentes como la inteligencia artificial, el Big Data y el blockchain, sin comprometer sus principios fundamentales de confidencialidad y transparencia. Este artículo analiza, a partir de una revisión documental y comparativa, cómo el uso de estas tecnologías im-pacta la gestión de casos, el análisis predictivo y la ejecución de laudos, al tiempo que mejora la eficiencia y accesibilidad del arbitraje, pero también genera riesgos en materia de privacidad, ciberseguridad y protección de datos sensibles. Asimismo, se analizan los enfoques regulatorios adoptados en distintas jurisdicciones, incluyendo el Reglamento de la Unión Europea, el modelo flexible de Estados Unidos y las iniciativas tecnológi-cas de países asiáticos como China y Hong Kong. La investigación concluye que, para equilibrar la innovación y la protección de la información, es indispensable implementar protocolos globales y estándares éticos que garanticen un arbitraje confiable y seguro en entornos digitales. International commercial arbitration faces the challenge of integrating technologies such as artificial intelligence, Big Data, and blockchain, without undermining confidentiality and transparency. This article examines how these tools impact case management, predictive analysis, and the enforcement of awards, improving efficiency while also raising concerns about privacy and cybersecurity. Regulatory approaches are explored, from the European Union’s framework to the more flexible model of the United States and technological initiatives in Asia. The research concludes that it is essential to establish global and ethical standards to ensure a secure and reliable arbitration process in the digital era.
Keywords: Arbitrage; Arbitragem; Arbitraje internacional; Arbitral award enforcement; Arbitration; Confidentiality; Confidentialité; Ejecución de laudos arbitrales; Emerging technologies; International arbitration; International dispute resolution; Resolución internacional de disputas; Tecnologías emergentes; Transparence; Transparency

Transparency in Investor-State Arbitration Under USMCA - Petrova Georgieva, Virdzhiniya (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
The provisions of USMCA and their interpretation and application in the developing case law of international arbitral tribunals constituted under its investment chapter show a progressive move towards a higher transparency standard in the resolution of inves-tor-State disputes. The incorporation of most of the UNCITRAL Rules on Transparen-cy in USMCA Annex 14-D expanded the scope of NAFTA’s transparency rules. The entry into force of USMCA and the recent end of NAFTA’s “legacy claims” is to bring normative uniformity across the case law of arbitral tribunals on issues of procedural transparency. In addition, better access to arbitral orders and awards under USMCA will promote the quality of the decisions, as tribunals and parties will be able to lean on the experience of their predecessors. Las disposiciones del T-MEC y su aplicación en la jurisprudencia arbitral internacional muestran un avance hacia mayores estándares de transparencia en disputas inversionista-Estado. Al incorporar la mayoría de las Reglas de Transparencia de la CNUDMI en su Anexo 14-D, el T-MEC amplió el marco del TLCAN. La entrada en vigor del T-MEC y el fin de las “reclamaciones heredadas” del TLCAN promueven una mayor uniformidad normativa en torno a la transparencia procesal. Esta coherencia fortalecerá la aceptación del capítulo de inversión del T-MEC y aumentará la legitimidad del arbitraje de inversiones a nivel global.
Keywords: Arbitraje internacional de inversiones; Arbitrajes entre Inversionistas y Estados; CNUDMI; International Investment Arbitration; NAFTA; Procedural transparency; T-MEC; TLCAN; Transparencia procedimental; UNCITRAL Rules on Transparency; USMCA

La transparencia en el arbitraje internacional: avances y nuevos retos - Pollero, Marianela Bruno (Jurídica Ibero: Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
Este artículo responde a la propuesta académica del Departamento de Derecho de la Uni-versidad Iberoamericana en conmemoración del 10.° aniversario de las normas de trans-parencia de la Comisión de las Naciones Unidas para el Derecho Mercantil (CNUDMI) y complementa la actividad académica realizada por la Universidad Iberoamericana, la Secretaría de Relaciones Exteriores de México y el Centro de Mediación y Arbitraje de la Cámara de Comercio de la Ciudad de México (CANACO), con el apoyo de la Secre-taría de la CNUDMI, en el marco del UNCITRAL LAC DAYS- México 2024. Durante esta actividad se organizaron tres mesas de debate integradas por desta-cados miembros de la comunidad arbitral, de la sociedad civil y del sector privado. La temática de estudio brindó desde México una visión sobre la confidencialidad vs. la transparencia, así como los avances y los retos de la transparencia en el arbitraje inter-nacional.
Keywords: Arbitrage international; Arbitragem Internacional; Arbitraje internacional; Arbitration; Transparence (droit); Transparencia

Reflexiones sobre el régimen de transparencia en el arbitraje comercial internacional - Rendón, Martha Angélica Alvarez (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
From an approach to the concepts of transparency, confidentiality, and privacy, this article examines the tension that may arise between these principles in international commercial arbitration. It also analyzes how arbitration rules address confidentiality and transparency, questioning whether a balance between the two has been achieved. Additionally, it reflects on the impact of public interest in promoting transparency in arbitral proceedings, considering whether the measures adopted are compatible with this type of arbitration. Desde un acercamiento a las nociones de transparencia, confidencialidad y privacidad, en este artículo se valora la tensión que puede existir entre dichos conceptos en el arbi-traje comercial internacional. Asimismo, se alude a algunos reglamentos de arbitraje que abordan la confidencialidad y la transparencia, parar mostrar si se alcanza un equilibrio entre los principios analizados. Además, se llama a reflexionar sobre el impacto del inte-rés público en la búsqueda de la transparencia en los procesos arbitrales, con la finalidad de abrir el debate sobre la compatibilidad de las medidas que se han adoptado en este rubro en el arbitraje comercial.
Keywords: Arbitrage; Arbitragem; Arbitraje comercial internacional; Arbitraje de inversión; Arbitration; Confidencialidad; Confidentiality; International commercial arbitration; Interés público; Investment arbitration; Privacidad; Privacy; Public interest; Transparence; Transparencia; Transparency

Les ADR comme mécanismes de gestion des différends sociaux et environnementaux dans les grands projets miniers au Cameroun - Abane Engolo, Patrick Edgard; Abomo Efoua, Christiane (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Les grands projets miniers sont porteurs d’enjeux économiques, sociaux, et environnementaux au Cameroun. L’exploitation minière est dans ce sens juridiquement encadrée par le Code minier. Elle implique autant d’opportunités que de risques susceptibles d’engendrer des différends sociaux et environnementaux. La gestion de ces différends implique la convocation des Alternative Dispute Resolution (ADR), qui constituent une voie d’accès à la résolution des litiges aussi importante que la saisine du juge. Cependant, l’apparente libéralité de ces ADR suscite des inquiétudes quant à l’efficacité de leur mise en œuvre et leur force juridique. Il en ressort que, bien que ces mécanismes soient consacrés, leur encadrement juridique nécessite d’être renforcé. Major mining projects pose economic, social and environmental challenges in Cameroon. Mining operations are therefore legally regulated by the Mining Code. They present both opportunities and risks that can lead to social and environmental disputes. Managing these disputes therefore requires the convening of Alternative Dispute Resolution (ADR) mechanisms, which constitute a means of accessing justice as important as going to court. However, the apparent liberality of these ADR mechanisms raises concerns about the effectiveness of their implementation and their legal force. It appears that although these mechanisms are established, their legal framework needs to be strengthened.
Keywords: Arbitrage; Arbitration; Conciliation; Mediation; Médiation; Parties prenantes; Stakeholders

L’apport du juge à l’autorité de la chose jugée de la sentence arbitrale en contentieux du sport au Cameroun - Mandeng, Naomie Audrey (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Par le truchement de la résolution des litiges nés du mouvement et des acteurs sportifs, le juge statuant dans le contentieux sportif se préoccupe également de l’applicabilité de ses décisions juridictionnelles. Sauf que l’on ne devrait pas généraliser le poids de celle-ci sur tous les cas rendus par le juge sportif. Se voulant intelligible ce dernier l’acuité de l’autorité de chose jugée face à certains incidents de procédure. Cette négation est davantage entretenue par des modalités spécifiques. Par ailleurs, dans son énoncé, le juge sportif prescrit de se référer au dispositif pour dériver prosaïquement les termes de l’autorité de chose jugée et la force exécutoire de la sentence arbitrale.
Keywords: Autorité de la chose jugée; Cameroun; Juge; Sentence arbitrale; Sport

Libres propos sur la volonté des parties dans l’arbitrage OHADA - Waham Mayegle, Joseph Laurent (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
L’arbitrage est une réalité en Afrique depuis longtemps déjà. C’est avec l’avènement de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires que ce domaine a pu avoir un dispositif bien structuré. Etant un mode alternatif de règlement des différends, l’arbitrage a pour fondement prépondérant la volonté des parties qui y font recours. Il s’est donc posé en filigrane la question de la portée de la volonté des parties à l’arbitrage OHADA. Le constat est que tout comme en matière contractuelle, elle est un élément indispensable à l’efficacité de ce mode de résolution des litiges. C’est la raison pour laquelle sa portée est traduite par une prégnance avérée, et un recul tout de même constaté.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Volonté des parties

La seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario - Muñoz, Nohely Alejandra Zambrano; Pacheco, Marco Antonio Acosta; Reyes, Eloísa Carolina Solís; Parra, José Antonio Velez (Polo del Conocimiento, 2025)
El estudio de la seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario tuvo como objetivo analizar la incidencia de la seguridad jurídica en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario como garantía de los procesos judiciales. Para lo cual, se utilizó una investigación de tipo desriptiva y de campo, con un enfoque mixto y el método hermenéutico; para la recopilación de información primaria se aplicó una encuesta y entrevista a los juristas en libre ejercicio de su profesión. Se obtuvo que que todas las personas tienen derecho al debido proceso, el cual está ligado estrechamente al derecho a la seguridad jurídica ya que, este segundo implica el conocimiento y certeza del derecho positivo, la confianza de la sociedad en las instituciones del Estado y en el orden jurídico y la existencia de mecanismos jurídicos frente a las afectaciones que pudieren existir. Se concluyó que la seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales es esencial para mantener la confianza en el sistema legal y para proteger los derechos fundamentales de las personas involucradas en cualquier procedimiento legal, ya sea voluntario, sumario u ordinario.
Keywords: Debido proceso; Due process; Judicial decisions; Legal certainty; Ordinary procedure; Procedimiento ordinario; Procedimiento sumario; Procedimiento voluntario; Resoluciones judiciales; Seguridad jurídica; Summary procedure; Voluntary procedure

Promoting Treaties in Nigeria and Operationalising the Singapore Convention on Mediation - Okoli, Pontian (African Journal of Legal Studies, 2025)
In Nigeria, the United Nations Convention on International Settlement Agreements Resulting from Mediation (2018) has entered into force. This Convention was incorporated or domesticated by referring to it in the Arbitration and Mediation Act (2023), but statutes are often dedicated to the domestication of treaties. There is no consensus on the most pragmatic way(s) to facilitate Nigerian treaty engagement. This article examines the Nigerian legal regime on treaties and explores the extent to which the regime can be maximised considering the Vienna Convention on the Law of Treaties (1969). A case is made for a principled basis to underpin the domestication of treaties that facilitate international business, including dispute resolution treaties. This analytical basis should enable legislative flexibility already woven into the overarching legal regime. The article articulates how such flexibility can be used to promote the operationalisation of relevant treaties using the Arbitration and Mediation Act as a paradigm.
Keywords: Good faith; International commercial mediation; Legislative flexibility; Singapore Convention; Treaties; Vienna Convention

International Arbitration: Impact on Global Economy - Jahan, Bushrat (International Journal of Innovation and Applied Studies, 2025)
The significant increase in the development of world economy over the last few decades have been experienced a considerable increase in the number of commercial disputes. When there is any business and dealings with contracts the question of dispute must be happened. But all of the parties actually want to run their business well and smoothly. In recent world a massive part of global economy depends on the trans-border business. But disputes in such business dealings sometimes can be the reasons to become risk the inter-relation of those parties. Which can affect the global economy as a whole. Comparing to the disputes inside domestic entities the trans-border or international business disputes can arise as bigger problem because of different jurisdictions, diverse legal systems and tradition. International Court of Justice (ICJ) already has the jurisdiction to try all the international civil suits but Alternative Dispute Resolution (ADR) mechanism also considered as a viable alternative to resolve the dispute over the court. The international arbitration arises as a way of alternative dispute resolution mechanism which upraise benefits both of the parties and maintain the confidentiality. In this paper details of international arbitration and the broader impact of this mechanism in the global business economy will be focused. The legal status and the implementation process of international arbitration also be the discussing point of this paper.
Keywords: Business economy; Enforcement of awards; Globalization; International Arbitration

The UNCITRAL Model Law: "Follow you follow me" or "I do it my way" - Wilske, Stephan (Contemporary Asia arbitration Journal, 2025)
Keywords: Arbitral Awards; Arbitral procedure; Arbitration agreements; Arbitration friendliness; Domestic arbitration law; Germany; Harmonization; Harmonization of law; International Commercial Arbitration; International standards; Modernization; Recognition and enforcement; Statutory frameworks; Taiwan; UNCITRAL Model Law

Arbitration Fees, Expenses and Determination Controls - Al-Taani, Muhanned; Al-Majali, Tawfiq; Mosabeh, Rageh; Mayah, Yousef (Jordan Journal of Applied Science-Humanities Series, 2025)

La mise en œuvre de la médiation institutionnelle en droit OHADA - Oueina, Florent; Oussale, Aladji Aberridjoua Aubin Hugues (Revue africaine de droit des affaires, 2025)
Il ne suffit pas d’adopter un nouvel Acte uniforme pour satisfaire à la demande ou garantir une sécurité juridique apparente du droit africain des affaires ou encore enrichir le régime uniforme du règlement des différends dans l’espace OHADA ; ou même pallier le vide législatif qui existait encore au sein de l’OHADA sur la médiation. Il ne s’agit pas d’un Acte uniforme de plus, mais d’un réel instrument juridique qui pourrait favoriser le retour des investisseurs et améliorer les conditions des affaires dans l’espace OHADA. Il faut chercher à savoir si cette nouvelle approche de la justice sera une réussite dans ledit espace.

Mediación y Arbitraje en Línea: Ventajas y Desafíos - Salguero, Katherine Coraima Guano; López, Vilma Patricia Salguero; Cáceres, Alez Remigio Escobar; Chávez, Luis Alberto Morales (Polo del Conocimiento, 2025)
La mediación y el arbitraje en línea han surgido como soluciones eficaces para la resolución de conflictos en un mundo digitalizado, ofreciendo ventajas como reducción de costos, accesibilidad y flexibilidad horaria. Sin embargo, enfrentan desafíos como la brecha digital y la seguridad de la información. Un estudio basado en encuestas a profesionales y usuarios confirma la utilidad de estas herramientas, pero subraya la necesidad de mejorar la infraestructura tecnológica y establecer marcos regulatorios claros. A pesar de los obstáculos, estos métodos representan una evolución significativa en la gestión de disputas legales.
Keywords: Arbitrage; Arbitragem; Arbitraje en línea; Arbitration; Brecha digital; Mediación; Mediation; ODR; Online dispute resolution

Party autonomy and the applicable law to the merits in intellectual property arbitration - Rivoire, Maxence (Arbitration International, 2025)
The freedom of the parties to choose the applicable law to the merits is often presented as an important benefit of arbitrating disputes involving intellectual property (IP). Yet, the reality is more uncertain and controversial than is commonly assumed. Is party autonomy really permitted in IP arbitration? Should it be? This article answers these questions with regard to patents, trademarks, and copyrights, using recent examples drawn from arbitral practice. It first examines the situation where the parties only made a choice of contract law, and considers in this regard whether that law can and/or should be extended to infringement claims and/or the remedies to infringement, either directly or through the technique of characterization. After discussing the impact of overriding mandatory rules in contractual IP cases, the article then examines the situation where the parties chose a law to govern IP questions, including by way of a broad choice-of-law agreement covering non-contractual problems. It seeks to provide as much guidance as possible to arbitral tribunals, using mainly the distinction among infringement, ownership, and validity issues, and by distinguishing among different scenarios in which party autonomy is more or less acceptable.
Keywords: Arbitrage; Arbitragem; Arbitration; Intellectual property; Party autonomy

L'équité dans l'arbitrage - Djeudjo Tankeu, Ghislain (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
Le tribunal arbitral tranche le litige conformément aux règles de droit, mais cette garantie est fragile car le législateur OHADA ajoute à moins que les parties lui aient conféré mission de statuer en amiable composition. Ces amiables compositeurs sont donc des arbitres qui peuvent ne pas appliquer la loi, qui peuvent statuer en équité, ce qui implique la reconnaissance, aux arbitres, d’un pouvoir modérateur sur les obligations contractuelles litigieuses. Mais cette autorisation de statuer en amiable composition ne leur interdit pas de statuer en droit, simplement, le tribunal arbitral amiable compositeur qui appliquerait exclusivement les règles de droit, doit s’expliquer sur la conformité de celles-ci à l’équité. L’arbitrage tend aussi à la satisfaction de l’idéal du procès équitable. C’est ainsi que l’équité est une exigence dans la constitution et lors des suites du tribunal arbitral. The arbitral tribunal shall decide the dispute in accordance with the rules of law; but this guarantee is fragile because the OHADA legislator adds unless the parties have given him the mission to rule in amicable composition. These amicable composers are therefore arbiters who may not apply the law, who can rule in equity; which implies the recognition, to the arbitrators, of a moderating power over the disputed contractual obligations. But this authorization to rule in amicable composition does not prevent them from ruling in law. Clearly, the amicable arbitral tribunal which would exclusively apply the rules of law, must explain their compliance with fairness. Arbitration also tends to satisfy the ideal of a fair trial. This is how fairness becomes a requirement in the constitution and during the proceedings of the arbitral tribunal.

Le règlement des différends en matière d’environnement au Cameroun - Gueukam Tchako, Yannick (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
La présente contribution intitulée « Le règlement des différends en matière d’environnement au Cameroun » ; vise la mise en œuvre des règles de protection de l’environnement de par l’impact des actes mis en cause ou du préjudice causé, selon l’origine des acteurs ou selon les règles invocables. Ce faisant, elle s’intéresse aux solutions qu’apportent certaines dispositions relatives à la matière environnementale au cameroun. A l’analyse, on observe dans la première hypothèse, que les modes alternatifs de règlement non contentieux des différends se veulent plus rapide et accessibles tout en favorisant le respect des lois environnementales. Dans la seconde hypothèse, il s’agit de faire appel au juge judiciaire pour trancher les différends. De par son impact, la position du juge apparaît comme l’outil essentiel d’identification des dommages susceptibles d’être causés à l’environnement et constituant le socle sur lequel est construit le plan de gestion de l’environnement. The present contribution entiled « The settlement of environmental disputes in Cameroon » ; aims at the implementation of environmental protection rules according to the impact of the acts in question or of the damage caused, depending on the origin of the impact or according to the invocable rules. In doing so, it looks at the solutions provited by certain provisions relating to environmental matters in Cameroun. On analysis, it can be observed in the first hypothesis, the alternative methods of non-contentious settlement of disputes that are intented to be faster and more accessible while promoting compliance with environmental laws. In the second hyperthesis, it is a question of appealing to the judicial judge to settle disputes. Because of its impact, the position of the judge appears to be the essentiel tool for identifying the damage likely to be caused to the environment and constituting the basis on which the environmental management plan is built.
Keywords: Différends; Disputes; Environment; Environnement; Jurisdictional settlement; MARD; Non-jurisdictional settlement; Règlement juridctionnel; Règlement non juridictionnel

Du dessaisissement du juge étatique face à la convention d'arbitrage en droit de l'OHADA - Anciza Migani, Ryan; Mbazi, Grâce Beda; Murhula Bahati, Pacifique; Iragi Ntwali, Valéry (Studia Universitatis Babeș-Bolyai Studia Europaea, 2024)
The State Judge's Relinquishment of Jurisdiction over Arbitration Agreements under Ohada Law. The use of arbitration instead of state judges is increasingly popular in the business world. The parties to contracts thus prefer to choose a judge more quickly and less cumbersomely, with more confidentiality and less publicity. If the advantages of resorting to arbitration are undoubted, its effects leading to the total withdrawal of state jurisdictions attract the attention of many. The incompetence of the judge due to arbitration then tends to completely rule out the latter, which merits a better understanding of the powers and competence of the arbitrator and a good understanding of the place of the state judge in the arbitration procedure.
Keywords: Arbitration agreement; Convention d’arbitrage; Divestiture; Droit OHADA; Juge étatique; OHADA law; State judge

The role and mandate of the motor industry ombudsman of South Africa : addressing prospects and challenges to enhance consumer protection - Tshabalala, Thapelo; Magau, Phemelo (PER / PELJ, 2024)
The Motor Industry Ombudsman of South Africa (MIOSA) is an industry ombud recognised under the Consumer Protection Act 68 of 2008 (CPA). The MIOSA regulates the interaction and provides for alternative dispute resolution in the automotive and related industries in South Africa. Moreover, the MIOSA is an impartial organisation that focusses on the resolution of disputes where a deadlock has been reached between the automotive and related industries and their customers, as well as relationships among participants in the automotive and related industries to the benefit of the parties. The role of the MIOSA is to make recommendations in cases referred to it where parties cannot reach common ground and are unable to arrive at mutually acceptable agreements following a dispute. This analysis explores and proffers possible solutions to address the challenges that impede the MIOSA from discharging its role and mandate under the CPA effectively in resolving consumer disputes in the South African automotive industry.
Keywords: Automotive industry; Consumer protection; Dispute resolution; MIOSA; Ombuds

Legal Certainty in the Resolution Process of Business Disputes due to Default on Payment with Bank Guarantee through Arbitration - Wijaya, Didit Wijayanto (International Journal of Science and Research, 2024)
Corporations have been established and recognized in Indonesia as entities engaged in business activities since 1602. In these business activities, disputes can occur regarding the non-disbursement of Bank Guarantees through the Indonesian National Arbitration Board (BANI). Therefore, this research uses the Normative Juridical method through a literature review. The research questions considered are (1) What is the guarantee of legal certainty in the process of resolving business disputes regarding Bank Guarantee payments through the Arbitration Board? (20) What can the Supreme Court Decision provide legal certainty for resolving business disputes through arbitration in Indonesia? The process of resolving business disputes in default on Bank Guarantee payments through the Arbitration Court has fulfilled the legal certainty principle. The results showed that the rules were available through different Arbitration and Alternative Dispute Resolution Laws, as well as other laws applied consistently in the BANI Surabaya Decision Number 59/ARB/BANI-SBY/XI/2021. The Supreme Court Decision Number 918 B/Pdt.Sus-Arbt/2023 tried the appeal case and rejected the application for annulment of the arbitration decision from the Applicant. In addition, legal certainty is created for corporate legal efforts to take the arbitration route.
Keywords: Arbitrage; Arbitragem; Arbitration; Business Disputes; Default; Legal Certainty

Lawyers and Non-Lawyers in International Arbitration: Discovering Diminishing Diversity - Nottage, Luke; Teramura, Nobumichi; Tanna, James (Loyola of Los Angeles International and Comparative Law Review, 2024)

A Proposal for Reforming the Calculation of Damages in Investment Treaty Arbitration = Proposition pour le calcul des dommages-intérêts dans l’arbitrage au titre des traités d’investissement = Propuesta para Reformar el Cálculo de Daños en el Arbitraje de Los Tratados de Inversión - Jarrett, Martin (Investment Treaty News, 2024)

Characterization (and Registration) of a “BRI Dispute” - Kirkwood, Jamieson (Asian Journal of International Law, 2024)
This article explores the terms “BRI dispute” and “BRI jurisprudence”. It undertakes a practical and theoretical analysis that considers whether “BRI disputes” have distinct and visible characteristics and are capable of being identified in a legal sense. This is important since practitioners – arbitration centres and law firms – use the term broadly and without specific criteria. By exploring the customary usage and the approach of legal scholars to the term, presenting examples of “BRI disputes” and examining their unique features, and constructing a theoretical approach (utilizing the concepts of ratione materiae, ratione loci, ratione temporis, and ratione personae; and considering the jurisprudence of the ICSID), this article moves from a broad to a narrow analysis to develop both a definition and a system of registration of “BRI disputes” for use by academics, practitioners, and policymakers.
Keywords: BRI; Belt and Road; China; Dispute Settlement; ICSID

The impact of ISDS arbitration claims and adjudication on cross-border direct investment - Du, Julan; Zhang, Yifei (Transnational Corporations Review, 2024)
This study investigates the impact of the arbitration cases under the Investor-State Dispute Settlement (ISDS) scheme on cross-border direct investment in the form of merger and acquisition deals. The initiation of ISDS claims has significant and negative effects on direct investment from the claimant home country to the developing or weak-institution responding country. Indirect expropriation claims often have stronger effects than direct expropriation claims. The investor-win arbitration cases produce a significant substantiation effect by reducing merger flows, while the state-win cases produce an acquittal effect that encourages the subsequent capital inflow to the respondent state. Both effects are more striking in weak-institution or less developed target countries. We also detect some spillover effects of ISDS arbitration.
Keywords: Arbitration decisions; Cross-border merger deals; Direct and indirect expropriations; ISDS claims

Les qualités essentielles de l'arbitre en droit OHADA - Agbénoto, Koffi Mawunyo (Revue africaine de droit des affaires, 2024)

Les actualités de l'arbitrage maritime - Delebecque, Philippe (Revue africaine de droit des affaires, 2024)

Panorama critique de l’arbitrage OHADA - Ngono, Véronique Carole (Revue africaine de droit des affaires, 2024)

The Enforcement of Settlement Agreements Under the Ohada Uniform Act on Mediation - Nshom, Kelese George (IUS LAW Journal, 2024)
On 23 November 2017, OHADA member states adopted the Uniform Act on Mediation. The Act lays down rules relating to mediation of disputes which, if successful, ends in a settlement agreement. Settlement agreements that are not freely respected by the parties will have no effect unless they are forcefully executed. Forceful execution is made with the help of a court or notably public who are empowered to insert an executory formula on the agreement after verification of its regularity. These local authorities involved in the enforcement process rely on domestic laws of member states which vary from state to state. This has the effect of tainting the harmonization process intended by the OHADA lawmaker and may be inimical to investors. This raises the problem of the suitability of the Act to dispute settlement as regards enforcement of settlement agreements. With the help of qualitative and comparative analysis, this article brings to limelight the intricacies of the enforcement of settlement agreements underOHADA. It concludes that enforcement of settlement agreements is rendered simple and rapid but faces serious drawbacks which could be alleviated by setting up OHADA mediation institution to oversee the entire mediation process, besides other recommendations.
Keywords: Agreement; Enforcement; Exequatur; MARD; Mediación; Mediation; Mediação; Médiation

L'amiable au service du sauvetage de l'entreprise en difficulté en droit OHADA : la médiation et la conciliation - Toe Adouabou, Laure (Revue africaine de droit des affaires, 2024)
L’acte uniforme originel sur les procédures collectives avait prévu une procédure préventive, le règlement préventif, au bénéfice des débiteurs qui traversent des difficultés sérieuses. La nécessité de la consécration d’une procédure à la fois amiable et préventive s’est imposée. C’est désormais chose faite depuis la révision de 2015. Le législateur a ainsi consacré les procédures de conciliation et de médiation à l’article 2-1 de l’Acte uniforme sur les procédures collectives d’apurement du passif (AUPC). Si pour la mise en œuvre de la première, il faut se référer à l’AUPC, la deuxième est règlementée dans l’Acte uniforme sur la médiation (AUM). Nous proposons donc dans cette étude, à la suite de la présentation de ces procédures amiables comme modes anticipatifs et efficaces de sauvetage d’entreprises, des pistes de réflexion afin de rendre effectif le recours à cet arsenal juridique.

L’autorité de la chose jugée dans l’arbitrage OHADA - Toe, Souleymane (Revue africaine de droit des affaires, 2024)

Current Issues of the Utilization of Online Dispute Resolution as a Method for International Trade Dispute Settlement - Rohmah, Nuzul Quraniati (Ipso Jure, 2024)
The transformation of international trade from conventional to digital impacts several things, including resolving international trade disputes. In order to realize an efficient and effective dispute resolution process, many countries have implemented ODR to settle international trade disputes. This study aims to analyze the implementation of ODR in various countries and examine issues with unclear guidelines based on international law. This research observes the development of ODR in Indonesia and the urgency for its implementation in Indonesia. The research is normative juridical, with a statutory and comparative approach. The results obtained in this study are model law arrangements relating to the standardization of ODR Providers aimed to protect the personal data of the parties, unification of ODR dispute resolution clauses, and formulation of national legal instruments to create legal certainty regarding ODR, including ODR proceedings, permits, and monitoring,  as well as recognition and execution process of electronic ODR decisions.
Keywords: International Trade; ODR; Online Dispute Resolution; Regulation

L'agence de régulation des télécommunications au Cameroun : un centre d'arbitrage d'une nature particulière - Silabing Ouethy, Jasmine Diane (Revue africaine de droit des affaires, 2024)
La Procédure de règlement des différends opposant les opérateurs de communications électroniques au Cameroun prévoit, en premier, la saisine de l’Agence de Régulation des Télécommunications (ART). Cette dernière devra tenter de concilier les parties. Si cette tentative de conciliation échoue, alors le dossier sera transmis au Comité de Règlement des Différends (CRD) qui devra trancher le litige. Au cas où la décision intervenue est contestée par une des parties, elle pourra saisir soit les juridictions de droit commun, soit l’arbitre. Cependant, le législateur de 2010 n’a pas résolu toutes les questions relatives à l’intervention de cet arbitre. Par exemple, qui le constitue ? Quelles règles gouvernent la procédure et sur la base de quelles normes doit-il trancher ? Où aura lieu l’arbitrage ? L’examen de la loi de 1998 qui a été abrogée par celle de 2010, plus explicite sur la question, nous livre un régime qui tantôt rapproche le régulateur d’un centre d’arbitrage sur certains aspects, tantôt l’éloigne sur d’autres.

L'adaptabilité de l'arbitrage OHADA au contexte africain - Zakari, Amadou Hamani (Revue africaine de droit des affaires, 2024)
Le règlement des différends par les parties à une relation d’affaires, à travers l’arbitrage, n’est pas un fait nouveau dans les pays africains. Seulement, la nécessité était posée d’adapter ce mode alternatif aux réalités économiques africaines. Pendant longtemps, la majeure partie des contentieux dans lesquels les parties africaines sont impliquées, était réglée en dehors de ses frontières. Ce qui ne favorisait pas leur participation active. Mais la mise en place de l’OHADA et surtout, la création de la CCJA et plus tard son Centre d’arbitrage, suivis par les différents Centres d’arbitrage des Etats ont permis de faire de l’effectivité de l’arbitrage, une réalité. De l’arbitrage traditionnel, l’OHADA, a élargi le champ d’application de ce droit, en y incluant l’arbitrage des investissements, à l’occasion de la réforme du 23 et 24 novembre 2017. Actuellement, cette réforme fait l’objet de nombreuses critiques, notamment, sur le fait que pour certains, ce mécanisme favorise plus l’investisseur étranger que l’Etat partenaire, et que la notion même de l’investissement, n’a jusque-là pas fait l’objet d’une définition claire, tant en droit, en jurisprudence encore moins en doctrine. Pour mettre en œuvre l’arbitrage, les parties font recours à des arbitres, auxquels elles confient leurs différends suivant une convention d’arbitrage ou un instrument d’investissement qui détermine leur mission. Cette dernière peut être accomplie selon les cas, sous la forme d’un arbitrage institutionnel ou ad hoc, et finira par une sentence arbitrale, qui tranchera ce conflit. Comme dans la justice étatique, cette sentence est susceptible des voies de recours. L’arbitrage ne va pas sans écueils : de la constitution du tribunal arbitral à la sentence finale, plusieurs difficultés peuvent surgir.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration

Evaluating the International Arbitration of Oil and Gas Investment Dispute Settlement in Nigeria - Bisina, Lucky N. (African Journal of International Energy & Environmental Law, 2024)
This paper examined international arbitration as a tool for resolving investment disputes in Nigeria’s oil and gas sector, a critical industry that contributes significantly to Nigeria’s Gross Domestic Product (GDP), foreign exchange earnings and government revenues. This sector is marked by high-risk investments and complexity and often faces disputes arising from regulatory changes, fluctuating global prices, environmental concerns and contractual breaches. Arbitration, particularly in cross-border investments, provides a neutral, efficient and flexible mechanism for resolving such disputes. Using a doctrinal research methodology, the study analysed statutes, case law, international treaties, and academic sources. Findings revealed that while arbitration offers benefits such as neutrality and enforceability, there are still some challenges that must be addressed as a matter of urgency. Issues include resistance to enforcement of arbitral awards by Nigerian courts on grounds of national interest, high arbitration costs and biases favouring foreign investors. Nigeria’s legal framework, including the Arbitration and Mediation Act 2023 and the Petroleum Industry Act 2021, supports arbitration but lacks procedural clarity, leading to delays and inefficiencies. The paper concluded that legal reforms are essential to strengthen arbitration processes, enhance enforcement mechanisms and align Nigeria’s framework with international standards. Such reforms would foster investment stability and improve Nigeria’s attractiveness as an investment destination by reducing legal uncertainties. The paper recommended legislative and judicial improvements in order to achieve these goals.
Keywords: Dispute Settlement; International Arbitration; Investment Dispute; Oil and Gas Investment

Arbitration in the era of e-commerce: A comprehensive overview - Buhuri, Kristi (World Journal of Advanced Research and Reviews, 2024)
Technology is continuously evolving and has changed human interaction. It is consequently changing the ways disputes are solved. International dispute resolution procedures, and international arbitration, more specifically, are considerably influenced by the rapid expansion of innovative technologies. Years after the dot-com boom, Online Dispute Resolution (ODR) emerged and evolved considerably. Due to the digitalization of ODR methods, remote arbitration (or e-arbitration) is expanding. Arbitration is of particular interest due to its formal and binding nature, from a theoretical perspective. E-arbitration, as other ODR methods have attractive features as well as drawbacks, which are addressed in this document.  The purpose of this paper is three-fold: providing an overview of e-arbitration and the different considerations of this method, presenting the e-arbitration models of the European Union (EU), the United States (US), and the People’s Republic of China (PRC) and suggesting recommendations to improve international e-commerce arbitration, notably through a revision of the UNCITRAL Model Law on International Commercial Arbitration (UNCITRAL Model Law).
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Digitalization; Innovative Technologies; ODR; Online Dispute resolution; e-Arbitration

التحكيم وفقًا لاتفاقية الأمم المتحدة بشأن نقل البضائع عن طريق البحر (هامبورغ، 1978) - Ghassan, ali; Haidara, jaber (Tishreen University journal of research and scientific studies -economic and legal sciences, 2024)
International maritime transport represents the backbone of international trade in our current era, for many reasons, such as low costs and the ability to transport large quantities of goods at once. The United Nations Convention on the Maritime Transport of Goods of 1978, known as the Hamburg Convention, represents a qualitative shift in regulating the rules of maritime transport of goods. Among the important topics regulated by the agreement is the subject of arbitration, as it is the most important means of settling disputes related to international trade contracts, especially the contract for the maritime carriage of goods. Accordingly, this research studies the rules of the Hamburg Convention related to arbitration as a means of settling disputes related to the contract for the maritime carriage of goods. يمثل النقل البحري الدولي عصب التجارة الدولية في عصرنا الحالي، ألسباب عديدة كانخفاض التكاليف والقدرة عمى والمعروفة 1978 نقل كميات كبيرة من البضائع دفعة واحدة، وتمثل اتفاقية األمم المتحدة لمنقل البحري لمبضائع لعام ىامبورغ، نقمة نوعية عمى صعيد تنظيم قواعد النقل البحري لمبضائع، ومن بين الموضوعات اليامة التي باسم اتفاقية نظمتيا االتفاقية، موضوع التحكيم، باعتباره أىم وسائل تسوية النزاعات المرتبطة بعقود التجارة الدولية، وخاصة عقد د اتفاقية ىامبورغ المتعمقة بالتحكيم كوسيمة لتسوية النزاعات النقل البحري لمبضائع، وبناء عميو يتناول ىذا البحث قواع ال
Keywords: Arbitration; Bill of lading; Bills of lading; Carriage of Goods by Sea (1978); Hamburg Convention; Hamburg Rules; International commercial arbitration; Maritime carriage contract; Maritime transport; UN Convention; اتفاقية ىامبورغ; التحكيم; سند الشحن; عقد النقل البحري

ISDS 2.0: Time for a Doctrine of Precedent? - Jarrett, Martin (Journal of international economic law, 2024)

La mediación y la cultura del acuerdo - Lagones, Delcy de Anglim (Deconstruyendo la justicia, 2024)
Keywords: China; Dispute Settlement; MARD; Mediación; Mediation; Mediação; Médiation; UN Convention on International Settlement Agreements resulting from Mediation (2018); UNCITRAL Model Law on International Commercial Conciliation (2002)

La bonne administration de la justice arbitrale en droit OHADA - Megou Ebock, Jocelyne Yvonne (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La résolution d’un litige passe généralement par la justice étatique habilitée à faire appliquer les lois, à corriger et réparer les injustices subies. Rendre justice suppose que certains moyens soient réunis afin de garantir une bonne administration de la justice. Mais de plus en plus la justice étatique est concurrencée par une forme de justice ayant pour principaux acteurs les parties : il s’agit de la justice arbitrale. Cette forme de justice semble être la parfaite incarnation d’une bonne administration de la justice dans la mesure où elle renvoie à un emploi équilibré des moyens de justice en conformité avec les objectifs de célérité de la justice arbitrale. Justice rendue sur la base d’une convention d’arbitrage, la justice arbitrale s’accommode bien du respect des exigences d’un procès équitable et garantie la bonne administration de la justice. S’agissant de la bonne administration de la justice arbitrale OHADA, tout parait plus simple dans la mesure où le législateur en a fait un mode privilégié de règlement des différends contractuels et un instrument juridique adapté aux exigences d’une justice de qualité. Ainsi, la préoccupation majeure de cette étude est celle de savoir dans quelle mesure la justice arbitrale pourrait être considérée comme la « pierre philosophale » de la bonne administration de la justice arbitrale en droit OHADA. C’est à travers l’analyse d’un corpus juridique entièrement rénové le 23 novembre 2017 que la justice arbitrale est considérée comme la pierre angulaire de la bonne administration de la justice. Ceci se justifie par la double assertion selon laquelle elle respecte les principes généraux de bonne administration de la justice et qu’elle demeure une justice ancrée sur le respect des principes spécifiques à la justice arbitrale.
Keywords: Administration; Arbitrage; Arbitragem; Arbitration; Arbitre; Good administration; Justice; Proceeding; Procès équitable

A comprehensive outline towards conciliation in the contemporary world of E-commerce - N, Vinod; Gupta, Poonam (World Journal of Advanced Research and Reviews, 2024)
Since the start of the millennial era, technical advancements have led to exponential growth in electronic commerce, or e-commerce. According to the United Nations Conference on Trade and Development (UNCTAD), e-commerce sales reached about US$25 trillion globally in 2021 [1] and are expected to grow at a compound annual growth rate of 9% through 2027, which is twice as fast as the 4% annual growth rate predicted for traditional in-person retail [2]. Online dispute resolution (ODR) techniques that aim to settle disagreements and lower the likelihood of expensive lawsuits are becoming more and more necessary as both individuals and corporations use online shopping platforms. Due of its legally binding nature, arbitration is the most formal method, as was briefly discussed [3]. Online arbitration is carried out using electronic methods, like email and digital tools designed to make the duties of arbitrators and parties to a dispute easier. It adheres to the same rules and processes as traditional arbitration. On the plus side of e-arbitration, advancements in technology allow for time and cost savings without sacrificing the ease of remote filing. The conclusion of e-arbitration agreements raises several negative issues, including privacy and data protection issues for the consumer signing the agreements and power imbalances between corporate entities and the consumer. The degree to which artificial intelligence (AI) is effectively and sufficiently analysing a dispute between parties is up for debate because it's unclear how new this adjudication process is.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Artificial Intelligence; Conciliation; E-Commerce; Inteligência artificial; Intelligence Artificielle; ODR; OECD

Concurrent Investor-State Claims Before Domestic Courts and Investment Treaty Arbitration Tribunals: Philip Morris, Vattenfall and Beyond - Nottage, Luke; Stendel, Robert (Virginia journal of international law, 2024)
Keywords: Arbitrage; Arbitragem; Arbitration

La compétence du for de situation de l’immeuble face aux conventions de juridictions - Tchouankeu Djeuda, Claudia (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
L’admission d’une maitrise par les parties de la compétence internationale par des clauses de juridictions ; notamment des conventions d’élection de for, des conventions d’arbitrage ou de médiation, amène à s’interroger sur l’efficacité réelle de ces accords. Pour ce qui est de la matière immobilière, le fort attachement de l’Etat aux questions de territoire et les considérations de proximité entre litige et le for du situs ont pour effet d’empêcher toute dérogation à la compétence directe du for de situation de l’immeuble ; tant lorsque l’immeuble est situé sur le for du juge saisi que lorsqu’il est situé à l’étranger. Toutefois, l’observation d’un possible fléchissement de l’exclusivité de ce critère de compétence conduit à un plaidoyer en faveur de l’efficacité, quoique encadrée, des conventions juridictions en la matière.
Keywords: Autonomie de la volonté; Autonomy of will; Compétence internationale des juridictions; Convention de juridiction; Immovable property’s location; International jurisdiction; Jurisdiction agreement; Lieu de situation de l’immeuble; Matière immobilière; Real estate matters

Blockchain and smart contracts: a game changer in mediation? - Mak, Charles Ho Wang; Mante, Joseph (Asian journal on mediaton, 2023)
In light of accelerating technological innovation and shifts in dispute resolution paradigms, this article elucidates the transformative potential of blockchain technology and smart contracts in mediation. The paper posits that these advancements offer an innovative framework for dispute avoidance and a more efficient, transparent process for resolving conflicts, particularly in commercial settings. The article critically assesses the inherent challenges and argues that overcoming these obstacles necessitates a multi-stakeholder approach, encompassing legislative measures, educational initiatives, and technological enhancements. It ultimately contends that blockchain and smart contracts hold the capacity to significantly reshape the landscape of mediation.
Keywords: Blockchain technology; Dispute resolution; MARD; Mediación; Mediation; Mediação; Médiation; Smart contracts

Arbitrage et modes amiables de règlement des conflits - Clay, Thomas (Recueil Dalloz, 2023)
Le hasard a voulu que la décision qui a été distinguée comme la plus importante de l’année 2023 corresponde à un arrêt annulant une sentence rendue par un tribunal arbitral que présidait l’auteur de ces lignes. Les usages académiques interdisant de commenter un tel arrêt, il sera renvoyé aux innombrables publications dont il a déjà fait l’objet (JCP E 2023. 1061, note D. Mainguy ; JCP 2023. 507, note D. Mouralis ; D. actu. 14 mars 2023, obs. J. Jourdan-Marques ; Rev. arb. 2023. 423, note F.-X. Train ; RTD com. 2023. 582, obs. E. Loquin ; Cah. arb. 2023. 501, note M. Henry ; Gaz. Pal. 16 mai 2023, p. 12, obs. L. Larribère ; JCP 2023. 221, § 4, obs. P. Giraud ; Lexis®PSL, 27 janv. 2023, obs. M.-L. Cartier et A. Meyniel ; Paris Baby Arbitration 2023, n° 59, p. 9, obs. G. Ghedjati et M. Villeneuve ; IA Reporter 12 janv. 2023, obs. L. Bohmer ; Global Arbitration Rev. 13 janv. 2023, obs. A. Ross), ayant même eu les honneurs de l’Agence France Presse (AFP) dans une dépêche du 20 janvier 2023 et… du Canard enchaîné (18 janv. 2023, p. 3). Les commentaires de doctrine sont d’ailleurs très majoritairement critiques sur cet arrêt inattendu, parfois avec des nuances, en dehors d’un seul, celui publié à la Revue de l’arbitrage, qui suit une approche univoque si singulière qu’elle interroge sur les motivations réelles de l’auteur : un professeur de droit ne devrait pas écrire ça. Il n’en reste pas moins que cet arrêt, aussi remarqué qu’il fût, ne sera donc pas commenté dans ces colonnes. Mais, pour que soit moins iconoclaste le paradoxe d’un panorama de droit de l’arbitrage qui n’évoque pas la décision la plus remarquée de l’année en droit de l’arbitrage, encore fallait-il qu’il en fût fait mention dans cet éditorial, lieu d’une licence académique plus libre, sous peine de laisser croire à une auto-censure, voire à une gêne du soussigné, qui, au contraire, assume pleinement d’user de sa liberté d’expression en toutes circonstances.
Keywords: Arbitrage; Arbitration; Convention d'arbitrage; Sentence arbitrale

La mediación y el arbitraje laboral en el Procedimiento concursal: regulación y dificultades aplicativas - Dormido Abril, Julia (Trabajo, Persona, Derecho, Mercado: Revista de Estudios sobre Ciencias del Trabajo y Protección Social, 2023)
La declaración de concurso de una empresa no solo va a afectar al deudor concursado, pues tal calificación también tiene un efecto directo sobre los trabajadores. Sobre todo, si en el seno de un procedimiento concursal, para salvar la continuidad de la actividad empresarial, se decide adoptar alguna medida de reestructuración, tal y como pueden ser las modificaciones sustanciales de las condiciones de trabajo, el traslado, el despido, la suspensión de contratos o la reducción de jornada por causas económicas, técnicas, organizativas o de producción. Las decisiones que sobre cualquier de éstas se tomen pueden dar lugar a conflictos que tienen que solucionarse mientras el proceso judicial sigue su curso. Por ello, el legislador ha incorporado la mediación y el arbitraje en la norma mercantil como vías de solución extrajudicial de tales conflictos. Se trata de una fórmula jurídica no exenta de interrogantes, relacionados en este caso con aspectos como, la norma aplicable a tales mecanismos de solución extrajudicial, la incorporación de la solución al auto o el modo en el que impugnar el acuerdo o el laudo en materia laboral. The declaration of insolvency of a company will not only affect the insolvent debtor, as such a classification also has a direct effect on the employees. Particularly if, within the context of an insolvency procedure, in order to save the continuity of the business activity, it is decided to adopt any restructuring measure, such as substantial modifications to working conditions, relocation, dismissal, suspension of contracts or reduction of working hours for economic, technical, organisational or production reasons. The decisions taken on any of these may give rise to conflicts that have to be resolved while the judicial process is still underway. For this reason, the legislator has incorporated mediation and arbitration into commercial law as a means of extrajudicial settlement of such disputes. This is a legal formula that is not free of questions, related in this case to aspects such as the rule applicable to such out-of-court settlement mechanisms, the incorporation of the solution into the or-der or the way in which to challenge the agreement or award in labour matters.

Standing in international investment and trade disputes - Ossa, Ralph; Staiger, Robert W.; Sykes, Alan O. (Journal of International Economics, 2023)
International investment agreements employ dispute settlement procedures that differ markedly from their counterparts in trade agreements. A prominent and controversial difference arises with respect to the issue of “standing”: Who has the right to complain to adjudicators about a violation of the agreement? While trade agreements limit standing to the member governments (state-to-state dispute settlement), investment agreements routinely extend standing to private investors as well (investor-state dispute settlement). We develop parallel models of trade and investment agreements and employ them to study this difference. We find that the difference in standing between trade and investment agreements can be understood as deriving from the fundamentally different problems that these agreements are designed to solve. Our analysis also identifies some important qualifications to the case for including investor-state dispute settlement provisions in investment agreements, thereby offering a potential explanation for the strong political controversy associated with these provisions.
Keywords: Bilateral investment agreements; Investments; Investor-State Dispute Settlement; State-to-state dispute settlement; Trade agreements; Trade dispute

Legal Reconstruction of Dispute Settlement Between Importers and Exporters International Law Perspective - Pristha Utama, Wahyu; Tri, Lazarus; Setiyono, Joko (Journal of Xi'an Shiyou University, Natural Sciences Edition, 2023)
Reconstruction of dispute resolution law between importers and exporters from an international law perspective. The purpose of this study is to analyze: 1) How does the law of dispute resolution between importers and exporters perspective international law? 2) How is the implementation of the recommendations of the dispute resolution bodies of the World Trade Organization from an international law perspective? The research method used is normative juridical with a statutory approach, concept approach, and case studies. The results showed that: 1) Import export is a series of company activities that begin with an agreement. The agreement is the result of previous activities carried out by exporters and importers, namely in the form of supply and demand. The agreement is poured into a sales contract which is an agreement between exporters and importers to trade goods in accordance with mutually agreed conditions and each party binds itself to carry out all obligations incurred. 2) The series of processes undertaken in dispute settlement at the WTO consist of 4 processes, including: Mandatory Consultation between disputing parties to reach a settlement approved by the parties, Application for the establishment of a Panel, the Appellate Body, and the implementation and implementation of recommendations and provisions endorsed by the DSB.
Keywords: Dispute Resolution; Exporter; Importer; International Law; Reconstruction

Chronique de jurisprudence de droit de l’arbitrage - Larribère, Lilian (Gazette du Palais, 2023)
Dans la période récente, de nombreuses précisions viennent affermir le régime procédural des recours portés devant le juge français du contrôle. Ainsi, de l’article 1520 du Code de procédure civile qui ne liste que les griefs portant sur la sentence arbitrale elle-même, et qui autorise donc à se prévaloir des moyens d’irrecevabilité de la requête d’exequatur (Cass. 1re civ., 13 avril 2023, n° 21- 50053). Ainsi encore, de l’irrecevabilité du recours en annulation qui n’emporte pas exequatur de la sentence arbitrale (Cass. 1re civ., 7 juin 2023, n° 22-12757). On notera également les arrêts nombreux portant sur le régime de la convention d’arbitrage, et partant de la compétence arbitrale. Enfin, l’arrêt rendu par la Cour de Strasbourg dans l’affaire Semenya (CEDH, 11 juill. 2023, n° 10934/21, Semenya c/ Suisse) montre que le contrôle des droits fondamentaux devra être mené de manière scrupuleuse par le juge de l’annulation, et ce, même si la situation litigieuse ne présentait guère de liens avec les États parties à la CEDH.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Contentieux para-arbitral; Contentieux post-arbitral; Jurisprudence arbitrale

L'incompétence du juge étatique en présence d'une convention d'arbitrage en droit OHADA - Fofana, Modibo Mohamed; Diallo, Hamadi (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
Le droit OHADA de l'arbitrage contient tous les ingrédients pour dissuader l’intervention du juge dans la procédure arbitrale soulevée par les plaideurs les plus récalcitrants. Face aux principes d’autonomie et de force obligatoire de la convention d’arbitrage, l’article 13 de l’Acte uniforme relatif au droit de l’arbitrage pose une obligation d’abstention à la charge du juge étatique à chaque fois qu’il est saisi d’un litige ayant déjà fait l’objet d’une compromission. À moins que la convention d’arbitrage soit manifestement nulle ou manifestement inapplicable, le juge étatique doit s’abstenir de toute intervention. Toutefois, en dépit du principe d’autonomie et de force obligatoire de la convention d’arbitrage, l’absence d’imperium qui caractérise la vie du tribunal arbitral nous amène à relativiser la posture de neutralité dont le juge étatique est contraint d’adopter. Ce dernier, dans le respect de la primauté reconnue à l’arbitre, se verra ponctuellement reconnaître le pouvoir d’assister l’arbitrage.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Convention d’arbitrage; Droit OHADA; Incompétence; Juge communautaire; Juge d’appui; Juge étatique

L’intervention du juge étatique dans l’arbitrage de l’Organisation pour l'Harmonisation du Droit des Affaires en Afrique (OHADA) : Une carence normative du droit communautaire - Fofana, Modibo Mohamed; Diallo, Hamadi (International Journal of Strategic Management and Economic Studies (IJSMES), 2023)
Les attributions du juge étatique sont confrontées à un flou juridique qui en résulte l’absence d’un régime juridique claire. A l’issue de cette réflexion, il convient de retenir que l’intervention du juge étatique à l’arbitrage dans l’espace OHADA est une œuvre particulièrement complexe car, si dans l’arbitrage spécifique de la CCJA, Il revient au juge communautaire la charge d’administrer la procédure et d’assurer le suivi durant la phase post-arbitrale, la détermination du juge étatique dans l’arbitrage de droit commun est une opération complexe et ses attributions ne sont pas claires. En effet, le flou lexical entourant l’expression générique désignant le juge étatique, entraîne un morcellement de son champ de compétence. Ce sont ses faiblesses qui justifient que des palliatifs soient proposés en vue de renforcer l’efficacité de l’intervention du juge national et de garantir par la même occasion la sécurité juridique dans l’espace OHADA.
Keywords: Arbitrage; Arbitragem; Arbitration; Juge communautaire; Juge d’appui; Juge étatique; OHADA

Transparency in international arbitration: balancing the need for openness with the need for confidentiality - Mak, Charles Ho Wang; Rohatgi, Akshita (ACICA review, 2023)
International arbitration is often presented as an efficient and appropriate alternative to domestic court systems for resolving conflicts. For international arbitration to be effective, it is essential that the procedure adopted be open and accountable. This article will discuss the significance of openness in international arbitration and how it may promote justice, foster trust, and avoid corruption and misbehaviour.
Keywords: Corruption; International Arbitration; Justice; Misbehavour; Transparency; Trust

La pérennité du contrat international entre pacta sunt servanda et rebus sic stantibus : réflexions au regard du pouvoir interprétatif de l’arbitre - Bejeoui, Imed (UAEU Law Journal, 2023)

Addressing the Legitimacy Crisis of Investment Arbitration Through its Harmonization with World Trade Organization Law - Seifi, Seyed Jamal; Veis Karami, Mahdi (Public Law Researsh, 2023)
International investment law is facing a legitimacy crisis, in which to tackle, substantial efforts are being made in structural and procedural areas. The first step to overcoming this crisis is identifying the roots of it. The lack of a dynamic balance between public and private interests is one of the main factors creating this legitimacy crisis in this legal system.[1] This paper focuses on the changes in the investment arbitration jurisprudence to create this balance. The findings of this paper can explain one of the convergence points of international trade and investment law. Such a claim is based on the evolution of international trade law in facing a similar legitimacy issue and the structural-procedural approach of this legal system in balancing public and private interests as an ultimate solution to the crisis.[2] From this perspective, one of the major factors in creating a legitimacy crisis in both legal systems is the dominance of the paradigm for preference of private interests; and one of the convergence points of international trade and investment law has been to replace it by accepting the paradigm of creating a dynamic balance between competing goals.[3] This paper examines this convergence in arbitral jurisprudence.IntroductionIn recent years, the legitimacy crisis of the regime of international investment law and, as a result, the investor-state dispute settlement system has been one of the most important and controversial topics in the academic environment and the practice of states consequently, serious efforts in various fields to tackle this crisis have begun. According to this paper, choosing an arbitration mechanism modeled on international commercial arbitration to resolve disputes between host states and foreign investors can be evaluated as a wrong and hasty action that, regardless of its factors and contexts, has changed the nature and function of this system over time.[4] It should be noted that the main factor in such consequences is how this dispute resolution system is used which, contrary to the accepted model, always puts the host states in a "respondent" position in possible future disputes and, as a result, disrupts the balance expected in any international dispute settlement system. On this basis, the confrontation of the host state's sovereign competence in ensuring public interests with the foreign investors’ ability to challenge this competence is brought into the spotlight: currently, within the regime of international investment law, host states have only responsibilities and obligations in contrast to extensive and exclusive rights and privileges recognized for foreign investors, and this can be considered as the most important factor disturbing the said balance. The main issue in this field is to analyze the role of the investment arbitral tribunals in creating such a balance. In this regard, the authors, by focusing on the nature of investment treaties, and the relations between the parties in investment disputes and with emphasis on the general legal regime governing international investment, consider creating a dynamic balance between public and private interests to be the key to solving the crisis. They emphasize that; As long as the rights and obligations of the parties to the dispute are based on imbalanced grounds, the change in nature of the disputes and the function of the system -as the main roots of this legitimacy crisis - will remain. In this remark, it is very important to focus on the two-sided nature (public-private) of the relationships established in the framework of investment treaties. The relationship between the host state and the foreign investor is created within the framework of investment treaties and in light of fundamental differences from purely private relationships in international commercial arbitration.[5] Note that any dispute arising from this relationship is affected by its inherently public nature governed by public international law.[6] Thus, a purely private attitude towards these relations does not seem viable. As Ian Brownlie has stated in the case of SME v. the Czech Republic, it can lead to ignoring some of the basic elements of the relevant investment treaty.[7] In other words, the right and duty of the host state in protecting and promoting public interests is a fundamental part of this relationship, and any indulgence of it leads to a serious disruption of the mentioned balance through which the system's legitimacy will be the first victim.It is clear that the main task of any dispute resolution system is to create such a balance, and on this basis, and compared to the WTO dispute resolution system, the role of the investment tribunals in this process is discussed. This jurisprudential convergence is in line with the goal of strengthening the legitimacy of the international investment law system as a whole.Based on the above, the first part of this paper focuses on the process of establishing the ISDS in international investment law and its characteristics, the factors of the crisis of legitimacy are analyzed with an analytical approach, while also explaining the nature of investment treaties and explaining the general legal regime governing international investment. Furthermore, the lack of a dynamic balance between public and private interests is emphasized as the main cause of the crisis. In the second part, while comparing the two legal systems of international trade and investment with a similar crisis of legitimacy, we will examine the interaction of investment arbitration with the WTO's jurisprudence in facing this crisis through a case study of several investment arbitral awards. [1]. David Gaukrodger, “The Balance between Investor Protection and the Right to Regulate in Investment Treaties: A Scooping Paperˮ, OECD Working Paper on International Investment 2017/02, at 4.[2]. Nicholas DiMascio & Joost Pauwelyn, “Non-Discrimination in Trade and Investment Treaties: Worlds apart or Two Sides of the Same Coin?”, AJIL, Vol. 102, No.1, (2008), at 89.[3]. Jurgen Kurtz and Sungioon Cho, “Convergence and Divergence in International Economic Law and Politics”, EJIL, Vol. 20, No. 1, (2018), at 187.[4]. Benedict Kingsbury & Stephan W. Schill, “Public Law Concepts to Balance Investor's Rights with State Regulatory Actions in the Public Interest - The Concept of Proportionalityˮ, In Schill Stephan W., International Investment Law and Comparative Public Law (UK: Oxford University Press, 2010) at 76. [5]. Crina Baltag, “Reforming The ISDS System: In Search of a Balanced Approach?ˮ, Contemporary Asia Arbitration Journal, Vol. 22, No. 2, (2019), at 285.[6]. Ibid.[7]. Andreas Kulick, “Sneaking Through Backdoor – Reflections on Public Interest in International Investment Arbitrationˮ, Arbitration International, Vol. 29, No. 3, (2013), at 438.
Keywords: Crisis of Legitimacy; International Investment Law; Investor-State Dispute Settlement; WTO; World Trade Organization

L’immunité des arbitres dans l’arbitrage OHADA - Diallo, Hamadi; Traoré, Abdramane; Traoré, Abdou Bougoury (International Journal of Strategic Management and Economic Studies, 2023)
Cet article, est une contribution à la réflexion sur le statut de l’arbitre en droit OHADA, entamée par plusieurs chercheurs africains, et au centre de laquelle se trouve la problématique de l’immunité en droit de l’arbitrage OHADA. Le débat sur le choix d’un système d’immunité et la définition d’un véritable statut pour l’arbitre est toujours d’actualité. Cet article fait le point global des approches et conceptions sur l’immunité diplomatique des arbitres de la CCJA. En effet, le débat sur la responsabilité touche de façon étroite celui du statut de l’arbitre : la responsabilité étant la résultante d’un statut, cela nous permettra d’aborder la question du statut juridique de l’arbitre en droit OHADA. Dans un contexte où les différentes législations, la jurisprudence ou encore les conventions internationales, n’abordent que très peu le statut de l’arbitre, la détermination des éléments permettant de préciser les contours des devoirs, droits et obligations de l’arbitre, contribuera de façon certaine à mieux appréhender la mission de l’arbitre.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitre; CCJA; Immunité; OHADA

Rights and Obligations of the Parties Against International Arbitration Awards in Indonesia - Puspita, Lona; Budiono, Abdul Rachmad; Kusumadara, Afifah; Widagdo, Setyo (International Journal of Social Science Research and Review, 2023)
The position of international arbitration awards which is different from national arbitration awards and district court decisions causes differences in the rights and obligations of the parties to arbitral awards, especially those relating to legal remedies against awards. The formulation of the problem in this study is how are the rights and obligations of the parties to international arbitral awards in Indonesia. The research method used in this article is legal research using primary and secondary legal materials. The results of the study state that the rights possessed by the parties to international arbitral awards in Indonesia are related to legal remedies against decisions, namely corrections to these international arbitral awards. The corrections to the decisions here are not only limited to administrative corrections but also corrections related to the principal international arbitral awards made before the request for execution was registered at the Central Jakarta District Court. While the obligations of the parties to international arbitral awards are to carry out international arbitral awards in good faith.
Keywords: International Arbitration Award; Rights and Obligations

L’ouverture du droit d’agir au système des règlements alternatifs des différends en droit OHADA et Camerounais : un procédé séduisant mais d’une efficacité incertaine - Njock, Luc Kevin Leny (Uniform Law Review, 2023)
The processes by which a model of social regulation channels its way of resolving conflicts make the strength of its conflict resolution system. Court justice has lost its exemplary function. The crisis of effectiveness and the crisis of legitimacy that the processual mode of dispute resolution is undergoing in our States, make it a justice system that is considered to have broken down. The need for justice thus directly raises the question of social regulation, the relevant model of social regulation. The call for a ‘right to sue’ open to the system of alternative dispute resolution rather than restrictively to the judiciary to resolve disagreements is the spearhead of the combinatorial approach to the administration of conflicts, the ferment of a plural approach to access to justice. Has Cameroonian law begun to renew its vision of the right to take legal action? Does it renew the dominant classical approach to the system of social regulation? The study notes the global and integral recognition of the alternative dispute resolution system, another, less contentious, way of dealing with disputes, the emergence within the traditional dispute resolution system of a right to amicable dispute resolution, but in an embryonic state. It then poses, in a prospective approach, the need for a unitary and global approach to private justice as challenges to be met to ensure the quality of this form of justice.

L'Arbitrage en matière des litiges contractuels - Ismail, Mahmoud (International Multilingual Journal of Science and Technology, 2023)
Le recours à l’arbitrage en matière des litiges contractuels entre des parties privées présente des avantages par rapport aux procédures devant les tribunaux. Les avantages de l’arbitrage qui a une valeur particulière en matière contractuelle se multiplient : les arbitres peuvent être choisis en raison de leurs compétences spéciales selon le sujet du contrat; la confidentialité peut être préservée; l’arbitrage peut être utilisé pour régler des questions sur le même sujet ou des sujets semblables mais survenant dans des pays différents, ceci peut présenter l'avantage de régler en une seule fois tous les différends entre les parties, surtout en matière de commerce.
Keywords: Arbitrage; Arbitrage Conventionnel; Arbitrage Judictionnel; Arbitragem; Arbitraje; Arbitration; Commerce; Droit civil; France; Jordanie; Litiges contractuels

La médiation en matière des litiges contractuels - Ismail, Mahmoud (International Multilingual Journal of Science and Technology, 2023)
Dans une économie de plus en plus globalisée, faute d’harmonisation juridique, les parties aux litiges contractuels n’hésitent plus à consulter les forums juridiques pour identifier les pays susceptibles de leur offrir le meilleur niveau de protection. Presque tous les litiges en matière contractuels se prêtent au début des conflits à la médiation. Il arrive souvent que lors d’un litige relatif aux droits contractuels, les parties recourent à la médiation. Cependant, pour pouvoir y recourir de manière utile, il est important d’éluder certains obstacles. Un litige ayant trait à un contrat, soulève des questions complexes de faits et de droit, peut nécessiter des dépenses importantes et exiger la présence de témoins experts. Puisque l’obligation contractuelle émise sera presque toujours un enjeu, un litige ayant trait au commerce, notamment international, commande une connaissance approfondie de la législation sur les objets de transactions, ainsi qu’une expérience des tribunaux qui traitent la plupart du temps de ces questions. En pratique, l’espace de rencontre entre la médiation et les litiges contractuels est le contrat lui-même. Or, le domaine contractuel est le domaine privilégié de la médiation. En réalité, la médiation peut avoir lieu dans les relations liée aux contrats de commerce, dans lequel une dévolution des droits contractuels est prévue. Ce mode alternatif fournit un moyen pour éviter les contentieux judiciaires.
Keywords: Approche comparée; Commerce international; Droit civil; France; Jordanie; Litiges contractuels; Mediation; Médiation

Investigation of Investor-State Arbitration Problems in Afghanistan - Nikzad, Nezamuddin; Anwari, Gulaqa (International Journal of Social Science Research and Review, 2023)
The main purpose of this research is to explain and identify the major Investor-State Arbitration (ISA) problems in Afghanistan. Afghanistan's government is committed to providing legal security for the resolution of foreign investment disputes. The dispute resolution system's assessment is very important for foreign investors because they pay special attention to the dispute resolution system and consider it a criterion for their investments. This research will be the first comprehensive study about the Investor-State Arbitration problems in Afghanistan. In the writing of this research, the library method has been used. To extract reasons, laws, books, articles, and reliable scientific sources have been used. Afghanistan is a good market for foreign investment because it has good investment opportunities in different sectors. Foreign investors can choose the easiest and best mechanisms, such as arbitration in their contracts to deal with disputes. But the resolution of foreign investment through arbitration has some problems, and sometimes foreign investors are facing challenges with the settlement of their disputes through arbitration internationally and domestically in Afghanistan.
Keywords: Arbitration; Dispute; Foreign Investment; Investigation in Afghanistan; Problems

The Pros and Cons of Third Party Funding in the International Investment Arbitration Regime - Mirveisi, Alireza; Zakerian Amiri, Mehdi; Abdollah Zadeh, Mohammad Ali (Public Law Researsh, 2023)
There is a growing stream of critics who see investment arbitration in favor of foreign investors and as a negative force as opposed to sustainable development. The phenomenon of third-party funding and its use in investment arbitration has increased such concerns. Third-party funding is basically the payment of all or a part of the arbitration costs of one of the parties of dispute by a third party funder which in return, the funder receives a percentage of the output of the award if successful. The purpose of this article is to explain and analyze the theoretical differences between pros and cons of third-party funding regarding the access to justice, screening mechanism for the claims, and the financial consequences on the host state. In this article, the advocates see third-party funding as a means of access to justice for aggrieved investors in investment claims, while the adversaries refering on the profitability of third-party funding, see this method in arbitration a form of wealth transfer from public sector to private corporations and also refer to the asymmetric structure of the investment arbitration regime as well as the risks arising from the transfer of management and control of arbitration process to the third party funders. یک جریان رو به رشدی از منتقدان وجود دارد که داوری سرمایه‌گذاری را به نفع سرمایه‌گذاران خارجی و بعنوان یک نیروی منفی در تضاد با توسعه پایدار می‌داند. پدیده تأمین مالی ثالث و بکارگیری آن در داوری سرمایه‌گذاری به این نگرانی‌ها افزوده است. تأمین مالی ثالث اساساً پرداخت تمام یا بخشی از هزینه‌های داوری یکی از طرفین دعوی توسط تأمین کننده شخص ثالث است که در ازای آن، تأمین کننده مالی درصدی از رأی صادره را در صورت پیروزی دریافت می‌نماید. هدف مقاله، تشریح و تحلیل اختلافات نظری موافقان و مخالفان تأمین مالی ثالث در خصوص دستیابی به عدالت، غربالگری دعاوی و تبعات مالی آن بر دولت است. در این مقاله موافقان، تأمین مالی ثالث را ابزاری جهت دستیابی به عدالت برای سرمایه‌گذاران زیان‌دیده در دعاوی سرمایه‌گذاری در نظر می‌گیرند در حالی که مخالفان با اتکا به اهداف سودآوری تأمین مالی ثالث، این روش را در داوری نوعی انتقال ثروت از بخش عمومی به بخش خصوصی می‌دانند و به ساختار نامتقارن رژیم داوری سرمایه‌گذاری و خطرات ناشی از انتقال مدیریت و کنترل فرایند داوری به تأمین کنندگان شخص ثالث نیز اشاره می‌نمایند.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitragem; Arbitration; Investment Arbitration Regime; Investments; Screening Mechanism for Claims; Third Party Funding; تأمین مالی ثالث; دستیابی به عدالت; رژیم داوری سرمایه‌گذاری; غربالگری دعاوی

Procedural powers of arbitrators in international arbitration- Real or perfunctory? - Mishra, Ajit Kumar (International Journal of Law, 2023)
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; International Arbitration; Lex arbitri; Procedural powers; Tribunal power

The Dilemma of International Arbitration Awards in Indonesia - Puspita, Lona; Budiono, Abdul Rachmad; Kusumadara, Afifah; Widagdo, Setyo (International Journal of Social Science Research and Review, 2023)
The final and binding nature of international arbitral awards results in the nullification of the rights of the parties to file legal remedies against the arbitral award, as is the case with decisions of national courts that can be appealed, appealed, or reviewed. However, Article 68 paragraph (2) of Law Number 30 of 1999 concerning arbitration and Alternative Dispute Resolution provides an opportunity for parties who refuse to recognize and implement an international arbitral award that can be appealed to, as well as Article 70 must also be explained that Article this applies only to national arbitrations. This of course creates legal uncertainty, disuse, and injustice for the parties. Therefore, what is highlighted in this research is what is the position of the final and binding international arbitration award in Indonesia. The research method used in this article is legal research using primary and secondary legal materials. The results of the research show that the position of international arbitral awards in Indonesia is not the same as the decisions of national courts because they cannot be appealed, cassated, and reviewed. Therefore, it is necessary to completely amend international arbitration arrangements by removing Article 68 paragraph (2) of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution in order to provide legal certainty, benefit, and justice for the parties.
Keywords: Award; Final and Binding; International Arbitration

L'unanimité de l'accord de conciliation en droit OHADA : une logique juridique irréaliste ? - Kourouma, Moussa Fanta (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2023)

Les garanties du procès équitable à l’épreuve des modes alternatifs de règlement de conflits - Guedegbe, Igor Samson Bidossessi (Revue Béninoise des Sciences Juridiques et Administratives, 2023)

The International Validity of Domestic Law in Investment-Treaty Arbitration - Jarrett, Martin (Arbitration international, 2023)
Keywords: Arbitrage; Arbitragem; Arbitration; Investment arbitration; Investments

Regards sur l’intervention du juge étatique dans la constitution du Tribunal Arbitral dans l’espace OHADA - Mainibe Tchiombe, Calice Cléopâtre (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
Qu’il soit institutionnel ou adhoc, L’arbitrage est vu comme un mode de règlement des litiges qui a vocation à se dérouler, de la requête initiale à la sentence finale, sans l’intervention du juge étatique. Il arrive, cependant que, ce juge soit amené à intervenir dans le processus arbitral, pour une raison ou pour une autre. On a pu ainsi dire qu’il n’y a pas de bon arbitrage sans un bon juge. Bien que l’intervention du juge étatique doivent rester exceptionnelle en matière d’arbitrage, il importe que ledit juge soit identifié, d’autant qu’il n’est pas le mena selon la phase à laquelle il intervient et peut varier d’une organisation judiciaire à une autre.
Keywords: Juge étatique; Organisation judiciaire

Les principes directeurs du procès équitable en médiation OHADA - Ngono Yakam, Marie Joseph (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
L'image de l’alternative et de la souplesse de la médiation semble aux premiers abords exclure les principes directeurs du procès équitable de ce mode de règlement des conflits. Mais la réalité en est tout autre. Entant qu'instrument de justice, la médiation ne saurait s’affranchir des garanties d’ordre procédurales. Cette survivance va donc de soi puisque tout comme le procès, la médiation fait intervenir un tiers. La présente étude consiste donc à examiner la question des principes du procès équitable appliqués à la médiation OHADA.
Keywords: Fair trial; Guiding principle; MARD; Mediación; Mediation; Mediação; Médiation; OHADA; Principe directeur; Procès équitable

L'arbitrage international dans les contrats publics en droits marocain et français - Raissi, Imane (Revue du Droit Marocain, 2023)
Le recours à l’arbitrage, comme mode de règlement des différends commerciaux internationaux qui s’applique aux contrats publics reliant les Etats et leurs démembrements et avec des investisseurs privés, s’est étendu au fur et à mesure de l’interventionnisme croissant de l’Etat dans l’économie et de la multiplication des leviers juridiques qui lui sont dédiés (marchés publics, gestion déléguée, partenariat public-privé, etc.). Or, ces contrats ainsi soumis à l’hypothèse de l’égalité des parties posent la problématique de l’équilibre entre la portée de la clause compromissoire et la souveraineté des Etats en matière du régime juridique et de la compétence juridictionnelle. Dans une approche comparée entre les Droits marocain et français, cet article analyse les effets du recours à l’arbitrage international sur les règles applicables aux contrats publics à l’origine du différend, notamment, au niveau de la clause attributive de compétence, la compétence juridictionnelle et l’exequatur des sentences arbitrales.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Commande publique; Contrat public; Droit comparé; France; Maroc; Morocco

Arbitrability of Intellectual Property Dispute: A Pragmatic Dispute Resolution Mechanism - Singh, Vaishali (International Journal of Science and Research, 2023)
Conventionally, conflicts over intellectual property rights have been addressed primarily in national courts. Nonetheless, there has been a considerable inclination towards arbitration in recent years. For example, the number of cases decided under the WIPO Arbitration and Mediation Rules is constantly increasing, and the number of specific IP-related arbitral institutions is rising as well. This is due, in part, to the territorially limited reach of state court procedures, which no longer match the needs of modern international commercial processes. The transition to arbitration is appropriate since arbitration is particularly well suited to settling intellectual property conflicts. Arbitration is a private process, which is especially beneficial in IP issues due to the sensitive nature of the material involved. Furthermore, specific knowledge is necessary to properly settle technological disputes, a challenge that might be overcome by choosing adequately competent arbitrators.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Intellectual property; WIPO (World Intellectual Property Rights Organization)

La jurisprudence arbitrale : composante principale du droit international des investissements - Uranga, Paul (Les Cahiers de droit, 2023)
Le droit international des investissements résulte principalement d’une multitude de traités d’investissement, souvent bilatéraux, parfois régionaux et très rarement multilatéraux. Ce régime éclaté, ayant l’arbitrage comme moyen principal de règlement des différends entre investisseurs et État, ne favorise pas, en théorie, l’émergence d’une jurisprudence réellement cohérente et pertinente. Toutefois, la pratique arbitrale florissante en matière d’investissement s’est révélée constituer une véritable jurisprudence à l’importance non négligeable. Bien que le précédent n’ait pas de valeur juridique obligatoire, force est de constater sa valeur persuasive et la systématicité de son usage. Une telle utilisation des précédents arbitraux a pu permettre le développement d’une compréhension commune des normes des traités d’investissement et favoriser ainsi indirectement le développement conventionnel de ce droit. La jurisprudence arbitrale innerve de ce fait tous les pans du droit international des investissements, du discours des arbitres à l’évolution même des normes applicables. C’est en cela que la jurisprudence arbitrale peut s’entendre comme la composante principale du droit international des investissements.

Effective strategies for resolving labour disputes in the corporate sector: Lessons from Nigeria and the United States - Uzougbo, Ngozi Samuel; Akagha, Onyinyechi Vivian; Coker, Julie Olajumoke; Bakare, Seun Solomon; Ijiga, Amina Catherine (World Journal of Advanced Research and Reviews, 2023)
The relationship between an employer and employee though governed by various laws and regulations can still at some point witness some disagreements and dispute. Labour disputes are not uncommon neither are they peculiar to a particular industry in a country. Usually, trade disputes are hinged on agitation of employees for compensation, good working conditions, job stability and agitation against unlawful termination or dismissal of from service. Over the years, employees have adopted different ways to exhibit their discomfort and grievances in order to convey their message such as strike actions, peaceful protest and so on.  There’s no doubt that these disputes will drastically reduce the level of productivity and overall beneficial impact of the industries in the economic growth of the country. Hence, there’s a need to adopt strategies for resolving these labour disputes. Some industries have applied round table discussions, arbitration, mediation, collective bargaining as well as grievances remedial processes. This work will provide an overview of the causes of disputes in the corporate sector, examine the features of the Nigerian and United States disputes resolution system and also juxtapose the strategies for resolving labour disputes in the two countries. Furthermore, it will provide recommendations to effectively addressing labour issues within the business sector.
Keywords: ADR; Alternative dispute resolution; Industrial relations; Legislative Framework; Multi-door courthouse; Trade unions

L’arbitrage des marchés publics - Sinclair, Kongni Ngoula (International Multilingual Journal of Science and Technology, 2022)
Les contrats administratifs, plus précisément les marchés publics, sont moyens par lesquels l’Etat assure sa mission d’intérêt général. Ainsi, il peut arriver que pendant la phase de passation ou d’exécution d’un contrat de marché public, que l’une des parties ne puisse pas accomplir les formalités, d’où la naissance d’un litige. De ce fait, pour résoudre ce litige, les parties peuvent décider d’un règlement à l’amiable du différend. L’arbitrage étant le mode par excellence de règlement à l’amiable des litiges, il est donc opportun en partant de ces spécificités, de mettre en œuvre la procédure d’arbitralité des marchés public et l’issue positive de cette procédure qu’est la sentence arbitrale.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; CEMAC; Commande publique; Contrats administratifs; GICAM; Marchés publics; Organes communautaires; Procédure arbitrale; Sentence arbitrale

The Unilateral Arbitration Clause between Permissibility and Nullity - Mahmoud Jaradat, Nashat; JassimSarhan, Ghassan (Information Sciences Letters, 2022)
Researching the judicial applications of Arab countries to one of the issues that have occupied legal thoughts in the Western world for decades and still in one form or another, the so-called Unilateral Arbitration Clauses, we did not find a discussion of the applicability of this clause within the laws. Even though this condition takes a reasonable space of the legal arguments as previously mentioned, it has even become widely used in contracts, such as tenancy, contracting, and financial investments. The study showed that the above-mentioned clause has recently increased its use in financing contracts, especially with the increasing globalization of banking services and bank transfers. Although banks usually prefer to resort to traditional litigation, lack of similarity in the legal rules and judicial applications related to banking transactions and their difference from one country to another was a reason for the banks preference of resorting to arbitration. There is no examination of the legitimacy of an unequal or optional arbitration clause in Bahrain. Also, the Bahraini and Egyptian courts, to the best of our knowledge, did not decide whether it should be considered null or valid. The same case is applied to the French courts which have no cases that examined this type of clauses except for a case in 2006 and the other is a judgment close to the same issue on October 7, 2015, from the French Court of Cassation. The English and American courts were different; they examined this clause and had several judicial implementations due to the fact that most of the arbitration terms are either related to multinational companies operating within the framework of the Wall Street Stock Exchange in New York or those that stipulate the enforcement of British and Wales law on the provisions of the contract . However, many Arab countries, in general, as well as Bahrain and some Gulf countries, in particular, are seeking in their economic model to attract foreign investments and capital, especially those related to financial and banking industries, to diversify sources of income. The decision of investing or not investing the capital in a country is made by the judicial authority in terms of independence as well as the judicial application of legal texts as these factors are directly reflected in the desire to invest and show the possibility of protecting investors.

Settlement of Disputes Arising from Documentary Credit Under National and International Regulations - Nour, Hoda Magdy (UAEU Law Journal, 2022)
The need Settlement of disputes arising from bank credit between national and international rules, protecting the interests of the bank and ensuring its financial rights before the debtor. As the Bank faces different technical and legal difficulties, as well as the multiplicity of legal adaptation, we deal with the rules governing banking accreditation from the point of pleadings law, and the methods of amicable settlement of these disputes and following, and compulsory execution. International efforts are taking the lead in establishing the technical regulation of bank accreditation and setting rules "DOCDEX" in 1997, and the 2015 amendments, which still need more as they do not provide a legal way to implement them. It is necessary to find out legal regulation at the domestic and international levels, which calls for the legislator to intervene to organize its rules and procedures. We have sought in this study to weave the legal entity to seize bank credit within the legally acceptable limits based on a system of seizure of the debtor with third parties against the background of the legal system of documentary credit and the relationships arising from it, and its financial and economic effects that go beyond the parties to the beneficiaries of companies, bodies, and economic institutions, As the matter still requires the existence of special legislation regulating the seizure of bank credit, to ensure the effectiveness of the guarantees surrounding the appropriations by the national legislator and at the international level. This would expand the insurance of bank credit so that the creditors recover their full right directly or by seizing the value of the credit, which calls for organizing this seizure with rules that consider the privacy of this seizure and its rules and are consistent with the required speed in such transactions in a way that protects the creditor from abuse, in a manner that ensures the observance of confidentiality, due process, and the spirit of banking work, anticipate the possible future that will witness the decline of documentary credit and replace it with electronic transactions, the establishment of specialized banking courts that save time and effort.

Business Dispute Settlement Through Mediation in State Courts and Arbitration Institutions - Yuspin, Wardah; Aziz, Abdul (International Journal of Social Science Research and Review, 2022)
In social life, there are often differences in perceptions between humans, causing problems or disputes, whether minor or serious. Likewise in the relationship of economic activities or more commonly known as business relations. Not infrequently humans experience a clash and differences of opinion that lead to disputes. Various problems will always arise in business as long as humans run their business solely for profit, so there are often differences of opinion because the parties will not be harmed which will eventually lead to disputes. In the end, dispute resolution, especially business disputes, is often resolved through a trial in court through a lawsuit by one of the parties who feel aggrieved. However, what was expected from the settlement turned out to be unsatisfactory for the parties because the settlement through litigation sometimes took a long time to obtain legal certainty so that it actually harmed business people because of the loss of time, energy and materials. As an alternative to resolving business disputes, business actors have a tendency to avoid disputes in court and choose to use mediation or through arbitration institutions. This study will briefly describe the comparison of business dispute resolution through court mediation with settlement through arbitration institutions. The research was conducted through descriptive empirical legal research.
Keywords: Arbitration; Business; Dispute

El principio de voluntariedad y la tenencia en mediación - Sarmiento, Mónica Piedra; Pazmiño, Esteban Polo (Polo del Conocimiento, 2022)
En los últimos tiempos la mediación se ha visto involucrada en varios conflictos y sucesos de la realidad actual, pues este procedimiento, como el resto de métodos alternativos de solución de conflictos siempre ha estado presente, sólo se tiene que acudir a los autores clásicos y observar que se hacía referencia a ellos. Sin embargo, la mediación ha tomado fuerza a través de su verdadero desarrollo hacia una cultura de paz. El principio de voluntariedad es una característica esencial en los medios alternativos a la solución de conflictos, en el que, las partes resuelven sus controversias en materia transigible, asistidos por un tercero neutral llamado Mediador/a, el mismo que, guía, y conduce a las partes a resolver de manera eficaz, eficiente, rápida, y legal los conflictos. Si bien es cierto, dentro de este procedimiento se presentan muchos problemas al momento de resolver esta situación, y se ha encontrado en el mismo con personas, situaciones, posiciones, intereses y necesidades diferentes, así también se evidencian sentimientos, que al momento de llegar a un acuerdo de tenencia, lo único que se prioriza es todo lo mencionado anteriormente, pero no de manera consciente y responsable el bienestar de los menores, y ante este escenario, las partes deciden, y como es lógico el tercero neutral (mediador) debe respetar esa voluntad. Para esta investigación se ha utilizado una metodología histórica - lógica, así como inductiva - deductiva y dogmática jurídica, con un tipo de investigación cuantitativo, y un nivel de investigación descriptivo, lo que permite detallar y caracterizar el fenómeno en estudio.
Keywords: Conciliación; Conciliation; Mediación; Mediation; Médiation; Relación padre – hijo.; Tenencia

The Right to Water in Investment Treaty Arbitration and Its Impact on Jurisdiction and Applicable Law - Geravand, Farshad (Public Law Researsh, 2022)
The right to water in investment arbitration has been one of the most contentious issues before investment arbitration tribunals in recent decades. The privatization of public services, including water and sanitation, and assigning them to foreign investors has caused the right to water as a vital benefit being repeatedly raised in investment arbitrations. However, due to tribunals’ narrow interpretation of jurisdiction and applicable law, this fundamental human right has been considered irrelevant and ignored, and this has fueled the legitimacy crises in investment arbitration. This research seeks to indicate the potentiality of more protection of the right to water through balancing the states international obligations in the two areas of investment law and human rights law. Proposed methods for integrating human rights with investment law include the correct interpretation of jurisdictional clauses and the applicable law based on the treaties interpretation principles, systematic integration and the inclusion of new clauses in investment agreements. طرح حق بر آب در داوری سرمایه‌گذاری یکی از مناقشه‌انگیزترین مباحث پیش روی دیوان‌های داوری در چند دهه اخیر بوده است. خصوصی‌سازی خدمات عمومی از جمله آب و فاضلاب و سپردن آنها به سرمایه‌گذاران خارجی موجب شده تا حق بر آب بعنوان یک منفعت عمومی و حیاتی بارها در داوری‌های سرمایه‌گذاری مطرح شود. با تفسیر مضیق محاکم از شروط صلاحیتی و قانون حاکم، این حق بنیادین بشری در برخی موارد نامربوط و نادیده تلقی شده و این امر به بحران مشروعیت در داوری سرمایه‌گذاری دامن زده است. این جستار می‌کوشد تا امکان حمایت بیشتر از حق بر آب را از طریق برقراری تعادل بین تعهدات بین‌المللی دولت‌ها در دو عرصه حقوق سرمایه‌گذاری و حقوق بشر نشان دهد و در پایان روش‌هایی را برای ادغام این دو از جمله تفسیر درست شروط صلاحیتی و قانون حاکم با تکیه بر اصول تفسیر معاهدات، تلفیق سیستمیک و گنجاندن بندهای جدید در موافقتنامه‌های سرمایه‌گذاری پیشنهاد کند.
Keywords: Applicable law; International Investment Arbitration; Jurisdiction; Right to Water; Systemic Integration; تلفیق سیستمیک; حق بر آب; داوری سرمایه‌گذاری بین‌المللی; شروط صلاحیتی; قانون حاکم

Role of Abuse of Rights Doctrine and Investment Arbitration Ratione Temporis in Limiting Nationality Planning - Saeedi, Niloofar; Askary, Pouria (Public Law Researsh, 2022)
Sometimes foreign investors after the dispute have arisen or when it is predictable and with the intention of bringing the dispute to arbitration, change their nationality or acquire new nationality. The phenomenon called Nationality Planning eases foreign investors’ access to a desirable treaty and increases the chance of bringing disputes against host states.So host states try to avoid these disputes by raising objections to Ratione Temporis or claiming abuse of rights. Arbitration tribunals’ approach towards their Ratione Temporis and abuse of rights is material in host states’ success in limiting Nationality Planning. So the question to be answered is that what requirements are considered by arbitrations in determining Ratione Temporis and abuse of rights and how these two are different. Arbitral precedent shows that these tribunals make distinction between cases of nationality planning contrary to their Ratione Temporis and cases that are considered as abuse of rights. However, in practice their strict approach results in limited acceptation of objections to Ratione Temporis or abuse of rights claims. گاه سرمایه‌گذار خارجی پس از بروز اختلاف یا زمانی که اختلاف قابل پیش‌بینی است و به قصد طرح دعوی در مرجع داوری، اقدام به تغییر تابعیت یا کسب تابعیت جدید می‌نماید. این اقدام که برنامه‌ریزی تابعیت نام دارد، دسترسی سرمایه‌گذار خارجی به یک معاهده سرمایه‌گذاری مطلوب را تسهیل کرده و احتمال طرح دعوی علیه دولت میزبان را افزایش می‌دهد. از این‌رو دولت‌های میزبان تلاش می‌کنند با طرح ایراد به صلاحیت زمانی یا سوء استفاده از حق، مانع پذیرش چنین دعوایی شوند. رویکرد مراجع داوری در احراز صلاحیت زمانی خود و تشخیص موارد سوء استفاده از حق، در موفقیت یا عدم موفقیت دولت میزبان در مقابله با برنامه‌ریزی تابعیت تعیین‌کننده است. بنابراین باید به این پرسش پرداخته شود که مراجع داوری چه شرایطی را برای احراز صلاحیت زمانی و سوء استفاده از حق در نظر می‌گیرند و چگونه میان این دو تمایز قائل می‌شوند. رویه مراجع داوری حاکی از آن است که این مراجع میان مواردی از برنامه‌ریزی تابعیت که مانع صلاحیت زمانی آن‌هاست و مواردی که سوء استفاده از حق تلقی می‌گردد، تمایز قائل می‌شوند. هرچند رویکرد سخت‌گیرانه آنها در عمل موجب می‌شود تنها در موارد محدودی ایراد به صلاحیت زمانی یا ادعای سوء استفاده از حق مورد پذیرش واقع شود.
Keywords: Abuse of rights; Bilateral Investment Treaty; Foreign Investment Arbitration; Nationality Planning; Ratione Temporis; برنامه‌ریزی تابعیت; داوری سرمایه‌گذاری خارجی; سوء استفاده از حق; صلاحیت زمانی; معاهده دوجانبه سرمایه‌گذاری

Effectiveness of the Recognition and Enforcement of the OHADA`S Arbitral Award - Juvelin, Rezara (International Journal of Social Science and Human Research, 2022)
OHADA is amongst an international organization consists of arbitral tribunal within regions in Africa to deal with international disputes on investment and commercial related. Henceforth, the purpose of the study examines the effectivity of arbitral awards enforcement under the perspectives of OHADA arbitration rules. The study axed through qualitative approach by interpreting legal rules, analyzing cases and commenting the weakness of the charter in terms of enforcement and recognition of arbitral awards. The decision of OHADA arbitral tribunal shall contain intrinsically legal effect to country members, however it leads problematics as the enforcement and recognition rules may be different in every country involved. Hence, the study interpreted the legal rules concerning enforcement and recognition of arbitral awards, effectiveness of the rules. In addition it exerted also the challenges and significant recommendation for improving the arbitration rules on enforcement of arbitral awards. It is found the weakness of the arbitral awards locates on refusal of concerned State to enforce the awards under the domestic law for undefinable conflict of interest
Keywords: Arbitrage; Arbitragem; Arbitral Awards; Arbitration; Enforcement; OHADA; res judicata and exequatur

Third Party Investment in International Commercial Arbitration - Ebrahimi, Seyed Sadegh; Boloori, Peyman; Solhchi, Mohammad Ali (Public Law Researsh, 2022)
International commercial arbitration imposes heavy costs to the parties involved. In this regard, one of the new phenomena in international commercial arbitration is "financing of court costs by a third party investor. There are several reasons for the emergence of a third party investor: 1- involved parties may not have the resources to pay for the costs of arbitration or they may be reluctant to use their funds to finance the litigation: 2. the uncertainty of receiving compensation as a result of paying the arbitration fees might encourage the parties to transfer this risk to a third party; 3. having its own advantages and disadvantages. Since the funder holds the power of the purse, TPF entails the risk of the control of the claim being transferred to the third party funder. We might ask whether international arbitration tribunals should examine the extent of the investor's influence in determining the allocation of costs or not. In addition, is it essential to disclose the third parties contracts confidential? Overall, it is concluded that those mentioned Tribunals should allocate and guarantee the arbitration cost and agree on disclosing of third parties fund contracts under urgent conditions by international arbitration tribunal. مراجعه به داوری تجاری بین المللی هزینه های کلانی را برای طرفین درگیر در فرآیند داوری به همراه دارد و تأمین این هزینه ها در خیلی از موارد به‌صورت مانع در مراجعه به داوری نمود پیدا می‌کند. در همین راستا یکی از پدیده‌های جدید در داوری تجاری بین المللی، «تأمین مالی هزینه دادرسی توسط سرمایه گذار ثالث» است. ظهور سرمایه گذار ثالث دلایل متعددی دارد؛ اولاً طرفین دعوی ممکن است فاقد امکانات مالی کافی برای هزینه های داوری باشند، ثانیاً ممکن است طرفین دعوی تمایلی به استفاده از منابع مالی خود برای تأمین مالی دادرسی پرهزینه نداشته باشند، ثالثاً عدم قطعیت ذاتی که در زمینه امکان اخذ خسارت در نتیجه دادرسی وجود دارد می تواند باعث تمایل طرف منازعه به انتقال این ریسک به شخص ثالث شود. پرسش این است که آیا محاکم تجاری بین‌المللی تعیین تخصیص هزینه‌ها بپردازد یا خیر؟ و آیا افشاسازی قراردادهای شخص ثالث ضروری می‌باشد؟ در نهایت این نتیجه حاص می‌شود که محاکم مذکور باید به تعیین تخصیص و تضمین هزینه‌های داوری پرداخته و از سویی با افشاسازی قراردادهای تامین مالی شخص ثالث در داوری تجاری بین المللی، در شرایط خاص و ضروری موافقت نمایند.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Cost Allocation; Disclosure; International Arbitration Tribunals; International commercial arbitration; Investments; Third Party Investment; Third parties; افشاسازی; تخصیص هزینه‌ها; داوری تجاری بین‌المللی; دیوان‌های داوری بین‌المللی; سرمایه‌گذاری شخص ثالث

A Legal Analysis of the Structure of Dispute Resolution Mechanisms of International Tax Agreements - Salehifar, Alireza (Public Law Researsh, 2022)
As international trade is expanding, international trade and tax disputes are increasing. Under international tax agreements, there are two mechanisms for the resolution of potential disputes between contracting States. These agreements mostly rely on a form of negotiation known as the “Mutual Agreement Process (MAP)” as the main mechanism for the settlement of disputes. During the last decade, the inclusion of “ad hoc arbitration” as a new dispute resolution mechanism in international tax treaties has become popular to augment the MAP. Iran has long concluded several international tax agreements with several countries for the avoidance of double taxation. Due to Iran’s macroeconomic policy for relying more on tax revenues as an alternative to revenues from the petroleum industry, it is important that the Iranian lawyers seek to focus more on tax law and tax dispute resolution mechanisms. The purpose of this article is to introduce and critically analyse the dispute resolution mechanisms of international tax agreements. In this article, to make some suggestions for the improvement of the dispute resolution system of tax treaties, the strengths and weaknesses of the MAP and ad hoc arbitration, will be scrutinised by adopting a descriptive-analytical approach. همسو با گسترش تجارت فراسرزمینی،‌ میزان دعاوی مرتبط با تجارت و مالیات‌های بین‌المللی نیز افزایش یافته است. در بسیاری از معاهده‌های مالیاتی بین‌المللی برای حل اختلافات، دو ساز و کار با عنوان «فرآیند توافق دوجانبه» و «داوری موردی» وجود دارد. فرآیند توافق دوجانبه که مبتنی بر مذاکره بین طرفین معاهده است بعنوان ساز و کار اصلی و داوری موردی هم که در یک دهه اخیر در این معاهده‌ها رواج یافته، بعنوان ساز و کار مکمل فرآیند توافق دوجانبه برای حل اختلافات استفاده می‌شوند. ایران از دیرباز جهت اجتناب از مالیات مضاعف، معاهده‌های مالیاتی متعددی را با کشورهای مختلف منعقد نموده است. همچنین سیاست کلان اقتصادی کشور در سال‌های اخیر مبتنی بر اتکای بیشتر به درآمدهای مالیاتی بعنوان جایگزینی برای درآمدهای نفتی بوده است. لذا اهمیت شناخت این نوع معاهده‌ها و‌ مکانیسم‌های حل و فصل اختلافات آنها برای حقوقدانان کشور بیش از پیش آشکار می‌شود. هدف این مقاله معرفی،‌ تحلیل و نقد ساز و کارهای موجود در معاهده‌های مالیاتی بین‌المللی برای حل اختلافات می‌باشد. در این مقاله نقاط ضعف و قوت فرآیند توافق دوجانبه و داوری موردی به شیوه توصیفی-تحلیلی بیان و راهکارهایی جهت بهبود این مکانیسم‌ها ارائه می‌شود.
Keywords: Arbitrage; Arbitragem; Arbitration; Dispute Resolution; International Tax Agreements; Mutual Agreement Procedure (MAP); Negotiation; داوری; فرآیند توافق دوجانبه; مذاکره; معاهده مالیاتی بین‌المللی; ‌ حل و فصل اختلاف

Dissenting opinions in international arbitration : More than an opinion? - Baltag, Crina (Principia, 2022)
Dissenting opinions have increasingly gained acceptance in international arbitration, with arbitration rules and laws allowing them, by either providing directly for such a possibility, or indirectly, by referring to ‘arbitral awards taken with majority of votes.’ Alan Redfern’s seminal 2003 Freshfields Lecture on dissenting opinions has highlighted the benefits, as well as the concerns with dissenting opinions, in particular, with those directed to alleged irregularities in the arbitral procedure. More recently, in the motion to set aside the arbitral award in Vantage Deep Water Co. v. Petrobras Am., Inc., the US District Court for the Southern District of Texas has rejected Petrobras’ argument that ‘the arbitral process was [so] “fundamentally flawed” … that “produced the extraordinary Dissent filed” by Mr Gaitis.’ While it is accepted that dissenting opinions have no legal effects, and in particular no legal effects similar to arbitral awards, they can have significant impact on the set aside and recognition and enforcement of arbitral awards. Las opiniones disidentes han ganado aceptación en el arbitraje internacional mediante reglas de arbitraje y leyes permitiéndolos, ya sea aceptando directamente la posibilidad de emitirlos, o indirectamente refiriéndose a ‘laudos arbitrales decididos por mayoría de votos’. El seminario del 2003 de Freshfields dictado por Alan Redfern sobre opiniones disidentes llamó la atención sobre los beneficios y las preocupaciones, en particular, aquellas opiniones disidentes dirigidas a señalar irregularidades en el procedimiento arbitral. Más recientemente, durante el procedimiento para anular el laudo arbitral de Vantage Deep Water Co. v. Petrobas Am., Inc., la Corte del Distrito Sur de Texas rechazó el argumento de Petrobras de que ‘el procedimiento arbitral había sido [tan] “fudamentalmente viciado…” que “produjo la extraordinaria opinión disidente consignada” por el Sr., Gaitis’. Mientras que es aceptado que las opiniones disidentes no tienen efectos legales, y en particular ningún efecto legal parecido a los laudos arbitrales, pueden lograr impactar significativamente a lograr la nulidad y el reconocimiento y ejecución de los laudos arbitrales.
Keywords: Anulación; Arbitral Awards; Dissenting opinions; Laudo arbitral; Recognition and enforcement; Reconocimiento y ejecución; Set aside; Voto salvado

A Closer Look at the Doctrine of Separability in Arbitration - Todorović, Ilijana (IUS LAW Journal, 2022)
In the ever-growing business world impacted by globalization, many commercial contracts nowadays contain an arbitration clause. This article focuses on the history behind arbitration as an alternative method of dispute resolution and its penetration to the forefront of mechanisms for resolving commercial disputes -with focus on England, France, and the United States. The article also delves into some of the key questions related to the relationship between an arbitration clause and the underlying contract in which it is contained. And those are the infamous separability and competence-competence doctrines. The author’s conclusion is that the efficiency of an arbitration clause is feasible only if its autonomy is entrenched and safeguarded from preventative and baseless court intervention. In that regard, the author addresses the consequences, current challenges, judicial and academic discourse, and the need for improvement when it comes to these two arbitral principles -all with the goal to provide contracting parties with forethought as to what to consider when drafting their contracts as to avoid unwelcome consequences.
Keywords: Arbitrage; Arbitragem; Arbitration; Competence-Competence; Doctrine; International Arbitration; Issues of Jurisdiction

Pratique de l'arbitrage international en Algérie : enjeux et modernisation - Bouchelaghem, Saloua (Revue des Sciences Juridiques et Politiques, 2021)
A l’instar des autres pays, l’Algérie a adopté la conception dualiste de l’arbitrage, avec un régime juridique réservé à l’arbitrage interne et un autre destiné à réglementer l’arbitrage international par des dispositions particulières (Titre II Chapitre IV du CPCA). Ce qui laisse supposer une plus grande faveur pour l’arbitrage international dont le régime juridique est moins contraignante que celui de l’arbitrage interne. Ce droit de l’arbitrage parvenu certes à un stade en évolution vers la modernité ne comporte pas moins certaines lacunes que le législateur ne manquera pas de combler au gré de l’expérience de la pratique. Like the other countries, Algeria has adopted the dualistic conception of arbitration, with a legal regime reserved for internal arbitration and another intended to regulate international arbitration by specific provisions (Title II Chapter IV of the CPCA). This suggests a greater favor for international arbitration, whose legal regime is less restrictive than that of internal arbitration. this law of arbitration, which has certainly reached a stage in evolution towards modernity, nevertheless has certain shortcomings, which the legislator will not fail to fill with the experience of practice.
Keywords: Algérie; Arbitrage; Arbitrage international; Arbitragem; Arbitraje; Arbitration; Contrôle des sentences internationales; Etat; Examination of international awards; Juge étatique; Personnes publiques; State judge; public figures

Capacity of the International Investment Arbitration Mechanism in Environmental Protection - Habibi Majandeh, Mohammad; Gholami, Afife (Public Law Researsh, 2021)
Environmental considerations have always been a challenge for foreign investment. The need to observe environmental minimums from the beginning to the end of the investment is also a concern of environmental law activists. In the meantime, the host state faces sometimes conflicting commitments. State dual obligations to foreign investors on the one hand, and the whole citizens on the other, has in many cases led to disputes, rooted in environmental norms. The main question is how the arbitration mechanism can take an active stand in the face of such disputes? The main purpose of this study is to examine the reflection of these conflicts in investment arbitration and the importance and role of arbitration in improving the environmental status. The authors of this paper believe that the arbitration system has tools that it can use in resolving disputes to balance these conflicting obligations. Some of these legal tools are directly or indirectly related to investment agreements, and others are beyond the treaty and based on international principles, rules, customs and practices. ملاحظات محیط زیستی همواره یکی از چالش های پیشروی سرمایه گذاری خارجی بوده است. لزوم رعایت حداقل های زیست‌محیطی از آغاز تا پایان سرمایه گذاری، از دغدغه های فعالان حوزه حقوق محیط زیست نیز می باشد. در این میان دولت میزبان با تعهداتی بعضاً متعارض روبروست. تعهدات دوگانه دولت در برابر سرمایه گذار از یک طرف و عموم شهروندان از طرف دیگر، در موارد متعددی به بروز اختلافاتی منجر شده که ریشه در هنجارهای محیط زیستی دارد. پرسش اصلی این است که سازوکار داوری در مواجهه با این نوع اختلافات، چگونه می تواند فعالانه موضع گیری نمایند؟ هدف اصلی این مطالعه بررسی بازتاب تعارض ها در رویه داوری سرمایه گذاری و اهمیت و نقش داوری در بهبود وضعیت محیط زیستی است. نویسندگان این نوشتار بر این باورند که سیستم داوری، ابزارهایی در اختیار دارد که می تواند از آنها در جریان حل اختلاف برای ایجاد تعادل میان این تعهدات متعارض استفاده کند. برخی از این ابزارهای حقوقی مستقیم یا غیرمستقیم با معاهدات سرمایه‌گذاری مرتبط است و دستهای دیگر فرامعاهده ای و ناشی از اصول، قواعد، عرف ها و رویه های بین المللی است.
Keywords: Arbitrage; Arbitragem; Arbitration; Bilateral Treaties; Environmental Protection; International Arbitration; Investment Disputes; Legal Instruments; ابزار حقوقی; اختلافات سرمایه‌گذاری; حمایت از محیط ‌زیست; داوری بین‌المللی; معاهدات دوجانبه

Comparison of Egyptian and English Mediation Procedures in Construction - Swelam, Ahmed; Eldosouky, Adel Ibrahim; El Korany, Tamer Mostafa (Journal of Engineering Research, 2021)
The mediation process is the parties' will to the dispute to reach an amicable, non-binding settlement to end their dispute. The Egyptian legislature adopted the idea of issuing a draft law on mediation in civil and commercial matters to settle disputes between the parties, whether before the litigation stage or after appearing before the courts. The Egyptian Ministry of Justice held many community dialogue sessions to find the final version of the draft law. However, the concerned authorities have not issued the law until writing this paper. This research aims to compare and analyze the Egyptian mediation procedures and the British mediation procedures to improve, develop, and enhance the Egyptian ones especially the draft law as well as overcoming the obstacles that hinder the spread of mediation. On the one hand, presenting the Egyptian procedures in the draft mediation law and the rules of the Cairo Regional Center for International Commercial Arbitration, CRCICA. On the other hand, the British procedures represented in the Institute of Civil Engineers' mediation rules, ICE.
Keywords: Egypt; England; Mediation

Post award arbitral tribunal's mandate under the UNCITRAL Model Law and national laws based thereon - Al Hyari, Omar Hisham; Al Ani, Abdullah Rabee (Heliyon, 2021)
The UNCITRAL Model Law on International Commercial Arbitration provides for the extension of the mandate of the arbitral tribunal post issuance of the final award for the issuance of correction, interpretation, additional award, and remittance of the award back to the arbitral tribunal to remove grounds for challenging the award. Using a doctrinal approach, this paper examines the deviations of the national laws of adopting jurisdictions from the Model Law in regards to this extended mandate, and evaluates the improvements and drawbacks in these deviations. Mainly, the findings of this paper are that, of the many deviations, the positive changes are those that provide comfortable and lenient default provisions for the benefit of inexperienced parties, and since correction, interpretation, additional award, and remittance are useful provisions that are designed to help self-rectify the arbitral process, without adversely delaying it, then the changes that increase the efficacy of these provisions are welcomed. On the other hand, unnecessary deviations are seen as drawbacks that hinder the harmonization of national arbitration laws aimed at by the Model Law. The adopting jurisdictions shall be limited to those acknowledged as such by the UNCITRAL.
Keywords: Additional award; Arbitrage; Arbitragem; Arbitration; Arbitrators' mandate; Award; Correction; Interpretation; Model Law jurisdictions; UNCITRAL Model Law

Mediación y Cultura de Paz en los Objetivos de Desarrollo Sostenible 2030 - Gonzalo-Quiroga, Marta (Polo del Conocimiento, 2021)
El objetivo de la presente contribución es analizar el papel de la mediación como bisagra referencial entre dos de los Objetivos de Desarrollo Sostenible (ODS) para 2030: el núm. 4 -Educación- y el núm. 16 -Paz, Justicia, e Instituciones sólidas-. La metodología empleada parte de un estudio del panorama internacional para detenerse en la legislación española, tanto en mediación como en educación en cultura de paz, con las correspondientes novedades al respecto. Todo ello responde a una investigación analítica sobre distintas bases legislativas, documentales y bibliográficas que, como resultado, ha dado lugar a la creación de distintas tablas que resumen la investigación y, pretendemos, contribuyan a facilitar su difusión, en el marco de los ODS 2030. Se trata así de promover la mediación como una de las herramientas esenciales para fomentar la convivencia pacífica, la educación y la justicia en el contexto universal de la cultura de la paz.
Keywords: Cultura de Paz; Cultura de paz; Culture of Peace; Educación; Education; Educação; Justice; Justicia; Justiça; Mediación; Mediation; Mediação; Objetivos de Desarrollo Sostenible (ODS); Objetivos de Desenvolvimento Sustentável; Sustainable Development Goals

Les centres d’arbitrage de l’espace OHADA face aux technologies de l’information et de la communication (TIC) - Ndongo Dimouamoua, Céline (Revue Juridique de la Sorbonne, 2021)
Depuis l’adoption de l’Acte uniforme relatif au droit de l’arbitrage, les centres d’arbitrage se sont multipliés dans la zone OHADA. Même si tous ces centres ne sont pas au même niveau de développement, les acteurs économiques leur confient de plus en plus le règlement de leurs différends. Toutefois, la fermeture des aéroports, la limitation des déplacements, l’impossibilité de se réunir, conséquences de la crise sanitaire mondiale apparue en mars 2020, ont perturbé le fonctionnement des centres d’arbitrage du monde entier, y compris ceux situés dans la zone OHADA. En abolissant les distances et les contraintes de temps, les technologies de l’information et de la communication (TIC) se sont révélées être des moyens efficaces de contournement des difficultés nées de la pandémie. En effet, les grands centres d’arbitrage en ont profité pour mettre en œuvre des solutions technologiques permettant de réduire l’impact de la crise sur les procédures arbitrales. Dans cet environnement hautement concurrentiel, la question de l’arbitrage en ligne dans les centres d’arbitrage de l’espace OHADA s’est alors de facto posée. La question de la place réservée aux TIC dans l’administration des procédures par ces centres et les moyens d’y développer l’arbitrage à distance est posée. Pour répondre à cette double interrogation, un état des lieux de l’arbitrage en ligne dans les centres d’arbitrage de la zone a été fait. Il en ressort que les règlements d’arbitrage des centres abordent le sujet de manière lacunaire. Bien plus, l’environnement économique et technologique dans lequel ils évoluent peut constituer un frein au recours aux TIC. La nécessité de compléter les règlements d’arbitrage sur des questions comme la cybersécurité, l’organisation des réunions virtuelles ou encore la signature électronique des documents est clairement apparue. Afin d’accélérer le développement de l’arbitrage en ligne, les centres d’arbitrage situés dans l’espace OHADA doivent aussi former leur personnel à l’usage des TIC, encourager les parties à signer des cyber-protocoles, et mettre à leur disposition des guides d’usage des TIC dans les procédures arbitrales. En pratique, la révolution numérique dans les centres d’arbitrage africains n’aura pas lieu sans les efforts combinés des centres, des parties et des arbitres. 22 ans après l’adoption de l’AUA, la compétitivité et la maturité des centres d’arbitrage de l’espace OHADA seront fonction de leurs capacités à intégrer les TIC dans leurs méthodes de travail.
Keywords: Arbitrage en ligne; Arbitrage institutionnel; Arbitration centres; Centres d’arbitrage; Cyber protocol; Cyber-protocole; Guides sur l’arbitrage en ligne; ICT; Institutional arbitration; OHADA; Online Dispute Resolution; Online arbitration guides; TIC; Vidéoconférence

L'arbitrabilité des litiges en droit des marchés financiers - Megam, Nadège Flore (International Multilingual Journal of Science and Technology, 2021)
Keywords: Arbitrage; Arbitration; Financial markets; Marchés financiers

The Role of Alternative Dispute Resolution (ADR) in Dispute Settlement of Logistics Activities - Quan, Gao (International Journal of Trend in Scientific Research and Development, 2021)
The Alternative Dispute Resolution (ADR) provides a non-litigation settlement mechanism for the parties of logistics activities. The advantages of ADR are highlighted in logistics dispute resolution due to the characteristics of logistics dispute and the difficulties faced in the litigation procedure. In the dispute resolution process, ADR means a simple, cost-efficient, and convenient method for the parties involved to settle disputes quickly, flexibly, and friendly. With its legitimacy and rationality, ADR should be the preferred choice for the parties involved in logistics dispute resolution.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Dispute settlement; Litigation procedure; Logistics activities; MARD; Mediación; Mediation; Mediação; Médiation

Mediation: Is There a More Promising Future? The Case of the Cairo Business Community - Soliman, Cherine (Arab Journal of Administration, 2021)
In an era of economic distress, some organizations have found refuge and growth potential in cooperation. Mediation, a highly recommended cooperative concept, has been enabled in certain countries but not all. Some applications lacked local cultural support making it, despite government efforts, a failure to launch. In this article, we investigate attempts to launch mediation in the Cairo Business Community (CBC). This study enabled us to revisit how Egyptian culture was prototyped by Hofstede and to question its representativeness. Hofstede has consistently described Egyptian culture as being highly cooperative / collectivist but our observations indicate that this culture is now more of an individualistic / competitive type, due to the tremendous economic difficulties that Egyptian society is going through. These difficulties and their impact on culture are at the heart of the explanation of the failure to launch mediation in the CBC.
Keywords: Cairo Business Society; Conflict Resolution; Culture; Egypt; Mediation

Les paradoxes de l'arbitrage institué par la Conférence Interafricaine des Marchés d'Assurances (CIMA) - Sindjui Siani, Brice Carlin (International Multilingual Journal of Science and Technology, 2021)
La constance dans l’arbitrage est sans doute la volonté dans le recours à ce mode de résolution de conflits. C’est parce que les parties trouvent un intérêt à l’arbitrage, qu’elles décident d’échapper à la compétence de principe des juridictions étatiques. Or, ce bel édifice est remis en cause par le législateur CIMA à l’article 276 par l’instauration d’une Commission Nationale d’arbitrage au sein des États membres dont les assureurs sont obligés de saisir lorsque nait un différend dans l’exercice des recours subrogatoires entre eux. Le paradoxe arbitral ainsi analysé comme ce qu’il est convenu d’appeler l’ « arbitrage forcé » n’empêche pas toute fois d’entrevoir dans ledit arbitrage institutionnel, un instrument au service de la justice et des assureurs tant les vertus sont variées.
Keywords: Arbitrage; Arbitration; Assureurs; CIMA; Commission Nationale d’Arbitrage; Insurers; National Commission of Arbitration; Recours subrogatoire; Recourse of subrogation

Experimenting with international commercial dispute resolution - Erie, Matthew S; Bookman, Pamela K (AJIL Unbound, 2021)
In this essay, we describe the overlapping phenomena of new legal hubs (NLHs), international commercial courts, and arbitral courts. We survey their impact on the law and geopolitics of international commercial dispute resolution, identifying key issues these new dispute resolution institutions raise. While the rise of international commercial courts spans authoritarian and liberal states, Western and Asian states, common law and civil law traditions, it also highlights and builds upon regional differences. We question the assumption that the establishment of new courts is always consistent with an increase in the rule of law, particularly in non-democratic states. We close with thoughts about the potential influence and future role of these institutions. Some of the procedural innovations discussed here may lead to shifts in international commercial dispute resolution for years to come, but the question of whether there is sufficient demand for these new institutions lingers.

The Power of an Arbitral Tribunal to Determine Its Own Jurisdiction in International Commercial Arbitration - Kamanga, Patricia N. S. (Beijing Law Review, 2021)
Keywords: Arbitration Agreement; Competence-Competence; Jurisdiction; Party Autonomy; Power

Le financement de l’arbitrage par les tiers - Makhlouf, Amel (Revue internationale de droit comparé, 2021)
ruit de la pratique anglo-saxonne, le financement de l’arbitrage par un tiers financeur connaît un essor significatif tant à l’échelle nationale qu’internationale. Intervenu en France ces dernières années, ce mécanisme permet à un tiers (fonds d’investissement, société de financement spécialisée…) de financer une partie ou la totalité des frais relatifs à une procédure arbitrale tels que les frais d’avocats, d’experts, de témoins, d’arbitres ainsi que ceux liés à l’exécution de la sentence arbitrale. En cas de succès, le tiers financeur perçoit en contrepartie un pourcentage sur les dommages et intérêts alloués par la sentence arbitrale à la partie financée . Bien que dans une large majorité des cas le tiers financeur intervienne en faveur de la partie demanderesse, il peut aussi intervenir en faveur du défendeur ayant formulé une demande reconventionnelle. Le tiers financeur assume seul les risques financiers liés à la procédure. Si la partie financée n’obtient pas gain de cause à l’issue de la procédure arbitrale, le tiers ne percevra donc aucune rémunération et ne sollicitera auprès de son client aucun remboursement des frais qu’il aura avancés pour lui.

The prospective evolution of international commercial arbitration - Purqurian, Lily Leila (Revue libre de Droit, 2021)
“It is a curious fact that the Americanization of international arbitration is a topic that is often felt but is rarely discussed.” Roger P. Alford Similar to Alford’s sentiments, the shift towards arbitration in the United States alone is a phenomenon often felt, but feebly interrogated. Law schools across the nation continue to operate under the premise of judicial decision-making grounded in “rights protection.”[1] Yet, there is a clear shift towards arbitration as the preferred procedural process, with over 303,999 cases resolved by way of arbitration in 2019 alone.[2] While this brief note does not seek to interrogate the shift towards arbitration as much as it intends to examine the impact of American arbitration on international commercial arbitration generally, that shift, as you will see, looms in the background of any and all analysis of arbitration in the United States. I will begin by briefly noting the origins- and current regime of international commercial arbitration in the United States so to address the impact of its arbitration law and arbitral institutions on arbitration globally. I will then offer thoughts on the prospective evolution of international arbitration in the United States and how that may change the directions of legal procedural processes both in the United States and abroad. I. ORIGINS- AND CURRENT REGIME OF INTERNATIONAL ARBITRATION IN THE USA As arbitration flourishes as the choice for commercial disputes, there is no doubt that the United States has become a newfound hub for arbitration. It was not always this way, however. The Federal Arbitration Act (FAA) of 1925 established a steady road to an increasingly pro-arbitration policy, in three chapters, that shows itself in case-law as: when in doubt, favor arbitration.[3] The first chapter of the FAA establishes the framework for arbitration seated in the U.S. and provides the grounds for enforceable arbitration agreements and awards, while the second and third chapters implement the 1958 New York Convention and 1975 Panama Conventions, respectively. The strictly pro-arbitration policy does not lack in its own confusion, however, because of its basis in an otherwise federalist system. The FAA has largely remained unchanged since its nascence and has thus, left a substantive amount of discretion in interpreting arbitration law in the United States to the Supreme Court. One such source of confusion in U.S. arbitration law due to a lack of amendment lies in the term “arbitrability.” Arbitrability is the susceptibility of a case to be resolved by way of arbitration. In order to define the parameters of this susceptibility, the Supreme Court has distinguished between “procedural” and “substantive” arbitrability, wherein the former concerns itself with “prerequisites such as time limits, notices, laches, estoppel, and other conditions” and the latter, with a court’s decision.[4] The benefits to arbitration remain unmatched for commercial entities, however, which inspires the aforementioned pro-arbitration policy despite any real judicial framework. Arbitration allows parties to customize their dispute resolution by choosing the venue, applicable procedural law, and an expert adjudicator who may be more familiar with the intricacies of the dispute, among other benefits. There is a commitment to secrecy that is not found in the common court and the single, binding, and final resolution of a dispute through arbitration is the precise source of criticism that inspires the flock towards arbitration. Without the federal rules of civil procedure that would otherwise govern litigation, arbitration is governed by the procedural rules that each side agrees upon. The FAA paved the way for case law in the United States that would eventually shape a stronger pro-arbitration policy than ever—counseling against “even the mildest interference by courts in the conduct of U.S.-seated arbitrations.”[5] II. THE IMPACT OF U.S. ARBITRATION LAW AND U.S. ARBITRAL INSTITUTIONS IN THE WORLD OF ARBITRATION Assessing the impact of U.S. arbitration law begins by assessing what characterizes U.S. law: civil procedure. The adversarial form of litigation in which procedural tools are employed by advocates to advance arguments in a distinct style distinguishes the United States from other countries—and this feature inevitably slipped, in some capacity, into global arbitral institutions. Because the Rules of Arbitration for the International Chamber of Commerce are so brief,[6] American lawyers had tremendous flexibility in bringing American trial procedures with them. This came specifically in the form of document production for discovery and cross-examinations “to confront adverse witnesses.”[7] Critics refer to these added procedures as costly in both time and expense, defining them as the source of the “Americanization” of arbitration. Yet, while there is truth to such criticism, it may be more accurate to acknowledge the incorporation of aspects of American trial procedure as one country’s influence on arbitration. Far from inheriting solely American practice, global arbitral institutions maintain classic procedural tools while assimilating facets of each major country’s influence on arbitration.[8] III. THE PROSPECTIVE EVOLUTION OF INTERNATIONAL ARBITRATION IN THE USA Apart from being a source of revenue,[9] international arbitration is the natural response to the increase in “trade, investment, and supply-chain relationships” that hope to live free of potential biases from domestic fora.[10] The California Supreme Court may have briefly lost sight of this when deciding Birbrower, wherein attorneys not admitted to the bar of a certain state are not only ineligible to recover attorney’s fee but also, may be fined for unauthorizing practice of law.[11] Since Birbrower over two decades ago, however, the California Legislature unanimously passed Senate Bill 766. Under SB 766, non-California lawyers are able to represent parties in international arbitration proceedings in California, bringing California to the arbitration table. As home to Silicon Valley – and even aside from big technology, home to some of the largest companies in the world – California’s SB 766 will bring a swath of arbitration proceedings to its terrain. While California may certainly work in tandem with New York as the home to arbitration for technology and privacy concerns, reserving trade and investment disputes for New York, California may very well be the next major hub of arbitration. Already, it has received massive interest in being an arbitration destination. SB 766 will transform that interest into a revenue. It thus becomes all the more important, internationally, to understand and confront the ways in which the Americanization of arbitration would take place. [1] See, e.g. Thomas E. Carbonneau, Revolution in Law Through Arbitration, The Eighty-Fourth Cleveland-Marshall Fund Visiting Scholar Lecture, 56 Clev. St. L. Rev. 233, 233 n.3 (2008), available at https://engagedscholarship.csuohio.edu/clevstlrev/vol56/iss2/3 (“judicial decision-making has shifted from rights protection to guaranteeing access to some form of adjudication. As a result, law and adjudication have become less sacramental.”) [2] See American Arbitration Association, Adr.Org, https://adr.org/ (last visited Dec. 28, 2019). [3] See, e.g., Moses H. Cone Memorial Hosp. v. Mercury Construction Corp., 460 U.S. 1, 24-25 (1983) (“[A]ny doubts concerning the scope of arbitrable issues should be resolved in favor of arbitration …”). [4] See Howsam v. Dean Witter Reynolds, Inc., 537 U.S. 79, 85 (2002) (distinguishing between “issues of substantive arbitrability [which] are for a court to decide and issues of procedural arbitrability, i.e., whether prerequisites such as time limits, notice, laches, estoppel, and other conditions precedent to an obligation to arbitrate have been met, [which] are for the arbitrators to decide.”) (citations omitted). [5] See Laurence Shore, Tai-Heng Cheng, Jenelle E. La Chuisa, Lawrence Schaner, and Mara V.J Senn, International Arbitration in the United States 1, 320 (2018). [6] George M. von Mehrem and Alana C. Jochum, Is International Arbitration Becoming Too American?, 2 Global Bus. L. Rev. 47, 51 (2011) available at https://engagedscholarship.csuohio.edu/gblr/vol2/iss1/6. [7] Id. [8] Philip J. McConnaughay, Introduction to International Commercial Arbitration in Asia 1, xxix (2002). In support of his assertion, McConnaughay reports that from 1995 to 2000, China’s leading international arbitration commission, CIETAC, received 4,200 new international commercial arbitrations and the Hong Kong International Arbitration Centre (HKIAC) received 1,394, totaling 5,594. Id. Note: interrogatories and depositions are not included. [9] See ICC (International Chamber of Commerce), ICC Arbitration Figures Reveal New Record for Awards in 2018, https://iccwbo.org/media-wall/news-speeches/icc-arbitration-figures-reveal-new-record-cases-awards-2018/. [10] Daily Journal, International Arbitration Finally Comes to California, Howard B. Miller, https://www.dailyjournal.com/mcle/330-international-arbitration-finally-comes-to-california. [11] See generally, Birbrower, Montalbano, Condon & Frank v. Superior Court, 17 Cal. 4th 119 (1998).
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial dispute; International Arbitration

国际商事仲裁费用构成及合理控制仲裁费用探索 - 侯, 进才 (Journal of Oil and Gas Technology, 2021)
仲裁作为解决国际商事争议的主要方式之一，受到国际工程承包企业的青睐，然而当事人在决定一个案件是否要提起仲裁时，常会把仲裁费用作为一个重要考量指标，高昂的仲裁费用可能会限制国际商事仲裁制度的健康发展。本文以2017版国际商会仲裁规则下的收费标准为基础，从仲裁费用的构成、计算方法入手，探讨了仲裁费用影响因素，并给出了控制仲裁过程费用的合理化建议。 Arbitration, as one of the main ways to resolve international commercial disputes, remains a popular choice for international engineering company. The arbitration fees will be an important evaluating indicator when the parties considering apply for arbitration. Expensive arbitration fees may restrict the healthy development of international commercial arbitration system. Based on the arbitration cost and fees under the arbitration rules of the 2017 edition of the International Chamber of Commerce, characteristics, composition and calculation method of the arbitration fees are showed in this paper firstly; then, its influencing factors are discussed. Reasonable suggestions for controlling the arbitration fees are given in the end of this paper.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration Fees; Composition of Arbitration Fees; Controlling the Arbitration Fees; International Commercial Disputes; 仲裁费用; 国际商事; 控制费用; 费用构成

Foreign Investments in Disputed Maritime Zones: Maritime Disputes as Events of Force Majeure in International Law and International Investment Contracts - Kassem, Hazem (BAU Journal - Journal of Legal Studies, 2020)
Sovereign rights in Exclusive economic zones and Continental shelves are functionally limited to the economic exploitation of these zones. Moreover, in the case of disputed maritime zones these sovereign rights are neither exclusive nor necessarily constant. Nevertheless, states are still expected to provide the investments established in these zones the same treatment they should provide in their territories where they exercise full and constant sovereignty. If a host state agrees to the establishment of an investment in a maritime zone that become later contested, do the occurrence of the contestation and the hazards arising from such contestation relief the host state from its contractual and treaty obligations toward the investment by virtue of the force majeure concept. This paper argues that a traditional interpretation of the force majeure concept in respect of investment agreements and contracts, hampers states ability to de-escalate their maritime disputes, diminishes its capacity to conclude delimitation agreements and reduces the promotion of the UNCLOS III as well as its mechanisms for disputes settlement. It proposes a contextualist interpretation of the force majeure concept that is adapted to the exploitation of disputed maritime zones and states obligations under the international law of the sea. First, it examines the concept of force majeure as a doc-trinal hypothesis and its applications in international contracts and international in-vestment agreements. Second, it analyzes the legal act of maritime contestation as a force majeure event according to the possible interpretations of the concept of “force majeure”. Finally, it examines the recurrent legal implications susceptible of arising out of a contestation; provisional orders and unfavorable delimitation and their qualifica-tion as a force majeure event in the realm of investment agreements and contract.
Keywords: BIT; Disputed maritime zones; Force majeure; Foreign investment; Investment contracts; Maritime contestation; Maritime delimitation; Provisional measures

La portée de la conciliation préalable en matière de procédures simplifiées de recouvrement de l'OHADA dans la réalisation des droits du créancier - Tonda, Franck (International Multilingual Journal of Science and Technology, 2020)
Keywords: Conciliation; Créancier; MARD; Procédure simplifiée; Recouvrement de créances

International Commercial Arbitration - Kizi, Boratova Ziyoda Sobir (International Journal of Trend in Scientific Research and Development, 2020)
This article is devoted to the complex analysis of the English legislation of the international commercial arbitration. The author analyzed the commercial disputes and the bodies that proceed these disputes in England as well as main statutes regulating the international commercial arbitrations of England. The international commercial practices of the London International Court of Arbitration are described. Moreover, the author represents the main conclusions formed on the basis of the provisions of the national legislation on commercial arbitration and the regulations of the most well-known international arbitrations in England.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Act 1996; Arbitration institution; Commercial disputes; International commercial arbitration; The LCIA Rules; The London International Court of Arbitration (LCIA)

التحكيم رديفاً للقضاء في حل المنازعات - دراسة فقهية - Abu Lail, Mohammad (Jordan Journal of Islamic Studies, 2020)
Arbitration is considered as one of the basic means that has been legislated by Islam to resolve the people's disputes. Usually the resolutions of the arbitration are fast, guarantee the rights, respect the essence of justice and reduce the level of the controversy. Today, arbitration plays a vital role in resolving the international disputes such as the economic, political and local disputes as long as its effect upon the resolution of the internal disputes. This study highlights on the arbitration role in resolving the disputes as along with judiciary through showing the advantages of the arbitration and explain the relationship between arbitration and judiciary. And clarify its areas and its implications in jurisprudence. This study found out that the arbitration has a pivotal role in resolving the disputes resulting from the contractual and non-contractual relationships and the disputes resulting from the people in their natural and moral capacity, both internally as well as externally The study has shown the jurisprudence has taken the lead in explaining the terms and effects of the arbitration.

Le rôle de la confidentialité dans la procédure préventive de conciliation de l’OHADA - Nkouamo Ngnegue, Luc Norbert (International Multilingual Journal of Science and Technology, 2020)
La procédure de conciliation est l’une des innovations de la réforme de l’Acte Uniforme relatif aux procédures collectives d’apurement du passif. Le législateur OHADA l’a institué dans l’objectif de mieux gérer la prévention de la cessation des paiements des entreprises en difficulté financière. La conciliation est entrée dans la sphère des procédures collectives de l’OHADA avec un principe clé à savoir la confidentialité. Le principe de confidentialité constitue une pierre angulaire de la conciliation au regard de la place qu’elle occupe dans le dénouement de celle-ci. Le législateur communautaire fait intervenir ce principe dans tout le dénouement de la conciliation. La confidentialité se présente ainsi comme un aspect phare de la procédure. Cet état de chose nous a alors amené à s’interroger sur le rôle que peut bien jouer cette confidentialité qui anime l’ensemble de la procédure préventive. Selon notre point de vue, la confidentialité joue un double rôle dans la procédure de conciliation. Elle favorise d’une part la protection du débiteur soumis à la procédure en lui assurant la préservation de son crédit ainsi que les informations divulguées et d’autre part, facilite l’efficacité de la procédure à travers son imposition générale même si elle est un peu fragilisée par certaines atteintes. The procedure of conciliation is an innovation of the uniform Act organizing the legal treatement enterprises difficulties. The OHADA lagislator has institute it with the objective for the better manage in the suspension of payments prevention for enterprises in financial difficulty. The conciliation procedure has come in the sphere of OHADA legal treatement enterprises difficulties with a main principle which is confidentiality. The principle of confidentiality constitute a cornerstone of the conciliation procedure ending according to the Sport place it occupe. The Community legislator makes this principle to intervene in all the conciliation procedure. The confidentiality is present as a main aspect of the procedure. This situation brought us to question the role of the confidentiality witch lead all the preventive procedure. According to our point of view, the confidentiality plays a double role in the conciliation procedure. It favours firstly the protection of the debtor submit to the procedure insuring the preservation of his credit as well as divulgates informations and secondly, it facilitate the effectiveness of the procedure by his general using even it is fragilize by certains attacks.
Keywords: Cessation des paiements; Conciliation; Confidentiality; Confidentialité; Debtor protection; Efficacité de la procédure; Procedure effectiveness; Protection du débiteur; Suspension of payments

The Changing Paradigm of International Tax Dispute Settlement: What Are the Promises and Challenges of Mandatory Arbitration for China? - Ji, Xueliang (Oregon Review of International Law, 2020)
Through comparing dispute resolution methods under bilateral investment treaties (BITs) and bilateral tax treaties, this Article critically discusses the advantages of incorporating mandatory arbitration in bilateral tax treaties and demonstrates that national sovereignty will not be decreased by it. As a result, the Article argues that it would, in fact, be beneficial for China to adopt the mandatory arbitration method, which would further strengthen the global reform initiated by the OECD.
Keywords: China; Dispute resolution; International tax law

Reimagining the Framework for Resolving Intra-African Commercial Disputes in the Context of the African Continental Free Trade Area Agreement - Onyema, Emilia (World Trade Review, 2020)
This article examines the effectiveness of the framework for the resolution of intra-African cross-border commercial disputes, arising from the projected increase in intra-African trade in goods, services, and investments under the African Continental Free Trade Area. It examines the peculiar nature of intra-African trade and of the participating entities to provide the context to discuss the three major processes adopted in commercial dispute resolution (litigation, mediation, and arbitration) in Africa. It then argues for the promotion of arbitration as the dispute resolution process of choice for such disputes. It reimagined the framework for arbitration at the continental level and made two proposals targeted at the greater efficiency of the process: the designation of Regional Arbitration Centres across the African Union's eight recognized Regional Economic Communities, to administer such references; and the establishment of an African Commercial Court as a one-stop court for the enforcement or annulment of the final award.
Keywords: AfCFTA; Arbitrage; Arbitragem; Arbitration; Commercial dispute; Dispute Resolution; Litigation

The Applicability of Mediation as an Alternative Dispute Resolution Mechanism under OHADA Law - Leinyuy, Kifemmabuh Antonia (Scholars International Journal of Law Crime and Justice, 2020)
Almost 20 years after it adopted the Uniform Act on Arbitration, OHADA revised its Uniform Act on Arbitration and adopted a new Uniform Act on Mediation along with the fresh set of arbitration rules of the Common Court of Justice and Arbitration in Abidjan. These three texts were revised with the assistance of consultants. Among other changes, with the 2018 Uniform Act on Mediation, a solid platform for the use of mediation in the region is now in place. The ability of mediators to carry out their adjudication function with judicial intervention remains a major challenge by parties under the OHADA zones. In this light, the worry which this article seeks to uncover is how the new mediation law is applicable and facilitates the amicable settlement of investment disputes. The article also highlights the legal basis regulating the mediation process as a whole. In attaining these objectives, we employ doctrinal research methodology. The article conclude with vigorous recommendations which if effectively implemented will go a long way to enhance business (investment) security.
Keywords: ADR; Alternative dispute resolution; Applicability; Dispute resolution mechanism; MARD; Mediación; Mediation; Mediação; Médiation; OHADA Uniform Act

The Standards for Proving Damages and Its Amount: A Comparative Study under Transnational Instruments and International Arbitration Awards - Shoarian, Ebrahim; Sahebjam, Sara (Public Law Researsh, 2020)
Defining the applicable standards for proving and measurement of damages constitute one of the most significant issues under the law of damages. In principle, an aggrieved party, who claims compensation for damages based on contractual liability is responsible for showing the existence and the amount of losses suffered or to be suffered. Due to great importance of the issue, transnational instruments of contract law, such as UNIDROIT Principles of International Commercial Contracts (UPICC), Principles of European Contract Law (PECL) and Draft Common Frame of Reference (DCFR) have set out, explicitly or implicitly, special standards such as reasonable certainty, reasonably likely to occur and so on for proving damages; By contrast, the Iranian laws and regulations including the Civil Code do not set out such standards. The legal scholarship and jurisprudence have also failed to address the issue. Therefore, a comparative study of the issue with particular look at international instruments and arbitral awards could provide a reliable source of guidance. This paper analyzes the general and specific standards for proving damages and those situations that fall outside of ambit of the standards such as late payment damages. By doing so, the paper tries to open the debate in Iranian law. یکی از موضوعات قابل توجه در حوزه حقوق خسارت، تعیین استانداردهای قابل اعمال برای اثبات خسارات و میزان آنها است. علی القاعده، زیان‌دیدهای که به استناد مسئولیت قراردادی برای مطالبه خسارت اقامه دعوی میکند، بایستی اصل و میزان خسارتی را که متحمل شده یا خواهد شد، به اثبات برساند. نظر به اهمیت موضوع، اسناد فراملی مربوط به حقوق قراردادها از جمله اصول قراردادهای تجاری بینالمللی، اصول حقوق قراردادهای اروپا و پیشنویس طرح مشترک مرجع، به صورت صریح یا ضمنی، استانداردهای مشخصی مانند قطعیت متعارف، وقوع محتمل متعارف و غیره را برای اثبات خسارت پیشبینی کردهاند. در مقابل، مقررات موضوعه ایران از جمله قانون مدنی؛ چنین استانداردهایی را تنظیم ننموده و موضوع نیز مورد بررسی حقوقدانان و رویه قضایی قرار نگرفته است. بنابراین، مطالعه تطبیقی موضوع با نگاهی ویژه بر اسناد بینالمللی و آرای داوری می‌تواند منبع قابل اتکایی برای طرح بحث باشد. این مقاله، استانداردهای عام و خاص اثبات اصل خسارت و میزان آن و نیز مواردی مثل خسارت تأخیر تأدیه را که خارج از قلمرو شمول این استانداردها هستند، مورد تحلیل قرار میدهد و در نهایت تلاش دارد تا باب بحث را در حقوق ایران بگشاید.
Keywords: Arbitral Awards; Reasonable Certainty; Reasonably Likely to Occur; Standard for Proving Damages; Transnational Instruments; آرای داوری; استاندارد اثبات خسارت; اسناد فراملی; قطعیت متعارف; وقوع محتمل متعارف

Fall of Last Safeguard in Global Dejudicialization: The Problem of Protecting Public Policy in Private Business Disputes - Ghodoosi, Farshad (Oregon Review of International Law, 2020)
The importance of courts is shrinking. This is largely due to global dejudicialization: the process of outsourcing disputes to private dispute resolution. In the last several decades, along with the triumph of neoliberalism, privatization of the resolution of disputes has become the gospel of modern judiciaries. Courts have been pushed to the tail end of the private adjudication process and are used only as the last resort. The courts’ warm embrace of this structure along with practitioners’ push has led to a staggering expansion of private dispute resolution. The world therefore has witnessed an unprecedented growth of arbitration—the primary mode of private dispute resolution.
Keywords: Business law; Dejudicialization; Dispute resolution; Déjudiciarisation; Privatization; Public policy

L’exécution forcée des décisions de la Cour commune de justice et d’arbitrage et des sentences arbitrales impliquant le droit de l’OHADA - Kangambega, Élisabeth L. (Revue Burkinabè de Droit, 2020)

Arbitration related lessons: Insights from the supreme courts around the world - Nigmatullina, Dilyara; Vanlerberghe, Beatrix (b-Arbitra : Belgisch tijdschrift voor arbitrage, 2020)
In international arbitration, arbitrators have procedural powers that allow them to manage and conduct the arbitration proceedings in a fair and efficient manner. These powers are typically set out in the arbitration rules that the parties have agreed to, such as the International Chamber of Commerce (ICC) rules or the United Nations Commission on International Trade Law (UNCITRAL) rules. Arbitrators have the authority to determine the procedure to be followed in the arbitration, including the admissibility, relevance, materiality, and weight of the evidence presented. They can also decide on the language to be used in the arbitration and the location of the hearings. In addition, arbitrators can issue orders and directions as needed to ensure the fair and efficient conduct of the proceedings. This may include ordering the production of documents or witness testimony, or setting time limits for the submission of evidence. The present paper critically examines the lex arbitri, the law that governs the arbitral proceedings, and makes out a case that lex arbitri cannot be challenged in court, as the parties to the arbitration have agreed to resolve their disputes through arbitration rather than through the courts. However, if the tribunal exceeds its powers or acts in a manner that is inconsistent with the lex arbitri, the parties may have grounds to challenge the tribunal's decision on the grounds of lack of jurisdiction or due process. The paper summarises some key judgments in which Courts have upheld or quashed the Tribunals procedural orders. It will be concluded that the procedural powers of arbitrators in international arbitration are real and not perfunctory, though bounded within powers extended by Parties to the arbitral tribunal.
Keywords: Arbitrage; Arbitragem; Arbitration

基于国际商会仲裁规则下的国际工程项目仲裁管理 - 侯, 进才 (Journal of Oil and Gas Technology, 2020)
随着世界经济全球化，国内外企业之间的商贸往来迅猛发展，出现商事争议与纠纷的案件也呈现上升趋势，仲裁以其高效、快速等优点成为解决国际商事纠纷的最终方式之一。本文从仲裁的优点入手，首先阐述了完整仲裁过程中各个关键环节及注意事项，然后用流程图和横道图两种形式体现了一个完整的仲裁过程，最后就国际工程项目仲裁管理给出了具体建议。 With the globalization of the world economy, the commercial exchanges between domestic and foreign enterprises are developing rapidly, and the number of commercial disputes cases is growing quickly. Considering its advantages of high efficiency and speed, arbitration has become one of the final ways to solve international commercial disputes. This paper firstly presents the advantages of arbitration, then expounds the key stages and attention during the whole arbitration process. Flow chart and Gantt chart are drawn to show logics of the process. Specific suggestions on the arbitration management of international projects are given at the end of the article.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration Management; Arbitration Process; International Project; 仲裁程序; 仲裁管理; 国际工程

Problems of Enforcement of ICSID Awards: An Analysis of Micula Case - Hasankhani, Ali (Public Law Researsh, 2019)
In the case Micula A.O. v. Romania, the arbitration tribunal established under the auspices of the International Center for Settlement of Investment Disputes (ICSID) sentenced Romania to pay a compensation for the revocation of investment incentives and for the breach of fair and equitable treatment principle that had been laid down in a bilateral investment treaty between Sweden and Romania. Considering investment incentives as a breach of the EU regulations regarding state aids, the European Commission then rendered a directive, prohibiting the enforcement of the arbitration award by the member states. As articles 53 and 54 of ICSID emphasize that the awards are binding, the EU Commission’s act of rendering the aforementioned directive, and the member states refusal to comply with the award equals to giving the EU law primacy over international law, which should be considered as a breach of their international obligations. Using a descriptive-analytical method, this article seeks to explain the viewpoints of the parties and the courts which were asked to enforce the award, as well as to determine the nature of their acts.

A arbitragem internacional de protecção de investimentos e a dupla nacionalidade: dois pode ser igual a zero? - Duarte, Tiago (e-Publica, 2019)
The assessment of the investor’s nationality is of utmost relevance to determine the arbitral tribunal’s jurisdiction in Investor-State Arbitration. In treaty-based arbitration the investor must give evidence that is protected by the BIT, which means that he must have the nationality of the State party to the BIT that is not the host State. The case law considers irrelevant the fact that the investor possesses another nationality besides the nationality of the State party to the BIT and considers also irrelevant the fact that the invoked nationality is not the dominant one. Things get more serious if the investor has also the nationality of the host State (double nationality). In this scenario the investor cannot launch an ICSID arbitration against the host State because the Washington Convention forbids it. The possibility of an ad hoc arbitration is subject to the interpretation of the applicable BIT which has led to an unstable case law both because the BITs are not all equal and because different tribunals have analyzed the dominant nationality doctrine in different ways. A determinação da nacionalidade do investidor é um dos elementos mais importantes para a verificação da jurisdição dos tribunais arbitrais nas arbitragens de proteção de investimentos. Nas arbitragens baseadas em BIT (bilateral investment treaties) o investidor que inicia a arbitragem tem de demonstrar que está protegido pelo BIT que pretende invocar, pelo que terá de possuir a nacionalidade do Estado parte nesse mesmo BIT, que não seja o Estado onde o investimento foi realizado. A jurisprudência tem considerado irrelevante o facto de o investidor poder ter outras nacionalidades, para além da nacionalidade do Estado parte no BIT, desvalorizando igualmente o facto de essa nacionalidade não ser a nacionalidade dominante do investidor. Tudo se complica no caso de o investidor possuir igualmente a nacionalidade do Estado onde o investimento foi realizado. Nesse caso o investidor não poderá iniciar uma arbitragem com base no ICSID tendo em conta que a Convenção de Washington veda essa possibilidade. Já no caso de arbitragens ad hoc tudo dependerá da interpretação do BIT em concreto, o que tem levado a uma flutuação jurisprudencial, seja porque os BIT são diferentes, seja porque tem havido diferentes abordagens jurisprudenciais quanto à relevância da nacionalidade dominante.

Causes of Delay in the Resolution of Commercial Disputes via Litigation Arbitration as a Way out within OHADA Laws - Sigala, Buma Roland (International Journal of Trend in Scientific Research and Development, 2019)
An essential requirement of justice is that it should be dispensed as quickly as possible. It is a well-known adage that, « justice delayed is justice denied». Delay in litigation is caused by a number of factors. For example in litigation the parties have the right to make a counterclaim, right to make appeal etc. Arbitration has been able to overcome the factors which cause delay in litigation because in arbitration, parties are given the right to exclude the possibility to make a counterclaim, the right to make appeal has expressly been prohibited by the Organization for the Harmonization of Business Laws in Africa (OHADA)1 legislator etc. But since the OHADA legislator has not expressly prohibited counter claim in arbitration, it is recommended that counterclaim should be expressly prohibited in arbitration as it is the case with appeal. This article aims at identifying the causes of delay in the disposal of commercial disputes via litigation and how these causes of delay have been combated in arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial dispute; Delay commercial; Disputes Litigation; Law and management

Médiation du champ pénal dans le monde francophone - Jullion, Daniel (La lettre des médiations, 2019)
Initiée au milieu des années 80, dans le contexte bien particulier de la politique de la ville mise en place par un nouveau pouvoir politique, la médiation pénale a bénéficié du contexte très favorable des relations mises en place entre le politique et le judiciaire lors de la création du CNPD (1), sous la présidence de Gilbert Bonnemaison (2), des CCPD puis, en 1988 de la DIV (3) et, enfin la circulaire du 10 juillet 1989 « ... participation de l’institution judiciaire à la politique de prévention ». Véritables instances de concertation sur les problèmes de société et de sécurité, élus et professionnels se sont rapprochés sur leurs préoccupations communes : apporter une réponse « sociale » à un « contentieux de masse » (constitué de « petits » actes de délinquance qui participent au sentiment d’insécurité) et que « ... la Justice traiterait mal ou pas du tout ... » selon l’expression de G. Apap (alors procureur de la République de Valence) qui a initié les premières expériences de médiation pénale (appelée à l’époque « conciliation pénale » ... !!).
Keywords: Droit pénal; Mediation; Médiation

What the African Continental Free Trade Agreement Protocol on Dispute Settlement says about the culture of African States to Dispute Resolution - Akinkugbe, Olabisi (Articles, Book Chapters, & Popular Press, 2019)
An effective Dispute Settlement Mechanisms (DSM) upholds a rules-based trade regime; enunciates, clarifies and develops the jurisprudence of its constituent trade agreement; and also ensures predictability in the trading regime. Article 20 of the African Continental Free Trade Agreement (AfCFTA) establishes the DSM. The AfCFTA Protocol on Dispute Settlement (“Dispute Protocol”) provides for the rules and procedures for the settlement of disputes. Unlike the majority of the African regional economic community courts that are modelled after the Court of Justice of the European Union, the AfCFTA-DSM follows a handful of other regional judicial bodies – such as the Southern African Community Development Community (SADC) and the Tripartite Free Trade Area Agreement (TFTA) – that are modelled after the World Trade Organization (WTO) dispute settlement mechanism.
Keywords: AfCFTA; Dispute Settlement Mechanisms; Free Trade; Trade Agreement

Médiation dans le domaine de la santé - Bonafe-Schmitt, Jean-Pierre (La lettre des médiations, 2019)
Depuis le milieu des années soixante-dix, la médiation s’est développée dans tous les champs de la vie sociale de l’entreprise à la famille, sans oublier le quartier ou l’école… et plus tardivement dans le champ de la santé, ce qui tend à démontrer qu’il existe un certain nombre de résistances à son développement1. Pourtant, au-delà du phénomène de mode, il convient de s’interroger sur ce renouveau de la médiation qui ne peut pas être réduit à une simple technique de gestion des conflits, car elle vise plus largement à (re)créer du lien social dans nos sociétés marquées par l’individualisation, la fragmentation, le délitement des rapports sociaux. Le domaine de la santé n’échappe pas à ce délitement des se caractérise à la fois par la montée des incivilités et de la violence dans les établissements hospitaliers, et plus largement par une crise de confiance entre le monde médical et les patients.
Keywords: Mediation; Médiation; Santé

May an employer dismiss an employee if the disciplinary chair imposed a lesser sanction? South African Revenue Service v Commission for Conciliation Mediation and Arbitration 2017 38 ILJ 97 (CC) - Calitz, Karin Beatrix (Stellenbosch Law Review, 2019)
In South African Revenue Services v Commission for Conciliation, Mediation & Arbitration, Kruger, the employee, called his superior a “kaffir” on more than one occasion. The employer unilaterally dismissed the employee after the chairperson of the disciplinary hearing had imposed a lesser sanction. In doing so, the employer disregarded the collective agreement which did not make provision for the sanction of the disciplinary chair to be substituted. The employee claimed that his dismissal was invalid and therefore unfair. The Commission for Conciliation Mediation and Arbitration (“CCMA”), Labour Court and Labour Appeal Court (“LAC”) agreed. However, in the Constitutional Court (“CC”) the employer no longer argued that it was entitled to substitute the sanction in the light of the breach in the trust relationship, but only alleged that reinstatement was a remedy that no reasonable decision-maker would order. The CC agreed and held that the dismissal was substantively fair but procedurally unfair. The CC did not answer questions of lawfulness, fairness and invalidity, but in Steenkamp v Edcon the CC held that employees claiming remedies for unfair dismissal in terms of the Labour Relations Act 66 of 1995 (“LRA”) should not rely on invalidity. However, employees still have the right to common-law remedies based on their employment contract. Considering the importance of collective agreements, negotiated disciplinary codes, certainty and consistency, and to avoid employers exercising unfettered power over employees, state organs should apply for a review of an unsatisfactory sanction by the disciplinary chairperson in terms of section 158(1)(h) of the LRA. Private employers could negotiate a disciplinary code which allows both the employer and employee to appeal against the decision of the disciplinary chair which should make provision that a more severe sanction can be imposed on appeal.
Keywords: Arbitrage; Arbitragem; Arbitration; Commission for Conciliation; Dismissal of employees; Labor discipline; MARD; Mediación; Mediation; Mediação; Médiation; South Africa; South African Revenue Services

La protection du tiers lésé par une sentence arbitrale - Do, Van dai (Revue internationale de droit comparé, 2019)
L’arbitrage est un mode de règlement des litiges convenu entre les parties mais il se peut que la sentence issue de ce mode de règlement porte atteinte au tiers, qui n’est ni partie, ni représenté à l’instance arbitrale. La présente étude comparative montre qu’il existe divers moyens de protection offerts au tiers lésé mais le meilleur instrument de protection est la tierce opposition contre la sentence arbitrale. Toutefois, une telle tierce opposition est encore peu connue dans le monde, de très nombreux systèmes, l’ignorent. En espérant que ce recours se développe au profit du tiers, cette étude montre ses avantages, sa consécration dans certains pays ainsi que son régime juridique. Arbitration is a mode of dispute resolution agreed between the parties but it is possible that the award resulting from this method of settlement infringes a third party’s right, who is neither a party nor represented in the arbitration proceedings. This comparative study shows that there are various means of protection offered to the injured third party but the best protection instrument is the third party opposition to the arbitration award. However, such a third party opposition is still not widely known in the world, many systems ignore it. Hopefully this remedy will be developed for the benefit of the third parties, this study shows its advantages, its recognition in certain countries as well as its legal regime.

L'avocat et la résolution des conflits - Dutoit, Nicolas (Anwalts Revue de l'Avocat, 2019)
Keywords: Arbitrage; Conciliation; Différends; Droit collaboratif; Litiges; Médiation; Négociation; Orientation préalable; Résolution de conflit

A Critical Look at the Mechanism for Challenge of Arbitrators Under ICSID Convention and Arbitration Rules - Gautama, Ivan (Juris Gentium Law Review, 2019)
Administered arbitrations under ICSID are amongst the most-utilized means to resolve investor-state disputes. Part of why it is so is because the ICSID as an institution is heavily affiliated with the World Bank. This affiliation serves as a double-edged sword in ICSID’s hands: while on one side such affiliation lends ICSID the credibility any successful arbitral institutions need, on the other side ties between the two institutions are proving to become too close for comfort. This paper explores what could go and has gone wrong in the past within the current ICSID arbitration system with regards to the mechanism for challenging arbitrator(s), and whether such mechanism allows ICSID to effectively deliver what it is expected to provide.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Conflict of interest; ICSID; Investor-State; World Bank

Online Dispute Resolution: Methods and Effects - Kumari, Poonam; Sood, Geetika (International Journal of Science and Research, 2019)
The concept of online dispute resolution came with the development of e-commerce. It is a branch which resolves the dispute between parties without interference of court. It includes arbitration mediation and negotiation. It also includes consumer to consumer disputes. With the emerging to globalisation the concept of online dispute resolution emerging day by day. The purpose of this study is to present the main facets of online dispute resolution, including a definition of the term, the types of resolution available, and the most recent legal regulations in this area. Thearticle is a study of ODR, online mediation and electronic arbitration. It includes their uses and their relationships with e-commerce. The paper is regarding primary aspects of online dispute resolution, its definition and its growth and development. It also includes the relationship between ODR and technology. Research paper isdiscussing the two forms of ODR: online mediation and electronic arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Online Dispute Resolution

Emerging Issues in Arbitration, Mediation and Conciliation - Sunil, Bhawna Bhelly (International Journal of Science and Research, 2019)
The resolution of disputes through alternative dispute resolution mechanisms has gained momentum over recent decades. It has increasingly occupied space in the academic literature as the “new” method to achieve “justice” for disputing parties. It is important to note that a variety of definitions of “justice” can be relied upon. However, in many cases, justice will mean the parties being able to resolve their dispute fairly, justly and amicably by applying law or legal principles. Traditional legal mechanisms for resolving disputes have been increasingly questioned as to whether they are actually capable of achieving justice in individual cases. Resolution in the courts is not only the method of resolving disputes . If the parties can resolve their own disputes then there will arise no need for court system in world. All though court system is good and fair way of dealing with civil disputes yet it might not be the best method to resolve the disputes. Basically there are four ways to of alternate dispute resolution. They are Negotiation, Mediation, Conciliation and Arbitration . The of ADR is to resolve the matters in a cost effective manner and foster long term relationship.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Conciliation; MARD; Mediación; Mediation; Mediação; Médiation; Méthodes alternatives de règlement de conflit

Problématique de la compétence et de la procédure devant la Cour Commune de Justice et d’Arbitrage de l'OHADA : cas de recours dans les litiges commerciaux congolais - Banza Ilunga, Aimé; Mwansa Kalunga, Jean-Pierre (KAS African Law Study Library, 2018)

Exécution des sentences arbitrales étrangères en République Démocratique du Congo - Kangaseke Mbaka, John; Tshizena Tshinate, Céline (KAS African Law Study Library, 2018)

Pour une justice contractuelle efficace : la médiation OHADA - Kenfack, Hugues (La Lettre, 2018)
Pendant longtemps, la médiation a été le parent pauvre de la justice contractuelle dans le monde. Depuis quelques temps, un vent de faveur souffle sur tous les modes alternatifs de règlement des différends (MARD) parmi lesquels la médiation occupe une place importante.
Keywords: Mediation; Mediação

La renonciation ponctuelle à la mise en œuvre d’une clause compromissoire rend-elle cette dernière manifestement inapplicable dans d’autres contentieux ? - Posocco, Laurent (La Lettre, 2018)

Le litige du travail a-t-il une nature réfractaire à l'arbitrage - Posocco, Laurent (La Lettre, 2018)

Les parties à un arbitrage international sont-elles solidairement tenues de la rémunération due aux membres du tribunal arbitral ? - Posocco, Laurent (La Lettre, 2018)

Médiation de la consommation dans le monde francophone - Thomas, Vincent (La lettre des médiations, 2018)
Le litige de consommation est souvent modeste. Il appelle de ce fait une solution rapide à moindre coût. Sauf exception, l'action en justice ne convient ni au consommateur, ni à l'entreprise, nommée « professionnel » par Code de la consommation. En effet, l'action judiciaire est longue, son résultat échappe à la prévisibilité des parties et les frais induits sont sans commune mesure avec les montants en jeu. Le législateur en a conscience. C'est l'une des raisons pour lesquelles il expérimente depuis quelques années des alternatives à la justice ordinaire. Le juge de proximité a ainsi été créé en 2002 pour les litiges inférieurs à 4 000 €, taux de compétence qui a permis de régler bon nombre de contentieux de la consommation. Malgré son utilité, ce juge spécial n'a pas survécu aux critiques du monde judiciaire et a été supprimé en 2017. Parallèlement, les modes amiables – c'est à-dire par l'accord des parties – de résolution des différends se sont développés. Le Code de procédure civile consacre depuis 2012 un titre complet à la médiation et à la conciliation conventionnelles dont dispositions s'appliquent en dehors de toute procédure judiciaire.
Keywords: Consommation; Mediation; Médiation

Defragmenting Investment disputes: Multilateral Court of Investment Disputes as a Panacea? - Kidane, Brook Bekele (Revue juridique des étudiants de la Sorbonne, 2018)
Never was there a time whereby investment dispute settlement came to the forefront of every possible communication outlet, from academia and mainstream news to civil societies and an outright protest of the public. TTIP and CETA brought ISDS to a broad daylight scrutiny in many parts of Europe getting the attention of law and policy makers at EU and national level. The criticisms and anxiety over ISDS relates to divergent interpretation of similar or identical International Investment Agreements (IIAs) provisions that lead to inconsistency and unpredictability of decisions, lack of transparency in investment disputes, lack of independence and impartiality of arbitrators, the elite group of arbitrators, costs, diversions of public money from public goods and services, ‘chilling effect’ on state regulatory powers and bypassing national judicial systems.; With a view to establish and tackle the problem with a meaningful solution to the legitimate concerns and anxieties, the EU, with its competence to conclude the Investment Agreements, attempted to create two mechanisms. The inclusion of Investment Court System (ICS) in newly concluded IIAs and the creation of a multilateral investment court.; This article will assess the three systems together, i.e. the ISDS, ICS, and the multilateral investment court, in terms the pros and cons and attempt to envisage the policy shortcomings or benefits under any of the systems. Jamais il n'y a eu une époque où le règlement des différends en matière d'investissement a été au premier plan de tous les moyens de communication possibles, qu'il s'agisse d'universitaires, de la presse grand public, de la société civile voire d’actions publiques. La TTIP et la CETA ont permis à l'ISDS de faire l'objet d'un examen minutieux dans de nombreuses parties de l'Europe, attirant l'attention des législateurs et des décideurs politiques au niveau européen et national. Les critiques et l'anxiété à l'égard de l'ISDS ont trait à l'interprétation divergente de dispositions similaires ou identiques des accords internationaux d'investissement (AII) qui conduisent à l'incohérence et à l'imprévisibilité des décisions, au manque de transparence dans les différends en matière d'investissement, au manque d'indépendance et d'impartialité des arbitres, à l'élite des arbitres, aux coûts, aux détournements de fonds publics des biens et services publics, à l'"effet paralysant" sur les pouvoirs réglementaires des États et au contournement des systèmes judiciaires nationaux. En vue d'établir et d'aborder le problème avec une solution significative aux préoccupations et aux inquiétudes légitimes, l'UE, avec sa compétence pour conclure les accords d'investissement, a tenté de créer deux mécanismes. L'inclusion de l'Investment Court System (ICS) dans les AII nouvellement conclus et la création d'un tribunal multilatéral de l'investissement. Cet article évaluera les trois systèmes ensemble, c'est-à-dire le SIPDS, le SCI et le tribunal multilatéral de l'investissement en termes d'avantages et d'inconvénients et tentera d'envisager les lacunes ou les avantages de l'un ou l'autre des systèmes.

Political risk in energy-related investment disputes - Sahin, H. (The World Arbitration and Mediation Review (WAMR), 2018)
The energy industry is a key source of growth stimulation for developing states. This is true not only in terms of economic growth, but also in terms of the transfer of knowledge and skills as well as the provision of employment opportunities. Understandably, developing states are well-disposed towards international investors, and are eager to enter into petroleum investment contracts with the expectation that this will bring the aforementioned benefits to their countries particularly where the host state is less able to act as a provider of such resources autonomously. On a global scale, regardless of their type, all investments face risks. These risks are volatile in nature and reach as the world economy globalises. It is, of course, true that political risk phenomena per se are potentially destructive to all industries. However, it is fair to say that due to its high stakes, the energy industry is more acutely exposed and subject to political risk than most sectors. The purpose of this article is to examine political risk, particularly direct expropriation risk, in long-term energy investment projects. This paper will refer to arbitral decisions with regard to expropriation cases, as well as the valuation techniques applied by the investment arbitration tribunals in unlawful expropriation cases.

International Arbitration Practices in Nigeria: A Construction Industry Appraisal - Ewa, O. O.; Haytham, B.; Okon, E. E.; Enang, O. P.; Emiri, D. A. (World Journal of Innovative Research, 2018)
This paper aims to investigate Corporate Alternative Conflict Management and Dispute Resolution compliance through an appraisal of International Arbitration practices in Project-based Organizations in the Nigerian Construction Industry. In this study, simple percentages and frequencies of occurrence were used to analyse data derived through subject matter interviews and a questionnaire survey. Using the Survey Monkey tool, 85 questionnaires were distributed to key players in the AEC (Architecture-Engineering-Construction) Industry including Engineers, Project Managers, Architects and Quantity Surveyors and 53 were returned complete. The survey indicated that 66% preferred a more private Construction Arbitration to a public Litigation as a preferred method of dispute resolution, with 65% agreeing that a lack of proper project funding hinders the arbitration process in the Nigerian Construction Industry. 66% agree that Arbitration Time contributes more to project delays while 32% believe that Cost of the arbitration process is the greater source of project delays. We recommend that issues of confidentiality be carefully managed in dealing with outside counsels, while Project-based Organisations in Nigeria should ensure to develop master plans compatible with long-term strategies, including setting aside adequate funding for the timely resolution of project disputes through the implementation of only Arbitration-friendly contracts. This paper contributes to knowledge by bringing to bear the current compliance levels of project-based organisations in the practice of Arbitration in the Nigerian Construction Industry.

Who is in? Who is out? How the Uncitral Transparency Rules Can Influence the Upcoming Amendments of the ICSID Arbitration Rules - Yu, Hong-Lin (Contemporary Asia Arbitration Journal, 2018)
The International Center for Settlement of Investment Disputes (hereinafter "ICSID") has started its fourth amendment of its Arbitration Rules since 2016. The issue of transparency has been highlighted as a delicate issue in ICSID ongoing current amendment. It is also listed in the topics that have been identified for potential amendment. This article analyses how the issues of access to hearings and confidentiality over information arising from arbitration is treated under the current framework. A comparison is made against the Transparency Rules. The analysis is also made against the comments received from the public whose views are analysed as a possible direction the amendment may take.

L’arbitrage international dans l'OHADA : évolution vers l’arbitrage des investissements en Afrique - Dalil, Mustapha (Journal of Strategic Affairs, 2018)
En vertu des dispositions de l’article 53 Al. 1 du Traité de création de l’OHADA (l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires) : « Le présent traité est, dès son entrée en vigueur, ouvert à l’adhésion de tout Etat membre de l’Union Africaine et non signataire du traité. Il est également ouvert à l’adhésion de tout autre Etat non membre de l’Union Africaine invité à y adhérer du commun accord de tous les Etats Parties ». Cette action d’harmonisation du droit des affaires, tout en s’inspirant d’autres législations telles que le droit français et la common law, les Etats-membres de l’OHADA ont à leur disposition un arsenal législatif efficace et approprié à leur développement économique communautaire. Ce droit revêt un intérêt particulier pour les entreprises marocaines actives dans l’espace OHADA. Le Maroc, par le renouvellement de son adhésion à l’Union Africaine (UA) et en procédant à une demande d’adhésion à la Communauté Economique des Etats de l’Afrique de l’Ouest (CEDEAO) dont le but est de « promouvoir la coopération et l’intégration dans la perspective d’une Union économique de l’Afrique de l’Ouest », (le Maroc) a réaffirmé sa détermination d’intégrer les espaces économiques africains de référence
Keywords: Arbitrage international; Droit des affaires; Développement économique; Relations internationales; Union africaine; الاتحاد الإفريقي; التحكيم الدولي; التنمية الاقتصادية; العلاقات الدولية; قانون الأعمال

Médiation des relations de travail dans le monde francophone - Housty, Françoise (La lettre des médiations, 2018)
La médiation pour déminer les conflits au travail » : c’est ainsi que fut annoncée une grande vague de réforme judiciaire et des institutions du travail en France par les lois Macron dès 2016, afin d’introduire de la « médiation » dans le monde du travail1. L’objectif déclaré est de développer le dialogue au sein de l’entreprise et de prévenir le recours à une justice lente parce que engorgée.
Keywords: Mediation; Médiation; Relation de travail

L’arbitrage comme mode alternatif de règlement des litiges en RDC : cas de l’arbitre du CENACO - Kapinga K. Nkashama, Symphorien (KAS African Law Study Library, 2018)
Cette étude s’intéresse à l’arbitrage comme mode alternatif de règlement des litiges en RDC. L’auteur y analyse les règles juridiques qui s’appliquent à la compétence et à la sai- sine du Tribunal arbitral, au mode de désignation des arbitres qui le composent et à la pro- cédure arbitrale à suivre. Il étudie aussi la sentence arbitrale ainsi que les voies de recours offertes aux parties, avec un coup d’œil particulier sur l’arbitrage organisé par le centre Na- tional d’Arbitrage, de Conciliation et de médiation de la Fédération des Entreprises du Congo et en comparaison avec la procédure usitée devant les juridictions civiles étatiques
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitre; MARD; MARL; RDC

Les efforts de la CNUDCI pour accroitre le niveau de transparence dans l’arbitrage d’investissement - Belhadj, Miriana (Revue de l'ERSUMA, 2018)
Récemment, la Commission des Nations Unies pour le Droit commercial international (CNUDCI) a adopté deux instruments sur la transparence dans l’arbitrage entre investisseurs et États fondé sur des traités. Un Règlement adopté en 2013, prévoit des règles spécifiques pour compléter tout règlement d’arbitrage choisi pour régir un arbitrage conduit sur la base d’un traité d’investissement. Ces règles prévoient notamment, et sous certaines conditions, la publication d’informations et de documents relatifs à l’affaire. Elles permettent aussi que des observations soient présentées par les tiers ou par une partie au traité non partie au litige. Une Convention adoptée en 2014 met en place un mécanisme efficace permettant aux États de prévoir l’application du Règlement sur la transparence à leurs traités d’investissement antérieurs à l’entrée en vigueur du Règlement. À la date de cet article, la Convention compte cinq États parties, dont deux États africains (18 autres États, dont 3 États africains, l’ont signée) et est entrée en vigueur le 18 octobre 2017. Ces efforts de promotion de la transparence dans l’arbitrage d’investissement ont été suivis de discussions au sein de la CNUDCI aboutissant à ce qu’un nouveau groupe de travail au sein de la CNUDCI soit chargé de réfléchir à une possible réforme du système de règlement des différends entre investisseurs et États (RDIE). Dans le cadre de ces réflexions politiques et techniques de haut niveau, la question de la place de la transparence – autre que la transparence procédurale – est récurrente à plusieurs égards et inévitablement au cœur des débats.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; CNUDCI; Investissements; Investments; Transparence; Transparency

An Empirical Study of Dispute Resolution Clauses in International Supply Contracts - Coyle, John F.; Drahozal, Christopher R. (Vanderbilt Journal of Transnational Law, 2018)
International transactions present unique legal risks. When a contract touches several different nations, a party may not know where it will be called upon to defend a lawsuit or, alternatively, which nation’s law will be applied to resolve that dispute. To mitigate these risks, parties will often write dispute resolution provisions into their contracts. Arbitration clauses and forum selection clauses help to reduce uncertainty relating to the forum. Choice-of-law clauses help to reduce uncertainty as to the governing law. Over the past few decades, such provisions have become commonplace in international contracting. And yet there exist vanishingly few empirical studies exploring the use of these provisions in international commercial agreements.

Kroniek Internationale Arbitrage - De Ly, Filip (Tijdschrift voor Arbitrage, 2018)

L’arbitrage comme mode de règlement des différends dans les codes d’investissements des Etats membres de l’UEMOA - Djigle, Doundongue (Revue de Recherches en Economie et en Management Africain, 2018)
Dans le but d’attirer les investissements directs étrangers, les Etats membres de l’UEMOA ont adopté des codes d’investissements destinés à régir les relations entre investisseurs et Etats. Ces codes privilégient l’arbitrage comme mode de règlement des différends. Mais le fondement de cet arbitrage n’est pas le même dans chacun des codes. Certains codes comportent directement dans leur corpus la clause d’arbitrage que l’investisseur peut activer en cas de survenance d’un litige, tandis que d’autres renvoient à des sources extérieures, tel un contrat d’investissement ou un traité bilatéral d’investissement liant l’Etat d’accueil avec l’Etat d’origine de l’investisseur. En outre, dans leur pratique, les Etats de l’UEMOA donnent souvent le choix aux investisseurs entre différentes instances arbitrales. Pourtant, peu de procédures d’arbitrage sont engagées contre ces Etats sur le fondement des codes nationaux d’investissement.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Code des investissements; Etats membres.; Investissements; Investments; Offre d’arbitrage; UEMOA

Arbitration cost : a short comparative view of the schedule of fees of arbitration centers within the OHADA zone - Dogué, Karel Osiris Coffi (Revue de l'ERSUMA, 2018)
Amongst the seventeen OHADA member states there are over fourteen arbitration centers or institutions that handle disputes arising from contractual agreement without going through the courts of the state. The arbitration cost within the various arbitral centers differs from one arbitration center to another. The schedule or method for calculating fees are regulated by the rules of the various arbitration centers or by the OHADA Uniform Act Arbitration Rules pertaining to arbitration fees annexed to the rules of arbitration for the Common Court of Justice and Arbitration and for arbitration centers without arbitration rules. This contribution describes and contrast the various schedule of fees applicable with the arbitration centers under the OHADA zone in particular and also makes a comparative view of the arbitration fees out of the OHADA zone.
Keywords: Arbitragem; Arbitraje; Arbitration; Arbitration cost; Arbitration fee; Arbitration proceedings; Coût de l’arbitrage; Frais d’arbitrage; OHADA Arbitration's Center; Procédure arbitrale

Les MARD (modes alternatifs de résolution des différends) au prisme des droits fondamentaux substantiels - Dumas, Romain (Revue des droits et libertés fondamentaux, 2018)
La loi pour la justice du XXIème siècle a renforcé le recours aux MARD (modes alternatifs de résolution des différends) en incitant, voire en obligeant les parties à les utiliser pour tenter d’aplanir un nombre croissant de différends. Si la prise en compte des droits fondamentaux processuels par les MARD ne fait plus guère de doute, la question se pose néanmoins de savoir quel niveau de garantie ces processus accordent aux droit fondamentaux substantiels des parties qui les mobilisent.
Keywords: Arbitrage; Liberté contractuelle; Liberté d'expression; Médiation; Vie privée

Les fondements de la circulation de la convention d’arbitrage - Faye, Ousmane (Revue de l'ERSUMA, 2018)
« Il n’y a pas de contrat sans consentement des parties ». Tel est formulé le principe sacro-saint du consensualisme contractuel. Toutefois cette règle générale reconnue par tous les systèmes juridiques d’obédience romano-germanique ne finit pas de montrer des réserves. Ces exceptions se retrouvent dans tous les types de contrats même dans ceux qui portent sur le règlement alternatif des litiges. C’est cette dernière situation que traduit la problématique de l’application du contrat d’arbitrage à des tiers non-signataires, encore connu sous le terme de la circulation du contrat d’arbitrage. En principe la théorie de la relativité des conventions impose que l’engagement soit source d’obligations pour son auteur, mais pas pour les tiers auxquels l’acte ne peut ni profiter ni nuire. Malgré cette restriction, la jurisprudence et la doctrine restent largement favorables à la circulation de la convention d’arbitrage. Les fondements avancés pour justifier cet élargissement du contrat d’arbitrage à des tiers non-signataires sont assez divers. Certains sont tirés du droit des obligations notamment de la théorie de la représentation et des groupes de contrat. D’autres ont pour fondement le droit des sociétés, particulièrement la théorie des groupes de sociétés et celle de la levée du voile social ou l’alter ego.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Contrat d'arbitrage; Convention d'arbitrage; Corporate law; Droit des sociétés

La preuve dans la médiation commerciale - Kpako, Valentin V. V. (Revue de l'ERSUMA, 2018)
En considération de ce que la médiation commerciale entendue comme un processus par lequel des personnes physiques ou morales, demandent à un tiers de les aider à parvenir à un règlement amiable d’un différend découlant d’un rapport juridique, contractuel ou autre ou lié à un tel rapport, il est aisé de percevoir qu’il s’agit d’un mode de résolution non judiciaire de litige. A la différence du règlement judiciaire des conflits, la médiation commerciale tend à solutionner les points d’oppositions entre les parties, et à maintenir et soigner leurs relations d’affaires. Elle s’oppose à l’arbitrage qui tranche le litige par une sentence, qui s’impose aux parties, qu’elles la veuillent ou non. Elle ne génère donc pas de perdant, mais les deux parties doivent avoir fait des concessions, et gagner en temps. De ce fait, l’on est tenté d’affirmer que la médiation commerciale pourrait se passer de l’exploitation des moyens de preuve. D’ailleurs, l’Acte uniforme de l’OHADA relatif à la médiation ne fait aucune mention du principe de preuve dans la conduite de la médiation commerciale pas plus que l’ensemble des textes qui organisent la matière. L’on se pose même a question de l’opportunité d’avoir à prouver les faits dans une telle discipline si tant est que toutes les parties en sortent gagnantes. Mais à y voir de près, la médiation commerciale ne semble pas totalement exclure le système de la preuve tel que pratiqué dans la procédure judiciaire de résolution des conflits. Au contraire, elle en a fortement besoin pour à la fois justifier le fondement des prétentions des parties ainsi que la solution au litige. Précisément, la preuve dans la médiation commerciale participe à la détermination des points à discuter et à la justification tant des propositions formulées par le médiateur que des concessions à faire par les parties.
Keywords: Espace OHADA; MARD; Mediation; Médiation; Médiation commerciale; Procédure de médiation

L'arbitrage international et la place réservée à l’ordre public dans les pays du golfe persique - Mazidi, Sépideh (Revue de l'ERSUMA, 2018)
La notion de l’ordre public est l’un des concepts les plus complexes des systèmes juridiques. Dans les pays arabo-musulmans la difficulté est encore plus grande, car cette notion se rapproche de celle de la Chari’a. En effet, l’ordre public des pays de la région du golfe trouve sa légitimité dans l’Islam et dans les Constitutions de ces pays. Les Constitutions du Koweït, Bahreïn, Qatar et les Émirats Arabes Unis considèrent la Chari’a comme la source principale de la législation. A l’échelle internationale, la présence indirecte de la Chari’a se manifeste à travers l’arbitrage international, mode efficace et rapide de résolution des conflits du commerce international. Dans la procédure arbitrale, la Chari’a peut intervenir à tous les niveaux : elle peut jouer un rôle fondamental pour la conclusion de la convention d’arbitrage, le choix de la loi applicable ainsi que pour l’exécution et les recours contre la sentence. Dans le cadre de notre étude, nous étudions le choix de la loi applicable et la phase exequatur. Cependant le stade de la conclusion de la convention d’arbitrage est en dehors des limites de ce travail.
Keywords: Arbitrage international; Arbitration; Charia; International arbitration; Islam; Légitimité; Région du golfe

Vers des partenariats inter-états africains, gages d’équité en faveur des investissements économiques en Afrique - Nguemdom, Ruth Carelle (Revue de l'ERSUMA, 2018)
Est-il essentiel de créer de véritables et solides couloirs juridiques entre les régions et les Etats africains pour encourager les investissements économiques ? La question mérite d’être posée. Un tel partenariat implique que soit mise en place une stratégie commune autour des investissements économiques. Il va ainsi permettre de créer une dynamique industrielle et commerciale encore plus forte que celle observée aujourd’hui au sein de l’OHADA. L’UA ou l’OHADA doivent être dotées de moyens réels car l’union fera la force pour les africains trop faibles pour agir et compter seuls face aux puissances étrangères (l’UE, la Chine, l’Inde, la Russie, les USA…). Pour ces Etats, l’Union serait la négociatrice privilégiée pour de nouveaux partenariats plus équitables. Avec cette stratégie de coopération rentable, les Etats africains pourront parler d’une même voix et passer du statut de « perfusés » à celui de « partenaires ». Si ce vœu pieux semble loin de portée, il est malheureusement une des clés de la réussite africaine en matière de développement économique et social, de croissance durable par le biais des investissements économiques. Ceci au même titre que l’intégration régionale car, comme le rappelle si bien la CEA, l’approfondissement de l’intégration régionale permettra d’améliorer de façon significative l’attractivité du continent africain comme destination pour les investissements économiques.
Keywords: Afrique; Coopération Sud-Sud; Investissements; Investments; Partenariat inter-Etats

Vers la contractualisation de la justice : Cas de la médiation en droit OHADA - Ntumba Musuka, Zacharie-Richard (Annales de la Faculté de Droit, 2018)

La justice étatique à l’épreuve de l’avancée des modes alternatifs de règlement des différends en droit OHADA - Soumaïla, Sounon Tamou Abdou (Revue de l'ERSUMA, 2018)
La « raison d’être » de l’OHADA est de faciliter l’activité des entreprises et garantir la sécurité juridique et judiciaire des activités économiques. A cette fin, la justice ou « la juridiction compétente dans l’Etat Partie » selon les termes du législateur de l’OHADA, est d’une grande contribution. Mais, en marge de cette justice, on voit se développer remarquablement les Modes Alternatifs de Règlements des Différends (MARD) en Droit OHADA. Le législateur est parti de l’arbitrage pour en arriver aujourd’hui à la médiation, sans oublier la conciliation. Le souci du législateur est sans doute d’assurer la célérité dans le traitement des conflits, garantie que n’offre pas toujours la justice étatique. Que devient alors le juge étatique au milieu de ces «nouveaux» modes de règlement des différends dans le droit OHADA ? La réponse à cette interrogation est apportée en considération des deux Actes uniformes récemment adoptés (le 23 novembre 2017 à Conakry) par le Conseil des Ministres de l’OHADA sur la Médiation et l’Arbitrage. Dans l’un ou l’autre de ces textes, le juge n’est pas traité de la même manière, conséquence de la nature de chaque procédure. La nature contractuelle de l’accord de médiation s’impose au juge tandis que la sentence arbitrale doit faire l’objet de reconnaissance et d’exequatur. En conséquence, le juge qui semble s’effacer lors du déroulement des procédures d’arbitrage et de médiation, réapparaît à l’occasion de l’exécution des décisions qui en résultent, mais là encore, son intervention est nuancée. Dans l’exécution de la sentence arbitrale elle est obligatoire et exclusive ; dans la mise en œuvre de l’accord de médiation elle est facultative. Au final, l’on peut souhaiter que le législateur fasse interagir les différentes procédures de règlement des différends en droit OHADA.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Conciliation; Droit OHADA; MARD; Mediation; Médiation; Règlement des conflits

Quelle médiation dans l’espace OHADA sans professionnalisation des médiateurs ? Les inspirations du contexte belge - Tadjudje, Willy (Revue de l'ERSUMA, 2018)
Le 23 novembre 2017, le dixième Acte uniforme de l’OHADA sur la médiation a été adopté au cours de la 45e session du Conseil des Ministres tenue à Conakry (Guinée). Selon le communiqué final de ladite session, cet Acte uniforme a pour objectif « de combler le vide législatif existant en la matière dans la plupart des Etats membres de l’OHADA et promouvoir ce procédé amiable de règlement des différends ». Le but de cette réflexion est de jeter un regard critique sur ce texte dans une approche comparative avec le contexte belge. L’analyse sera focalisée sur la question de la professionnalisation des médiateurs. En Belgique, la médiation est une « profession réglementée », alors que dans l’espace OHADA, l’accès à la médiation semble libre, ce qui peut laisser des doutes sur la crédibilité de cet outil de règlement amiable des litiges.
Keywords: Belgique; Espace OHADA; Mediation; Médiateur; Médiation; Médiation et négociation; Procédure de médiation; Professionnalisation

Without Silence, There Is No Golden Rule; Without Dissent, There Is No Progress - Uluc, Inan; Sutton, Kristi R. (Oregon Review of International Law, 2018)
The frequency of dissenting opinions accompanying arbitration awards in international arbitration has multiplied, particularly in international investment arbitration. Accordingly, dissenting opinions are now inevitable companions to majority awards. Notwithstanding the fact that dissenting opinions neither form part of an arbitral award nor constitute a separate award, the escalation of dissenting opinions spawns anxiety in scholars and practitioners. This trepidation ignited a crusade whereby those opposed to the practice of rendering dissent challenge the role and usefulness of these opinions. In this respect, this Article initially considers and critiques specific arguments raised by those opposed to dissenting opinions in international arbitration. Following analysis of the criticisms, this Article explores the beneficial and constructive aspects of dissenting opinions. Evident from this discussion is that dissenting opinions are not only integral to supplement an arbitrator’s quasi-judicial capacity, but also encourage issuance of well-reasoned awards. Clear from the benefits of dissenting opinions in international arbitration, any departure from the present clemency espoused toward the practice will eventuate in the field’s regression.
Keywords: Civil law; Common law; International arbitration

The Impartiality and Independence of Arbitrators and Its Implication on the Validity of Arbitral Awards - Yoga, I. Ketut Dharma Putra (Juris Gentium Law Review, 2018)
Arbitration is a way to resolve disputes outside the courts as a form of an alternative dispute resolution. The submitted dispute will be decided by one or more arbitrators, who will then render an arbitral award. One of the most fundamental principles of arbitration that must be adhered to by all arbitrators worldwide is the impartiality and independence of arbitrators, which have been regulated in various International laws. Arbitrators are not allowed to communicate with any party related to the case they are hearing. Further, arbitrators should not be influenced by others in making their decision and drafting the arbitral award to ensure objectivity and prevent any bias. An arbitrator's failure to act impartial and independent can lead to the invalidity or annulment of an arbitral award.

O.E.C.D. promotion for arbitration as an additional tool of settling disputes in the field of international taxation - Zeyen, Gaëtan (Revue de l'ERSUMA, 2018)
In a globalized world, arbitration plays an increasing role in settling international disputes. Almost all areas of Law are or might be concerned. Until very recently, [international] taxation was - as a rule - seen as a not ‘arbitrable-friendly’ matter. As the ‘classical’ method of settling international tax disputes - i.e., based on the so-called ‘Mutual Agreement Procedure’ (shortly, ‘M.A.P.’) - has shown its limits (mainly: lack of efficiency and involvement from the taxpayers themselves), arbitration became a subject of study for well-known and established academics and even an appropriate method of settling such international tax issues. As a result, both on international (O.E.C.D.) and European levels, legal initiatives have been taken, in order to promote arbitration as an additional tool of settling disputes in the field of international taxation. The purpose of the present article is, therefore, to describe and scrutinize these [very] recent legal initiatives and raise some potential issues that, at least in the author’s view, need to be addressed. One of these issues concerns the enforcement of such arbitral decisions.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration proceedings; Dispute settlement; International taxation; O.E.C.D; OCDE

La pratique de l'arbitrage OHADA selon le règlement d'arbitrage CCJA - Bebohi Ebongo, Sylvie (Revue juridique de l'Océan Indien, 2017)
L’arbitrage OHADA repose sur un régime dual. Le régime dual de l’arbitrage OHADA est constitué, d’une part, par l’arbitrage de droit commun régi par l’acte uniforme OHADA relatif au droit de l’arbitrage qui réglemente l’arbitrage de droit commun dans l’espace OHADA et, d’autre part, par l’arbitrage spécifique CCJA qui repose sur le titre IV du Traité OHADA et le règlement d’arbitrage de la Cour commune de justice et d’arbitrage. Qu’est-ce qui caractérise dès lors l’arbitrage OHADA selon le règlement d’arbitrage CCJA et le distingue de l’arbitrage de droit commun de l’acte uniforme OHADA relatif au droit de l’arbitrage ? Comment fonctionne l’arbitrage selon le règlement d’arbitrage CCJA ? Pour mieux comprendre comment se pratique l’arbitrage OHADA selon le règlement d’arbitrage CCJA, il est nécessaire d’appréhender ses spécificités tant dans sa mise œuvre (I) qu’en matière d’exécution des sentences arbitrales qui en sont issues (II).
Keywords: Arbitrage; Arbitragem; Arbitration; Clause compromissoire; Compromis d'arbitrage; Convention d'arbitrage; Espace OHADA; Exequatur; Exécution; Investissements; Organisation pour l'harmonisation en Afrique du droit des affaires (OHADA); Promotion; Protection; Règlement d'arbitrage; Sentence arbitrale; TBI; Traités Bilatéraux; lois nationales

Le règlement par voie d'arbitrage des litiges relatif aux investissements dans l'espace OHADA - Kenfack Douajni, Gaston (Revue juridique de l'Océan Indien, 2017)
Keywords: Arbitrage; Arbitragem; Arbitration; Clause compromissoire; Commission des Nations Unies pour le droit commercial international (CNUDCI); Contrat; Convention d'arbitrage; Exequatur; Investissements; Investments; Jurisprudence arbitrale; Loi nationale; Organisation pour l'harmonisation en Afrique du droit des affaires (OHADA); Règlement des litiges; Sentence arbitrale; Traité de protection des investissements

Les ambigüités de la voie de cassation en matière de droit pénal des Actes uniformes, (A propos de l'arrêt de la CCJA n°143/2016, du 14 juil. 2016 Ibrahima Aboukhalil c/Etat du Sénégal et le ministère public et a) - Lekebe Omouali, Daphtone (Revue de l'ERSUMA, 2017)
L'interprétation des Actes uniformes est un défi pour son application. L'harmonisation des règles de droit des affaires dans l'espace OHADA s'est accompagné d'un objectif d'unification de la jurisprudence et la Cour Commune de Justice et d'Arbitrage joue à cet égard un rôle essentiel. L'articulation des compétences judiciaires entre la CCJA et les juridictions nationales statuant en cassation offre cependant, en matière pénale des Actes uniformes, l'image d'une option pathologique. Alors que la CCJA proclame la compétence exclusive des cours suprêmes nationales en cas d'application des sanctions pénales, la nécessité d'assurer une répression uniforme en cas de violation du droit uniforme milite en faveur d'un partage de compétence entre celle-ci et celles-là.
Keywords: Droit de l'arbitrage; Droit pénal des affaires

L’arbitrage en cinq idées reçues - Couturier, Jean-Pascal (La Lettre, 2017)
Les pouvoirs publics n’ont de cesse de vouloir orienter les justiciables (entreprises comme particuliers) vers des modes alternatifs de règlement des différends (MARD). L’arbitrage est le plus ancien d’entre eux ; le grand public l’a (malheureusement) découvert à travers les nombreux rebondissements de l’affaire Bernard TAPIE / CREDIT LYONNAIS.

Regards croisés sur l’arbitrage et sa perception par l’usager - De La Chapelle, Antoine; Heraud, Cindy (La Lettre, 2017)
L’affaire dite « Tapie », résolue par une sentence arbitrale en date du 7 juillet 2008, a placé l’arbitrage sous le feu des projecteurs médiatiques et a fait couler beaucoup d’encre, alimentée par un certain nombre de représentations erronées et de préjugés vis-à-vis de la justice arbitrale. D’aucuns ont ainsi dénoncé une justice arbitraire, au service d’intérêts privés et au fonctionnement opaque, invitant à une défiance généralisée.

La médiation interentreprises dans le monde francophone - Henry, Sophie (La lettre des médiations, 2017)
Concurrence déloyale, inexécution contractuelle, rupture brutale, conflit entre associés… Autant d’exemples de litiges qu’une entreprise peut être amenée à connaître au cours de son existence. La longueur et le coût des procédures, l’aléa et le carcan d’une décision de justice obligent les entreprises à repenser leur politique de gestion des conflits, Leurs contraintes économiques favorisent progressivement les modes amiables de règlement. Elles optent de plus en plus pour la médiation, dans une perspective d’efficacité, d’optimisation des coûts et délais et de maîtrise de leur image. Dans une étude réalisée en 2016 par le CMAP (Centre de Médiation et d’Arbitrage Paris) en partenariat avec Squaremic et Baro Alto, il apparait que 90% des entreprises interrogées ont eu recours à la médiation au moins une fois sur les douze derniers mois et 77% d’entre elles jugent ce mode de résolution efficace.
Keywords: Gestion de conflits; Mediation; Médiation

Les provisions pour arbitrage face à l’impécuniosité d’une partie - Posocco, Laurent (La Lettre, 2017)

Rejet de l’annulation de la sentence rendue par un arbitre ayant divulgué une hypothétique cause de partialité - Posocco, Laurent (La Lettre, 2017)

Dispute resolution in the oil and gas industry: an appraisal of mediation and litigation procedures. - Mohammed, Jamilu Ibn (Journal of private and business law, 2017)
The Oil and Gas Industry Resolution originally recognised negotiation and concede to the alternative dispute resolution rather, their litigation. The paper analysed appraised the different alternative dispute resolution, formulae including mediation the doctrinal method of research which analyses all legal in others as applied. All methods relating to the dispute resolution were analysed from the library and it has formed that mediation which involves the process of resolution dispute weather the involvement of litigating is prefer for being use costly and time consuming. Litigation been so expensive and time wasting is not recommence for oil and Gas Industry.
Keywords: Dispute Resolution; Gas; Industry; Litigation; MARD; Mediación; Mediation; Mediação; Médiation; Oil

Arbitrage et éthique : causes du mal, évolution récente et pistes d’amélioration – Regards sur le monde et sur l’océan Indien - Anilha, Fernande; Magamootoo, Julien (Revue juridique de l'Océan Indien, 2017)

Suggestions pour promouvoir la place de l’arbitrage en Afrique. Madagascar et la Tunisie comme illustration - Ben Hamida, Walid (Revue juridique de l'Océan Indien, 2017)

Alternative Dispute Resolution (ADR) and access to justice: An introduction - Betancourt, J. (Arbitration, 2017)
Text of a talk given by the author at the University of West London on 8 March 2016 on the topic of Alternative Dispute Resolution, its relation to the concept of access to justice and the idea of practising law in the interest of justice.

Juge judiciaire, acteur de l'essor de l'arbitrage : cas français, malgache et mauricien - Chuk Hen Su, Lalaina (Revue juridique de l'Océan Indien, 2017)

La déontologie de l’arbitre - Dupeyré, Romain (Revue juridique de l'Océan Indien, 2017)

Analyse comparative entre Maurice et Madagascar sur les spécificités liées à l’arbitrage international et à l’arbitrage institutionnel - Gunnoo, Dipna (Revue juridique de l'Océan Indien, 2017)
Les lois mauricienne et malgache relatives à l’arbitrage international s’inspirent toutes deux de la Loi type de la CNUDCI. En dépit de cette source d’inspiration commune, ces deux pays présentent plusieurs aspects divergents. Ces divergences, liées à l’arbitrage international, se retrouvent, non seulement, au sein des caractéristiques législatives et juridictionnelles de chacun de ces États, mais également au sein des caractéristiques des institutions arbitrales promues par ces deux pays. International arbitration laws in Mauritius and Madagascar are both largely inspired by the UNCITRAL Model Law. Despite this similar source of law, these countries have various differing aspects. In the field of international arbitration, discrepancies between these two States can be found, on one hand, in the legislative and jurisdictional features and, on the other hand, in the features of arbitration institutions showcased by these two countries.

Arbitrage et sécurisation juridique des investissements : l'arbitrage comme moyen de sécurisation des investissements à Madagascar - Jakoba, Raphaël (Revue juridique de l'Océan Indien, 2017)
Madagascar s’est doté d’un arsenal juridique cohérent et attractif relatif aux investissements. La panoplie de mesures est étoffée allant d’une loi spécifique sur les investissements (loi 2007-036 sur les investissements à Madagascar), à un cadre institutionnel tel que l’EDBM, et enfin des engagements internationaux (adhésion à la convention de Washington de 1965, ratification de plusieurs APPI (Accords pour la promotion et la protection réciproques des investissements) avec la France, le Benelux... À la lumière de cet arsenal en faveur des investissements, il est permis de dire que l’arbitrage, mode de règlement des différends pour les investissements, est placé au cœur d’une politique d’attraction et de sécurisation des investissements. Toutefois, la pratique malgache de l’arbitrage international tant commercial qu’en investissement révèle un certain nombre de dysfonctionnements et de défaillances qui impactent sur l’environnement des affaires. Madagascar has developed a coherent and attractive legal arsenal for investment. The range of measures was refined ranging from a specific investment law (Law 2007-036 on investments in Madagascar) to an institutional framework such as the EDBM, and international commitments (accession to the Washington convention of 1965, Ratification of several APPI [Agreements for the Promotion and reciprocal Protection of Investments] with France, the Benelux...). In the light of this arsenal in favor of investments, it can be said that arbitration, the method of settlement of Investment Disputes, is at the center of a policy of attracting and securing investments. However, the malagasy practice of international arbitration, either for commercial or investment arbitration reveals a number of dysfunctions and failures, impacting significantly the investment climate.

Le règlement par voie d'arbitrage des litiges relatifs aux investissements dans l'espace OHADA - Kenfack Douajni, Gaston (Revue juridique de l'Océan Indien, 2017)

International Arbitration - Liatowitsch, Manuel; Rosenthal, Jeffrey; Forneret, Martine; Scherker, Emily; Ashford, Peter; Janzik, Sabrina; Weldon, Matthew; Houston, Robert; Boog, Christopher; Gottlieb, Benjamin; Meijer, Gerard; Verberne, Valerie; et al. (The Year in Review, 2017)
Keywords: Arbitration; Dispute resolution; International Law

L'arbitrage et la lutte contre la corruption - Ligneul, Nicolas (Revue juridique de l'Océan Indien, 2017)

Primera ejecución en España de un laudo OHADA ¿Por qué tiene un juez español que forzar su cumplimiento? - Linares Rodríguez, Enrique (Arbitraje: revista de arbitraje comercial y de inversiones, 2017)
El Convenio de Nueva York de 1958 permite se busque el reconocimiento y la ejecución de un laudo OHADA en terceros Estados. Sin embargo, admite el empleo de la normativa interna para regir el procedimiento y deja a salvo cuestiones relacionadas con la inmunidad soberana de los Estados. Las nuevas leyes adoptadas en España en materia de cooperación jurídica internacional e inmunidad soberana, establecen la intervención del MAEC cuando un Estado extranjero sea demandado ante tribunales españoles como es el caso Commercial Bank / Guinea Ecuatorial. Esta previsión puede implicar un giro de la jurisprudencia hacia posturas más cercanas a la inmunidad absoluta. Como se verá en este artículo, aunque CBGE haya obtenido el execuátur del laudo en España y logrado el embargo del avión titularidad de Ceiba, las medidas coercitivas de ejecución podrán ser recurridas en revisión por el Estado, quien podrá plantear una estrategia fundamentalmente en dos direcciones: (i) bien demostrando la finalidad soberana del aparato embargado, para defender así su carácter inmune a la ejecución, o (ii) bien alegando que la persona jurídica afectada por el embargo no ha sido parte en el arbitraje y por tanto no es la deudora del laudo. La práctica jurisprudencial internacional ha demostrado que existen gran des posibilidades de que el tribunal termine levantando el embargo si se demuestra fehacientemente alguna de estas dos defensas.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Ejecución; Embargo; Guinea Ecuatorial; Inmunidad; Laudo arbitral

L'arbitrage de droit commun régi par l'Acte uniforme relatif à l'arbitrage - Ngwe, Marie-Andrée (Revue juridique de l'Océan Indien, 2017)
L’arbitrage de droit commun est régi par l’Acte uniforme relatif à l’arbitrage, véritable loi de procédure harmonisée applicable dans les 17 États membres de l’OHADA. Aux côtés de l’arbitrage CCJA dont il est complémentaire, il a sa légitimité et sa vocation propre qui est de permettre le développement d’un arbitrage de proximité. Conforme aux standards internationaux, qu’il soit ad hoc ou institutionnel, il met au cœur du processus les parties, afin de créer une véritable culture locale de l’arbitrage. À ce titre, il donne un rôle essentiel aux institutions nationales d’arbitrage dont la connaissance de terrain et la proximité des acteurs permettent l’enrichissement de la lex arbitri, jusqu’à permettre aujourd’hui d’inspirer une réforme de cette loi uniforme de l’arbitrage OHADA qui tend vers toujours plus d’efficacité et de modernité. Il nous sera donné en particulier de faire part de l’expérience du Centre d’arbitrage du GICAM, Douala (Cameroun). The Uniform Act on arbitration is the ordinary law that governs arbitration. This Uniform Act is a harmonized procedural enactment that is applicable in the 17 member states of OHADA. It exists alongside, and is complementary to CCJA arbitration. But it has its own legitimacy and its own vocation, which is to allow the development of an arbitration of proximity. Whether considered from an ad hoc arbitration viewpoint, or an institutional arbitration viewpoint, the Uniform Act complies with international arbitration standards. It places the parties at the heart of the arbitral procedure in order to create a local culture of arbitration. In this regard, it provides an important role to national arbitration institutions whose understanding of the field and proximity to stakeholders permit the enrichment of the lex arbitri. Today, this role given to national arbitration institutions has inspired a reform of the Uniform Act on arbitration, which aspires for more efficiency and modernity. We shall, in particular, share the experience of the GICAM Arbitration Centre in Douala Cameroon.

Document Production and Disclosure in Investor-State Arbitration - Oepangat, Dioputra Ilham; Janet, Janet (Juris Gentium Law Review, 2017)
It is not uncommon for states to engage in arbitration proceedings with their investors (“Investor-State Arbitration” or “International Investment Arbitration”) administered under the International Centre for the Settlement of Investment Disputes. When these parties engage in document production during evidentiary proceedings, there arises an issue with regards to documents requested by the investor, which is considered as a “state secret” by the state. Based on the IBA Rules on the Taking of Evidence in International Arbitration (“IBA Rules”), states may have particular interest to refuse the production of a document. This is based on the argument that a document may be exempted from production if the document qualifies as a state secret by virtue of Article 9 of the IBA Rules. This paper will discuss appropriate measures to be taken by tribunals in order to allow for material and relevant evidence to be produced during proceedings, which may be crucial in being able to prove the case of the investor in the case of a conflict pertaining to the production of documents containing state secrets.
Keywords: Arbitrage; Arbitragem; Arbitration; Disclose; Document; IBA; ICSID; International; Investments; Prove; Secrets; Sensitive

La Charte confiance du Centre d’arbitrage et de médiation de Madagascar (CAMM) - Ramangaharivony, Gérard (Revue juridique de l'Océan Indien, 2017)
Les litiges font partie intégrante du monde des affaires. Les gérer efficacement constitue un défi majeur pour le maintien de la paix sociale et l’accroissement du business. Dans sa mission de sensibilisation aux Marl, le Centre d’arbitrage et de médiation de Madagascar (CAMM) a élaboré et proposé une Charte confiance de règlement des litiges. Cette Charte a pour objectif la continuité des affaires, le respect de la loi et un marché sain et prospère.

L'Etat dans l'arbitrage d'investissement - Ranjeva, Hery Frédéric (Revue juridique de l'Océan Indien, 2017)

Règlement alternatif des litiges commerciaux et économiques dans la zone francophone - Ravaloson, Johary (Revue juridique de l'Océan Indien, 2017)

Can third party funding deliver justice in international commercial arbitration? - Yu, Hong-Lin (International Arbitration Law Review, 2017)
Third party funding arrives at international commercial arbitration without clear guidelines. The recognition and acceptance of its legality is hampered by the omissions of all stakeholders' rights involved in international commercial arbitration. In balancing the funder’s contractual rights to gather information under the third party funding agreement and stakeholders' rights to know, the current research examined how non-disclosure of the third party funding agreement would prevent the arbitrators from fulfilling procedural justice required for the integrity of arbitration on their part and impede the opposing party’s right to know during the proceedings. The research highlights the issues from the delivery of procedural and substantive justice as well as suggesting legal and jurisprudential grounds in third party funding governance. It also points out that all issues examined will ultimately contribute to the failure in delivering justice in international commercial arbitration if third party funding is left to self-governance.
Keywords: Arbitration; International commercial arbitration; Third Party Funding

The UNCITRAL Model Law on International Commercial Arbitration: Interpretation, General Principles and Arbitrability - Viscasillas, Pilar Perales (Journal of Law, Society and Development, 2016)
This article explores the possible modification of the UNCITRAL Model Law on International Commercial Arbitration (MAL) to include the topic of arbitrability. This is an area in which the domestic legal systems differ, particularly in relation to the arbitrability of intra-corporate disputes. The article also deals with new art 2A, introduced into the Model Law in 2006, which deals with the interpretation and gap-filling system under the Model Law. The interpretation of MAL in accordance with its international character is a very important step towards uniformity and therefore the different tools required for a uniform interpretation are analysed. These include case law and scholarly writings; the meaning and importance of achieving both a uniform and an international interpretation of MAL are also considered. The article also analyses the whole text of MAL in order to arrive at the general principles on which the Model Law is based; when problems have to be solved, these principles should guide issues of interpretation that arise under this law.
Keywords: Arbitrability; Arbitration; General principles; Interpretation; UNCITRAL

Arbitrability and public policy: an African perspective. - Mante, Joseph (Arbitration international, 2016)
Growth in international trade has led to considerable expansion of the scope of matters capable of settlement by arbitration. In spite of sustained scholarly activity on arbitrability, the question of what is arbitrable remains controversial but relevant in many regions of the world, including Africa. Arbitrability has the potential to affect the validity of an arbitration agreement, strip an arbitrator of jurisdiction, or derail enforcement of an award. Given the significance of the concept, it is vital that entities involved in international transactions do not speciously extrapolate knowledge of what pertains in Europe and America across all jurisdictions and regions of the world. This study draws a comparison between arbitrability and its relationship with public policy in Europe and America on one hand, and the trend in Africa in an attempt to critically investigate the extent to which African states are willing to extend the scope of arbitrable subject matters. A number of trends on arbitrability are discernible. Most commercial disputes are arbitrable and this observation generally aligns with practice in Europe and America. Beyond this, there are three significant differences in the areas of scope of subject matter, approaches to arbitrability regulation and the role of public policy.
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Policy

A mediação incidental como meio de solução dos conflitos trabalhistas individuais: a questão da dispensa de trabalhadores detentores da garantia provisória no emprego - Santos, Ricardo Goretti; Leite, Carlos Henrique Bezerra (Espaço Jurídico Journal of Law, 2016)
Resumo: Este artigo versa sobre a prática da mediação incidental no processo do trabalho e sua potencial contribuição para a efetiva solução de conflitos decorrentes da dispensa de trabalhadores dotados de garantia provisória do emprego. Acusa o uso desordenado da conciliação incidental, indiscriminadamente aplicada na solução de conflitos individuais situados no âmbito de relações trabalhistas, tanto circunstanciais quanto continuadas. Busca responder ao seguinte problema de pesquisa: a prática da mediação judicial incidental na Justiça do Trabalho pode contribuir para a efetiva solução de conflitos decorrentes da dispensa do trabalhador dotado de garantia provisória do emprego? Estabelece as bases do fenômeno da difusão dos métodos alternativos de solução de conflitos, no contexto do movimento universal de acesso à justiça. Desenvolve considerações sobre particularidades da conciliação e da mediação, destacando os aspectos principais de distinção entre elas. Finalmente, avalia a aplicação dos métodos autocompositivos, considerando as particularidades das controvérsias decorrentes da dispensa de trabalhadores dotados de garantia provisória no emprego. Conclui que, por objetivar a exploração aprofundada dos interesses em jogo, o fortalecimento do diálogo e da relação entre as partes, além do empoderamento dos envolvidos, a mediação judicial incidental seria a via mais adequada para a administração de conflitos decorrentes da dispensa de trabalhadores com garantia provisória do emprego. Além isso, evidencia uma proposição legislativa sobre o tema, já submetida à apreciação da Comissão de Juristas responsável pela elaboração do Anteprojeto de Lei de Arbitragem e Mediação, do Senado Federal.
Keywords: Arbitrage (droit du travail); Arbitragem; Arbitration; Conciliation (droit du travail); Conciliação trabalhista; Despedida arbitrária; Garantia no emprego; Labour dispute; Mediation; Mediação trabalhista; Médiation; Resolução alternativa de conflitos

L’arbitrage en droit espagnol des sociétés, à l’aune du droit comparé - Correa Delcasso, Jean-Paul (La Lettre, 2016)
Dans la présente étude, l’auteur expose l’évolution qu’a connue la pratique de l’arbitrage en droit espagnol depuis ses débuts. Il analyse, d’un point de vue pratique, les principales solutions dégagées par la jurisprudence espagnole, en ce qui concerne l’arbitrabilité d’un grand éventail de litiges, question qui s’est traditionnellement posée en droit espagnol. Il compare la situation avec celle d’autres systèmes juridiques européens culturellement proches.

Admission de la question préjudicielle posée par le juge de l’annulation de la sentence - Posocco, Laurent (La Lettre, 2016)
Le juge de l’annulation de la sentence arbitrale internationale a la faculté de demander à la Cour de justice de l’Union européenne (CJUE) de statuer sur une question d’interprétation du Traité sur le fonctionnement de l’Union Européenne (TFUE) en vertu de son art. 267.

Bonne foi de l’avocat dans la mise en œuvre de la clause compromissoire - Posocco, Laurent (La Lettre, 2016)
Ayant fait ressortir que les parties avaient eu la volonté de se soumettre à l’arbitrage, l’exigence de bonne foi pouvait leur être opposée et que les pouvoirs du cabinet d’avocats émirati étant apparents, la croyance de la société d’avocats londonienne mandatée à l’engagement des parties était légitime, la cour d’appel en a exactement déduit que le tribunal arbitral était compétent.

La responsabilité de l’arbitre et son assurance - Raibaut, Jacques (La Lettre, 2016)
La figure de l’arbitre, comme celle du juge, paraît étrangère à la responsabilité tant domine l’image de la fonction recherchée par le justiciable : dénouer le conflit qui les oppose. Au-delà de la déception que peut susciter la décision rendue chacun admet que l’indépendance, l’impartialité et la compétence sont inhérents à cette fonction et justifient que l’arbitre bénéficie d’une immunité juridictionnelle de principe qui le met à l’abri du ressentiment d’une ou des parties.

An Introduction and an Evaluation of Arbitration in Ivory Coast - Kalle, Aurélie (Recht in Afrika, 2016)
The paper deals with arbitration law in Ivory Coast and is mainly based on interviews with the most important authorities in this field. After a short introduction into the OHADA legal system the two main arbitration centres of Ivory Coast are presented. First, the paper treats the internationally known OHADA arbitration centre of the Common Court of Justice and Arbitration, hereinafter known as CCJA. It explains the bodies and the organisation of the CCJA, the arbitration procedure in detail, the enforcement of the arbitral award, the interim measures and the legal remedies against decisions of the CCJA. Second, the functioning of the Court of Arbitration of Côte d'Ivoire, hereinafter known as CACI, is explained. It is the second arbitration centre of Ivory Coast and it was created by the Ivorian Chamber of Industry and Commerce and settles mainly disputes between nationals. The analysis treats the same topics as mentioned for the CCJA centre, but is restricted to point out the differences or peculiarities of the CACI procedure, in order to prevent repetitions. Third, the paper analyses the advantages and disadvantages of the two arbitration centres and compares them to the proceedings of the Commercial Court of Abidjan. It avoids the comparison of yet well-known arguments such as confidentiality of arbitration proceedings or the parties' free choice in regard to the place of arbitration and the language, etc. The work rather limits itself to concretely address the problems or the advantages of each dispute solution considering the latest developments in the judicial system. The purpose of the report is to give a practical introduction into the Ivorian arbitration law, in particular to foreign lawyers. It should provide them with solid theoretical knowledge of the different dispute solutions. With the help of concrete comparisons and explanations of the actual situation regarding the civil and commercial judicial system it should enable them to find the most suitable dispute solution for their clients.
Keywords: Arbitrage; Arbitragem; Arbitration; Côte d'Ivoire; Ivory Coast

Contrariétés entre jugements étatiques et sentences arbitrales dans l'espace OHADA - Castellane, Béatrice (Penant : revue trimestrielle de droit africain, 2016)

LLCs and the Private Ordering of Dispute Resolution - Molk, Peter; Winship, Verity (The Journal of Corporation Law, 2016)
An emerging question in U.S. business law is how the organizational documents of a business entity set the rules for resolving internal disputes. This practice is routine in commercial contracts, which may specify where or how disputes must be resolved. Recent use of litigation provisions in corporation charters and bylaws have sparked controversy, ultimately leading to legislative action to preserve shareholder suits from contractual waiver. Yet despite accounting for the majority of business organizations and sharing features with corporations, non-corporate business entities and their internal dispute resolution process have been largely ignored. How do these non-corporate entities set ex ante rules for resolving disputes among their constituents? This paper begins to map this uncharted area with an empirical study of the practice of limited liability companies (LLCs). We find widespread use of contract to alter the default dispute resolution practices. This study helps not only to inform the evolving statutory and judicial framework for LLC regulation, but also to predict how corporations may respond in the future to recent judicial and legislative changes.
Keywords: Arbitration; Dispute resolution; Fee shifting; Forum; LLCs; Litigation; Operating agreements

Direct actions and arbitration: all at sea - Briggs, Adrian (Lloyd's Maritime and Commercial Law Quarterly, 2016)

Arbitration and Justice Denial on Foreign Direct Investment - Hendrawan, Daniel (Indonesian Journal of International Law, 2016)
The economic growth in Indonesia is thrive. The Economic growth can not be separate of the role of investment in Indonesia. The population in Indonesia very much and also the location of the Indonesian state strategic pretty much made Indonesia enjoyed by citizens of Indonesia itself and also foreign nationals who wish to also invest in Indonesia. In Indonesia there is a domestic investment and foreign investment. In this paper will be devoted to foreign investment. Foreign investment that currently exist in Indonesia has a sizeable amount and spread from Sabang to Merauke, and also has sometimes caused the dispute. Dispute occurs either the foreign investment by government or also foreign investment with other parties outside the government well with other foreign investment, and also in the company itself. Foreign investment dispute settlement is not only done through the court owned by the government, but there are also ways of alternative dispute resolution outside the court . One of the alternative dispute resolution outside the court is Arbitration. Arbitration carried out as part of efforts to achieve settlement of the problem in terms of investment activity . Arbitration itself is set in the legislation applicable investment in Indonesia . The parties in capital investment may create a separate section in the agreement governing the settlement of disputes in the case of investments completed by Arbitration. In the event that the parties have arranged to settle the case with Arbitration, then the court is not allowed to try again or to interfere in the decision Arbitration. Arbitration is one of the solutions if justice denial occur in the settlement of foreign direct investment issue.
Keywords: Alternative; Arbitrage; Arbitragem; Arbitration; FDI; Foreign direct investment

Due Process of Law in International Commercial Arbitration with Special Reference to Production of Documents - Zaheeruddin, Mohammed (Journal of Law and Criminal Justice, 2016)
Arbitration provides speedy mode of settlement of disputes between the parties. In the course of arbitration, the arbitration tribunal has an obligation to give a fair opportunity to the parties to present their case. The fair hearing or due process of law in arbitration requires that both parties must be treated equally and given opportunity to be heard, which include a party may request the other party for production of documents, which are relevant to the case. Hence, the international arbitration rules contained the provisions to order a party, on its own or on the request of a party, to produce the documents relevant to the outcome of the case. Unless otherwise agreed by the parties, any denial of this opportunity may be considered as a violation of due process of law, consequently a party may challenge the enforcement of the award.
Keywords: Arbitrage; Arbitragem; Arbitration; Discovery; Due process of law; Production of document; UNCITRAL

Online dispute resolution: The future of justice - Mania, Karolina (International Comparative Jurisprudence, 2015)
The purpose of this study is to present the main facets of online dispute resolution, including a definition of the term, the types of resolution available, and the most recent legal regulations in this area. The article is an in-depth study of this field, discussing online mediation and electronic arbitration, their uses and their relationships with e-commerce. The strengths and weaknesses of online dispute resolution are identified and used to help formulate de lege ferenda stipulations. The paper is divided into three parts. Part I looks at preliminary aspects of online dispute resolution (ODR), including a definition of the term and an examination of its phases of development, implementation examples and the relationship between ODR and technology. Part II is devoted to examining the two most frequent forms of ODR: online mediation and electronic arbitration. Part III is an analysis of consumer disputes arising from commercial transactions made using electronic communications. As an example of the implementation of ODR, the author emphasises the importance of new European regulations on that and alternative dispute resolution (ADR): Directive 2013/11/EU of the European Parliament and of the Council of 21 May 2013 on alternative dispute resolution for consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC (Directive on consumer ADR), and Regulation (EU) No 524/2013 of the European Parliament and of the Council of 21 May 2013 on online dispute resolution for consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC (Regulation on consumer ODR).
Keywords: ADR; Alternative dispute resolution; Consumer dispute; E-commerce; Electronic arbitration; ODR; Online Dispute Resolution; Online mediation

Building legal bridges: fostering eastern Africa integration through commercial arbitration - Muigua, David K. (Alternative Dispute Resolution, 2015)
This paper explores the feasibility of commercial arbitration as a means to foster the process of Eastern Africa integration. The author proffers an argument in the context of Eastern Africa integration, that commercial arbitration offers a better platform for dealing with commercial disputes that are bound to arise considering the differing personal or state interests in the ongoing Eastern Africa integration, as compared to national Courts. This discourse is premised on the fact that the five member countries making up the East African Community (EAC) have different legal systems and this presents a major challenge in harmonising the various legal systems. This also affects the possible use of courts in managing the potential transnational commercial disputes due to the potentially different rules of procedure and practice. The paper briefly examines the state of commercial arbitration in the EAC Member States with a view to identifying the existing frameworks and any impediments in their effectiveness. Finally, the author makes a case for utilizing commercial arbitration to build bridges and foster Eastern Africa integration for development.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

L’internationalisation du droit public des affaires face à l'arbitrage international : approche comparée en droit franco-maghrébin - Baisset, Didier (Annales de l’Université d’Alger, 2014)
Indiscutablement la sphère du droit public des affaires se déploie aujourd'hui dans un espace mondialisé, où les rapports entre les opérateurs se nouent en des termes qui différent radicalement de ceux qui posèrent les premiers linéaments de la matière au début du XXe siècle. Cela est en réalité lié aux tendances de fond qui touchent le monde contemporain. C'est donc dans un contexte profondément modifié par la globalisation, que les relations d'échanges internationaux et les litiges auxquels elles peuvent donner lieu s'envisagent désormais. On assiste ainsi, depuis déjà plusieurs décennies, à l’émergence d’un véritable droit public international des affaires. A cet endroit, le cas des marchés publics et des partenariats public-privé internationaux est particulièrement révélateur des mutations profondes qui taraudent la matière au niveau international. En effet, l'internationalisation des échanges économiques s'inscrit dans une réalité qui modifie en profondeur l'organisation des acteurs économiques et opère une vaste mutation des modalités d'intervention de la puissance publique; elle se fait maintenant dans un champ économique à l'échelle supra-nationale.

La participation à l'arbitrage des personnes morales de droit public : L’exemple de l’OHADA - Fénéon, Alain (Annales de l’Université d’Alger, 2014)
Dans beaucoup de législations nationales sur l’arbitrage, le principe de la non-arbitrabilité des litiges impliquant les personnes morales de droit public, en particulier l’Etat et les collectivités territoriales, est clairement posé, et ce depuis longtemps. Cette position s’explique aisément dans le système juridique français comme dans ceux qui s’en inspirent. La distinction entre la justice des particuliers et celle de l’administration, c’est à-dire de l’Etat, y est fermement établie.

Arbitrage en droit, arbitrage en équité : perspectives historiques - Juhel, Christophe (Annales de l’Université d’Alger, 2014)
L’expression « modes alternatifs de règlement des conflits » en vogue depuis quelques années et reprise dans l’intitulé de ce colloque est trompeuse. Elle procède d’une vision ethno-centrée moderne et plus spécifiquement occidentale et continentale du règlement des conflits. En effet, le qualificatif « alternatif » est employé par référence au mode de règlement des conflits actuellement privilégié par les sociétés modernes, notamment de la famille romano-germanique: la justice étatique. Or, historiquement, les sociétés traditionnelles les plus anciennes ne connaissaient pas de justice publique mais seulement des modes traditionnels et privés de résolution des litiges pacifiques comme la médiation, la conciliation et l’arbitrage, c’est-à-dire ceux que nous désignons « modes alternatifs de règlement des conflits », ou non pacifiques comme la vengeance privée.

L’arbitrage, une justice citoyenne, émancipée et pragmatique - Raibaut, Jacques (Académie de Législation, 2014)
Keywords: ARBITRAGE; Arbitration

Alternative Dispute Resolution (ADR): An Overview of Some Common Mechanisms, and their Strengths and Weaknesses in Context - Perrin, Harry (The Plymouth Law & Criminal Justice Review, 2014)
Alternative Dispute Resolution, or ’ADR’, offers parties in dispute an alternative to traditional court-based litigation, which is often seen as slow, costly and ineffective. ADR frequently involves a neutral third party who will settle or facilitate resolution of the dispute. This paper examines three common ADR mechanisms, adjudication, arbitration and mediation, and explores their relative advantages and disadvantages in different contexts.
Keywords: ADR; Adjudication; Alternative dispute resolution; Arbitration; Construction adjudication; Mediation; Negotiation

Les contours de l’arbitrage - Posocco, Laurent (La Lettre, 2014)
Les frais d’arbitrage peuvent compromettre l’accès au juge. L’exclusion de l’arbitrage comme méthode de recours à l’encontre d’une ordonnance du juge commissaire. Il ne revient pas aux parties d’apprécier la nature interne ou internationale de l’arbitrage.
Keywords: ARBITRAGE; Arbitration

L'arbitre et le droit - Prujiner, Alain (Revue de règlement des différends de McGill, 2014)
L’auteur se penche sur la relation qui existe entre l’arbitre et le droit, en focalisant sur les questions de procédure et de droit applicable au fond du litige en arbitrage international. L’auteur montre que les arbitres ne se réfèrent plus automatiquement au droit international privé de l’Etat du siège afin de déterminer le droit applicable à la procédure ou au fond du litige, ni même au droit international privé d’un Etat en particulier. Au contraire, l’auteur avance que la tendance est à l’internationalisation des règles de droit international privé : l’arbitre puise directement les règles de rattachement d’un ordre juridique transnational autonome, qui dispose de ses propres règles de droit international privé, tant pour le fond du litige que pour la procédure arbitrale. The author addresses the relationship between the arbitrator and the law, with an emphasis on the law and procedure that is applicable to international arbitration. It is demonstrated that arbitrators no longer automatically refer to the private international law of the state that is the seat of arbitration to determine the applicable law, nor to private international law rules of a particular country. On the contrary, there is a trend towards internationalizing the rules of private international law: the arbitrator obtains the governing law directly from an autonomous transnational legal system that has its own substantive and procedural rules in private international law.

Common Court of Justice and Arbitration: A Supranational Institution for the Administration of Commercial Disputes in Africa - Ogwezzy, Michael C. (Nordic Journal of Commercial Law, 2013)
Due to the expansion of business transaction across the globe, the private sector demands an adequate legal framework that is sufficiently clear, modern, predictable and transparent to permit investment with a sense of security. The Organisation for the Harmonisation of Business Law in Africa (Organisation pour l’harmonisation en Afrique du Droit des Affaires) is generally known by its French acronym OHADA. As long-standing idea, the foundation of the OHADA Treaty was first laid during a meeting of finance ministers of the members of the franc CFA1 area held in Ouagadougou, Burkina Faso, in April 1991. A group of experts, led by Senegalese Justice Keba Mbaye, was appointed to conduct a feasibility study on a form of legal collaboration designed to promote economic integration and attract investments.2 Identifying low investment as a major obstacle to economic growth, Keba Mbaye presented his report to the French-speaking African summit in Libreville, Gabon, in October 1992, recommending the creation of a supranational organization comprising the entire franc area. The recommendation was adopted and a steering committee of three experts were appointed and tasked with drafting an international instrument as well as identifying the areas of law to be harmonized. The OHADA was established through the treaty of Port Louis in Mauritius on 17th October, 19933 The treaty is open to any Member State of the Organization of African Unity (AU) as well as any other non-member of the AU invited to join with the common agreement of all the Member States.4 The OHADA has progressively become the common business law in anglophone and francophone African countries, taking the best from the civil law and the common law systems.5 The OHADA provides its Member States with 1) a single, modern, flexible and reliable business law adapted to each country’s economy; 2) arbitration as an appropriate and trustworthy way to settle disputes; and 3) an opportunity for training judges and judicial staff and ensuring their specialisation. In May 2003, the uniform OHADA business law came into force in the sub-Saharan African States of Benin, Burkina Faso, Cameroon, Central African Republic, Comoros, Congo, Ivory Coast, Gabon, Guinea, Guinea Bissau, Equatorial Guinea, Mali, Niger, Senegal, Chad, Togo and later the Democratic Republic of the Congo. The OHADA Treaty secures a legal framework for the conduct of business in Africa.6 Pursuant to Article 53 of the OHADA Treaty, any member State of the African Union may become a member, if it wishes to do so.7 Many countries are currently giving active consideration to joining the OHADA common system of business law.8 Most of the countries have a French colonial heritage, with the exception of the Democratic Republic of the Congo (former Belgian colony), Guinea-Bissau (former Portuguese colony), Equatorial Guinea (former Spanish colony), and Togo and Cameroon (formerly under partly British and partly French colonial rule). French is also an official language in most of the countries and many OHADA sources are only available in French. 9 It is interesting to know that the Council of Ministers of the OHADA organisation which is the legislative organ of the organisation have adopted the following uniform business law: the general commercial laws, corporate laws and rules concerning different types of joint ventures, laws concerning secured transactions, debt recovery and enforcement laws, bankruptcy laws, arbitration law, accountability law, and law regulating contract for the carriage of goods by roads.10 The OHADA treaty established the Common Court of Justice and Arbitration (CCJA) which is a supranational11 judicial institution based in Abidjan, Ivory Coast.12 2.

Written Arbitration Agreements: What Written Arbitration Agreements? - Yu, Hong-Lin (Civil Justice Quarterly, 2013)
First paragraph: This article considers the issue of an oral arbitration agreement in relation to the New York Convention. As Townsend once said "[a]rbitration offers a means to an end, and the end is to the resolution of disputes." This end would be extremely difficult to achieve without the approval of national courts. Fortunately, with 146 signatory countries signed on the New York Convention on the Recognition and Enforcement of Arbitral Awards 1958 (The New York Convention), the success of this Convention has attracted businessmen into using arbitration to resolve their disputes. Nevertheless, a voluntary arbitration cannot be commenced without a valid arbitration agreement. Setting out to achieve harmonisation in the enforcement of arbitration agreements, art.II of the New York Convention provides the written requirements to be followed by all 146 signatory countries. Accordingly, written requirements for arbitration are imposed upon all signatory countries and they are obliged under the convention to recognise all arbitration agreements which are made in writing.
Keywords: Arbitration agreements; Comparative law; Convention d'arbitrage; France; New York Convention awards; New Zealand; Oral contracts; Scotland

From Port Louis to Panama and Washington DC: Two Regional Approaches to International Commercial Arbitration - Bashi Rudahindwa, Jonathan (European Journal of Law Reform, 2012)
In recent decades, regional efforts have been made to reform and harmonize the rules governing international arbitration. These efforts have resulted in the adoption of regional instruments governing commercial arbitration in specific areas. This paper analyzes the arbitration regimes created at a regional level in Africa and America, and particularly focuses on arbitral institutions that were created within the Organization for Harmonization of Business Law in Africa (OHADA) and within the Organization of American States (OAS). The objective of the paper is to identify any advantages provided by either regime, which can help improve regional and international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

Arbitrability in the context of Ghana's new arbitration law. - Mante, Joseph; Ndekugri, Issaka (International arbitration law review, 2012)
Examines the approach of Ghana's Alternative Dispute Resolution Act 2010 to the question of arbitrability. Reflects on the concept of arbitrability under international law, the relevant trends emerging from case law, and the approach adopted by the Ghanaian High Court in Attorney General v Balkan Energy LLC. Reviews the Act's arbitrability exemptions, their implications for international arbitration in Ghana, the potential jurisdictional challenges under the legislation and how its provisions could be amended to increase its conformity with international trends on arbitrability.
Keywords: Arbitrability; Arbitrage; Arbitragem; Arbitration; Comparative law; Ghana; International commercial arbitration; Jurisdiction

Reflections on finality in arbitration - Roodt, Christa (De Jure, 2012)
Ondersoek na die Finaliteit van 'n Arbitrasiebevel Hierdie artikel oorweeg die Telcordia- en Lufuno-sake vanuit die oogpunt van die finaliteit van 'n arbitrasiebevel. Die vraag wat te berde kom, is wanneer 'n arbitrasiebevel finaliteit bereik waar 'n saak voor meer as een forum (arbitrasie en staatlike howe), in meer as een jurisdiksie gevoer word. Die prosedurele meganismes wat Amerikaanse en Suid-Afrikaanse howe tydens die Telcordia-dispuut toegepas het asook hul onderskeie benaderings tot res iudicata, het 'n groot mate van ooreenstemming getoon. Dit is te verstane dat die afhandeling van 'n internasionale proses vertraag kan word deur bepaalde grondwetlike regte wat die spoed van die afhandeling van 'n saak kan beïnvloed. Nietemin, indien die reg op 'n billike verhoor op enige stadium in die verrigtinge gepleit mag word, word 'n geleentheid geskep vir die dispuut om vryelik te eskaleer gedurende die verhoor. Dit kan die hofproses oopstel vir misbruik en die afhandeling van die geskil vertraag. Die minderheidsbeslissing in Lufuno skenk 'n mate van oorweging aan die potensiële negatiewe implikasies hiervan. Die finaliteit van die geskilbeslegtingsproses kan na behore bestuur word aan die hand van 'n wyer interpretasie van res iudicata in internasionale dispute en 'n meer geredelike ondersoek hierna, op die hof se inisiatief. Die moontlikheid dat die Telcordia-dispuut verder bespoedig sou kon word, word ondersoek met verwysing na die New York Konvensie op die Erkenning en Afdwing van Arbitrasiebevele van 1958, en aan die hand van aanbevelings wat deur ander gerekende internasionale liggame uitgereik is.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration

Arbitrage transnational et droit international général (2012) - Jacob, Patrick; Latty, Franck (Annuaire Français de Droit International, 2012)

Duty of Confidentiality: Myth or Reality? - Yu, Hong-Lin (Civil Justice Quarterly, 2012)
Explores the extent to which there is a duty of confidentiality in relation to the information used in arbitration proceedings. Considers how the duty is regulated by arbitration rules in different countries and whether there is a sufficient consensus to develop an internationally accepted principle of duty of confidentiality. Discusses which jurisdictions have an implied duty of confidentiality in the parties' arbitration agreement. Looks at how confidential information is defined in different jurisdictions, who is bound by the duty of confidentiality and the exceptions to the duty.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Confidential information; Confidentiality; Confidentialité; Information confidentielle

L'arbitrage CCJA - Wambo, Jérémie (Revue de l'ERSUMA, 2011)
L’arbitrage est désormais une institution traditionnelle de la vie des affaires sur le plan national, mais aussi et surtout sur le plan international. C’est un « mode alternatif de règlement des litiges qui consiste à faire trancher un différend par de simples particuliers », qui peuvent être des « personnes choisies par les parties »115. On distingue généralement deux types d’arbitrage, l’arbitrage Ad Hoc, qui demeure le plus fréquent, et l’arbitrage Institutionnel. Mais notre discussion va beaucoup plus porter sur le deuxième type d’arbitrage à travers le Centre d’arbitrage de la Cour Commune de Justice et d’Arbitrage de l’OHADA. Les signataires du Traité de Port Louis (Traité OHADA) du 17 Octobre 1993 avaient, dès le préambule, exprimé leur désir de « promouvoir l’arbitrage comme instrument de règlement des différends contractuels ». C’est pourquoi l’article 1er dudit Traité qui définit ses objectifs précise qu’il est question entre autres d’encourager le « recours à l’arbitrage pour le règlement des différends contractuels ». Les articles 21 à 25 posent les bases de cet arbitrage. La concrétisation de ces intentions s’est manifestée par l’adoption à Ouagadougou par le Conseil des Ministres de l’OHADA le 11 Mars 1999, de l’Acte Uniforme relatif au Droit de l’Arbitrage, et du Règlement d’Arbitrage de la CCJA qui fixe les règles applicables à l’arbitrage CCJA. Plusieurs textes ont été pris par la suite qui ont permis d’organiser l’arbitrage CCJA (I) afin de rendre lisible le professionnel le déroulement de procédure arbitrale.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Procédure arbitrale; Règlement d'arbitrage

Effectiveness and Remedies of the Arbitral Awards in OHADA’s System and in People’s Republic of China. - Samassekou, Mamoudou; Lianbin, Song (Journal of Politics and Law, 2011)
Today the arbitral justice has experienced an exceptional development. It is a universal phenomenon which requires the involvement of all economic and legal players of developed and developing countries.OHADA is a common business law and wish to secure legal security for regional and foreign economic agents by offering a vast economic space. The People’s Republic of China (PRC) is an emerging country which increases its economic outlets in a context of globalization. This natural interdependence will increase the scope of economic exchanges, which may generate some disputes in businesses. This article aims to compare two legal systems in the international commercial arbitration field: the legal system of OHADA and the PRC’s legal system; especially in the effectiveness and the remedies of the arbitrators’ decisions.

Dispute Resolution in International Electricity Trade - Han, Baoqing (Energy Procedia, 2011)
International electricity trade disputes can arise at three key levels: state to state; investor to state; private party to private party. Parties may be more open to submission of their disputes to international arbitration. However, they should make proper arbitration options according to the types of disputes. At the same time, considering the risks facing dispute resolution, it is imperative to specifically design effective tools to mitigate these risks.
Keywords: Dispute resolution; Disputes; International Arbitration; International electricity trade; Risk mitigation

Arbitration: One Size Does Not Fit All: Necessity of Developing Institutional Arbitration in Developing Countries - Namrata Shah, Niyati Gandhi (Journal of International Commercial Law and Technology, 2011)
Litigation in developing countries has many defects which has prompted a need for the development of alternative dispute resolution mechanisms. Arbitration, being one such substitutive mechanism as a type of private litigation is the most suitable for the same. This paper deals with the need to develop institutional arbitration to co-exist with ad hoc arbitration and scale it down to be available for dispute resolution in developing countries using an illustration of India. Certain recommendations to make institutional arbitration, which is considered to be appropriate for International commercial dispute resolution, suitable for domestic disputes in developing countries have been highlighted.
Keywords: Arbitrage; Arbitragem; Arbitration; Developing countries; Institutional arbitration

Les MARC en OHADA (Journal africain du droit des affaires, 2011)
GENERALITES SUR LES MARC La justice arbitrale La médiation commerciale : une alternative au système judiciaire L’utilité de l’expertise Interactions entre médiation et arbitrage LES MARC EN OHADA Approche culturelle des MARC en OHADA Regards franco-africains sur les étapes de la médiation commerciale La gestion d’une procédure d’arbitrage : vue d’un opérateur économique de l’espace OHADA Analyse comparée du droit de l’arbitrage OHADA et du droit international L’arbitrage de la Cour Commune de Justice et d’Arbitrage (CCJA) de l’OHADA Nouveau Règlement de médiation de la Cour d’Arbitrage de Côte d’Ivoire (CACI)
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Mediation; Médiation

A comparative study: Arbitration agreement in OHADA and People's Republic of China arbitration laws - Samassekou, Mamoudou; Song, Lianbin (Journal of Politics and Law, 2011)
This article aims to compare the arbitration agreement of the OHADA legal system to that of the People's Republic of China. In the Chinese legal system the parties to a contract are required to have an arbitration agreement written before the occurrence of any incident in the execution of their contract. The parties must specify in advance, in the said agreement, the chosen arbitration institution for potential disputes. In the OHADA legal system, the parties are free to decide before or during execution of the contract of an arbitration agreement. They may also decide whether in case of a dispute, they would want to refer to an institutional arbitration or an ad hoc arbitration. According to the chosen legal system the consequences are different.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; China-OHADA

L’ordre juridique arbitral : réalité, utilité et spécificité - Gaillard, Emmanuel (McGill Law Journal, 2010)
L’ordre juridique arbitral existe-t-il ? S’il est perçu par les arbitres, souvent de manière intuitive mais très réelle, c’est qu’il existe. L’ordre juridique arbitral ne doit pas cependant être exclusivement conçu comme une représentation mentale du rôle des arbitres et de la source de leur pouvoir de juger. Il existe en tant que système de droit.

Enforcement of Arbitral Awards in Sub-Sahara Africa - Onyema, Emilia (Arbitration International, 2010)
As the world celebrated the fiftieth anniversary of the New York Convention in 2008 it became necessary to examine the enforcement regimes for arbitration awards in Sub-Sahara Africa. This article examines the provisions for the recognition and enforcement, and requirements for the setting aside of both domestic and international arbitral awards under the arbitration laws of OHADA member states, Nigeria and Sudan, as representative of the legal regimes in Sub-Sahara African countries. The New York Convention applies to Convention awards in half of the countries of Sub-Sahara Africa. It is therefore relevant to examine the requirements for the enforcement of non-Convention awards in those states that are members of the New York Convention, and also in those states that are not members of the New York Convention. Different arbitration laws and regimes apply in the three representative jurisdictions chosen for this comparative analysis and these are also representative of the legal regimes in those countries with arbitration laws in the region. Though a generally supportive tendency towards the enforcement of arbitral awards can be gleaned from the examination of some arbitration-related judgments, this article again highlights the importance for the remaining countries in the region yet to sign up to and implement the New York Convention to consider adopting it, and for more arbitration hearings to be held within the region.
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Enforcement of Arbitral Awards; Sub-Sahara

Waiver of a Right to Arbitrate by Resort to Litigation, in the Context of International Commercial Arbitration - Gillies, Peter; Dahdal, Andrew (Journal of International Commercial Law and Technology, 2007)
This paper examines the circumstances in which a party to an arbitration agreement may be deemed tohave waived its right to arbitrate a dispute comprehended by the agreement, by involvement in litigation concerning this dispute. The focus is on the law in common law jurisdictions, particularly Australia and theUnited States of America. United Kingdom law will also be briefly surveyed. The paper focuses on the 2006 decision of the Australian Federal Court in Comandate Marine Corp v Pan Australia Shipping Pty Ltd, whichafforded the topic significant treatment. The theoretical bases for sustaining waiver claims are analysed, includingwaiver as a discrete doctrine, abandonment, estoppel, election, repudiation of contract and variation of contract.The policies that underlie and inform the development of principles for testing waiver submissions are noted.

'Legal Traditions' and International Commercial Arbitration - Trakman, Leon (University of New South Wales, 2007)
Codes, laws and guidelines governing international commercial arbitration developed by such organizations as the International Court of Arbitration, the International Bar Association and the International Chamber of Commerce have been drafted against the background of Common Law and Civil Law values. In balancing these two great legal traditions, it was assumed that together they represent a composite legal tradition governing international commercial arbitration. The result of that assumption was decades of fine work enshrining international arbitration doctrines, principles, and rules of law and procedures that blend these two important legal traditions. More recent concerns have begun to raise such questions as: How pervasive are the Common and Civil Law traditions? Part I of this article asks: What is a legal tradition and how should it be distinguished from a legal culture in relation to international commercial arbitration? Part II reflects on the influence of legal culture on international commercial arbitration. Parts III, IV and V investigate the Common and Civil legal traditions in relation to national, regional and international commercial arbitration. Part VI evaluates the public traditions that surround international commercial arbitration. Part VII considers whether change in the traditions of international commercial arbitration represent culture change or culture shock. Part VIII emphasizes the value of building an inclusive international arbitration tradition. Part IX suggests ways in which international commercial arbitration can accommodate diffuse and changing local, regional and global influences upon it. Codes, laws and guidelines governing international commercial arbitration developed by such organizations as the International Court of Arbitration (ICA), the International Bar Association (IBA) and the International Chamber of Commerce (ICC) have been drafted against the background of Common Law and Civil Law values. In balancing these two great legal traditions, it was assumed that together they represent a composite legal tradition governing international commercial arbitration. The result of that assumption was decades of fine work enshrining international arbitration doctrines, principles, and rules of law and procedures that blend these two important legal traditions. From the doctrine of freedom of contract to specific rules of evidence and procedures that govern arbitral hearings, the international arbitration community has sought to maintain the respected legal traditions that lawyer-arbitrators and counsel find familiar and comfortable. More recent concerns, partly expressed by William K. Slate II, President of the American Arbitration Association, have begun to raise such questions as: How pervasive are the Common and Civil Law traditions? Are they sufficiently uniform in nature and operation to justify their dominant status in formulating codes, laws and rules governing international commercial arbitration? And has international commercial arbitration become unduly reliant upon both the Common and Civil Law traditions at the expense of other legal traditions that operate against the background of different and changing legal cultures? Part I of this article asks: What is a legal tradition and how should it be distinguished from a legal culture in relation to international commercial arbitration? Part II reflects on the influence of legal culture on international commercial arbitration. Parts III, IV and V investigate the Common and Civil legal traditions in relation to national, regional and international commercial arbitration. Part VI evaluates the public traditions that surround international commercial arbitration. Part VII considers whether change in the traditions of international commercial arbitration represent culture change or culture shock. Part VIII emphasizes the value of building an inclusive international arbitration tradition. Part IX suggests ways in which international commercial arbitration can accommodate diffuse and changing local, regional and global influences upon it.

Arbitrage et procès équitable dans la zone sud-ouest de l’Océan indien - Zattara-Gros, Anne-Françoise (Revue internationale de droit comparé, 2007)
L’étude des rapports qu’entretiennent l’arbitrage et le procès équitable dans les différents droits des îles de la zone sud-ouest de l’Océan indien prend toute sa dimension dès l’instant où la zone offre un patchwork de systèmes juridiques différents. La question est alors de savoir si dans les droits des îles des Grandes Mascareignes, l’arbitrage revêt le costume juridique français, sachant que le Nouveau Code de Procédure civile (NCPC) édicté en France le 5 décembre 1975 a été, suite à l’accession à l’indépendance de ces différentes pays, transplanté à Madagascar, aux Comores et à Maurice. La logique conduirait à répondre par l’affirmative. Mais la diversité du contexte, constitué soit de transposition du droit français de l’arbitrage, qui intègre le modèle de procès équitable notamment défini par l’article 6 de la Convention européenne des droits de l’homme, soit d’érection d’un droit interne de l’arbitrage composé partiellement de dispositions juridiques françaises, offre des situations inédites. Si à l’instar des grandes tendances, l’étude croisée des dispositions relatives à l’arbitrage et celles du procès équitable dans l’Océan Indien révèle une perméabilisation croissante de ce deux dernières sphères, et de là un risque de processualisation de l’arbitrage, l’institutionnalisation de l’arbitrage permet également aux parties, de trouver des garanties, ce qui est pleinement satisfaisant dans des pays où l’État de droit est défaillant et la justice étatique mise à mal de façon à assurer la sécurisation juridique des investissements et des échanges commerciaux. The study of reports stating that arbitration and fair judgment exist in the different laws of the islands in the south western zone of the Indian Ocean takes on a whole new dimension if the zone provides a patchwork of different legal systems. The question is whether or not arbitration is the same as in the French legal system. One must consider that the New Civil Procedure Code (NCPC) which was decreed in France on 5th December 1975, was transplanted to Madagascar, the Comoros Islands and Mauritius. Logic would thus lead one to believe the affirmative. However the diversity of the context, which is constituted either by transposing French arbitration law that integrates the decreed trial model as defined by article 6 of the European Convention of Human Rights, or the erection of internal arbitration law composed partially of French legal dispositions, provides some new situations. If, in accordance with the trends, the cross study of dispositions relative to arbitration and those of the fair trial in the Indian Ocean reveal that these two spheres are growing, and that a result of this there is a risk of procedure arbitration, the institutionalization of arbitration also allows for the concerned parties to find guarantees, which is very satisfying for countries whose state law is weak and where state justice has difficulty in ensuring legal security for investments and commercial exchange.

The Role of International Arbitrators - Franck, Susan D. (ILSA Journal of International & Comparative Law, 2006)

The Contractarian Model of Arbitration and Its Implications for Judicial Review of Arbitral Awards - Kirgis, Paul F. (Oregon Law Review, 2006)

Harmonizing Business Laws in Africa: Ohada Calls the Tune - Dickerson, Claire Moore (Columbia Journal of Transnational Law, 2005)
OHADA (in English, Organization for Harmonization in Africa of Business Laws) is a system of business laws and implementing institutions. Sixteen West African nations adopted this regime in order to increase their attractiveness to foreign investment. Because most of the member states are former French colonies, the OHADA laws are based on the French legal system. Despite certain economists’ recent, well-publicized assertions that any French-based legal system is incompatible with development, other studies challenge those claims and in doing so outline characteristics that a pro-development system of business laws should possess. This Article reviews selected provisions from OHADA’s corporate law and of OHADA’s institutions, revealing that they correspond to those pro-development characteristics. Interviews conducted with legal professionals in Senegal, Côte d’Ivoire, and Cameroon highlight the local perception that the OHADA regime, while still
Keywords: Africa; Claire Moore Dickerson; Harmonizing Business Laws; OHADA; SSRN

O processo de composição do Tribunal arbitral internacional e o seu funcionamento - Vescovi, Luiz Fernando (Espaço Jurídico Journal of Law, 2005)
O presente trabalho vem a delinear, sob forma objetiva, o efetivo escopo de um Tribunal Arbitral, ponderando as suas características e o comprometimento com as partes que a elegem. Apresenta o procedimento e o processo de como se constitui um tribunal dessa espécie, assim como as vantagens existentes quando da sua utilização. Enfatiza, de plano, a escolha dos apreciadores do juízo arbitral, assim como a análise circunstancial sobre a incidência da Lei de Arbitragem brasileira à luz do Direito supranacional. Enaltece a viabilidade jurídica (segurança e validade) que o instituto arbitral expressa, concernente às disposições principiológicas que dele decorrem. Ainda, descreve, de maneira esmiuçada, a forma de como o Tribunal Arbitral se compõe, sua competência, prerrogativas, e finalidades, bem como do funcionamento efetivo, no plano do Direito Internacional Privado.
Keywords: Composição; Direito Internacional Privado; Tribunal Arbitral

Les recours dilatoires contre les sentences arbitrales devant la Cour d'Appel de Paris (Analyse des décisions rendues entre janvier 1996 et décembre 2000) - Mantilla Espinosa, Fabricio (Estudios Socio-Jurídicos, 2003)
Este artículo está basado en el ensayo realizado en mayo de 2001, bajo la dirección de los doctores Jean de Hauteclocque y Christian Larroumet del departamento Contentieux et Arbitrage de la firma de abogados Lovells en París.

L’arbitrage international en Afrique : quelques observations sur l’OHADA - Boivin, Richard; Pic, Pierre (Revue générale de droit, 2002)
Avec le Traité relatif à l’Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) de 1993, l’Acte uniforme relatif au droit de l’arbitrage et le Règlement d’arbitrage de la Cour commune de justice et d’arbitrage (CCJA) de 1999, l’arbitrage international a fait une entrée remarquée en Afrique francophone. Dans cet article, les auteurs esquissent une vue d’ensemble du fonctionnement et des mécanismes de l’arbitrage OHADA.
Keywords: Arbitrage; Arbitrage international; Arbitragem; Arbitration; International Arbitration; OHADA

La portée internationale de l'annulation de la sentence arbitrale dans son pays d'origine - Fouchard, Philippe (Revue de l'arbitrage, 1997)
Keywords: Annulation; Sentence arbitrale

L’arbitrage en réassurance : la fin d’une idylle ? - Havens III, Charles W (Assurances, 1992)
In order to avoid resorting to the courts when faced with litigation, insurers and reinsurers have favored arbitration services. Today, arbitration and reinsurance no longer live in harmony. Charles W. Havens III, Partner of LeBoeuf, Lamb, Leiby & MacRae, an American law firm, explains why with numerous examples.

Internationales Schiedsverfahrensrecht: Doppelexequatur - Anderegg, Kirsten (Rabels Zeitschrift für ausländisches und internationales Privatrecht, 1989)